Genome sequencing reveals genes under selection for olfactory transduction in highland sheep - Anees Ahmad; Muhammad Ibrahim; Muhammad Yaqoob; Muhammad Fahim; Sher Hayat Khan; Israr Ud Din; Majid Khan; Sohail Ahmad (Molecular Genetics and Genomics, 2026)
Kutta is an indigenous sheep breed found in the mountainous region of Swat, Pakistan. In this study we evaluated the performance of Kutta sheep within their natural habitat and identified genomic regions associated with environmental adaptability using whole genome sequencing. Flocks are mostly managed under a transhumant production system with year-round breeding. Kutta sheep demonstrated higher lambing efficiency under the available resources. Although the body size of rams and ewes was comparable, significant variation was observed among different age groups. Whole genome sequencing identified 15.46 million variants relative to Oar_v1.0 reference genome assembly. Exonic variants accounted for 2.3% of all protein coding gene variants and affected 6347 genes. These genes were primarily enriched in pathways related to G protein-coupled receptor signaling (700 genes) and olfactory transduction (500 genes). Selective sweep analysis detected 1930 genes within the regions of high homozygosity across the genome. Based on homozygosity patterns, biological relevance, and colocalization with known QTLs, 11 candidate genes were identified as putative selective signature. Five of these genes (OR4C6L, OR1086L, OR5AK2L, QR5T2L, OR9Q2) belonged to the olfactory receptor family. These olfactory receptor genes may contribute to high-altitude adaptation in Kutta sheep by enhancing their ability to locate food resources, recognize mates, and detect predators in challenging mountainous environments. Further screening of the OR4C6L sequence across 12 indigenous sheep breeds revealed marked differences between highland and lowland populations. Collectively, these findings provide comprehensive genomic insights into high-altitude adaptation of sheep and highlight the potential role of olfactory perception in survival and environmental fitness.

Generational selection, transcriptomics and functional characterization reveal the impact of environmental pollutants on the evolution of insecticide resistance in malaria vectors - Abdullahi Muhammad; Sulaiman S. Ibrahim; Helen Irving; Talal Al-Yazeedi; Jack Hearn; Mark J.I. Paine; Charles S. Wondji (Insect Biochemistry and Molecular Biology, 2026)

Satellite-anchored UAV sensing system for high-resolution soil moisture mapping - Muhammad Ibrahim Rana; Hamza Rafique; Hassan Jaleel (Computers and Electronics in Agriculture, 2026)

Evolution of Maastrichtian paleoproductivity along the southern Tethys margin (Jordan): From upwelling to runoff - Maria Ardila-Sanchez; Jihede Haj Messaoud; Amir Kalifi; Khalil Ibrahim; Muhammad Usman; Israa S. Abu-Mahfouz; Samer Aljurf; Volker Vahrenkamp; John H. Powell; Frans van Buchem (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Finite element-based investigation and explainable machine learning prediction of moment resistance of steel flush end-plate connections - Md. Ibrahim Kholil; Muhammad Harunur Rashid; Aziz Ahmed; Md. Waliul Islam (Next Research, 2026)

Microbial diversity enhancement in a bio-electro-fenton system driven by sediment microbial fuel cells for photocatalytic PAHs degradation in antibiotics applicate soil-water systems - Muhammad Usman; Zenhua Zhao; Muhammad Adnan; Muhammad Ibrahim; Olive Mekontchou Yemele; Ghulam Abbas Ashraf; Mukhtorjon Karimov; Alisher Abduvokhidov; Naoufel Ben Hamadi (Journal of Environmental Chemical Engineering, 2026)

Influence of tea-derived polyphenols architecture on the structural, functional and allergenicity properties of β-lactoglobulin: A comparison of non-covalent and covalent interactions - Zhi-Wei Liu; Jia-Wei Zou; Xiu-Bin Liu; Waqar Ahmed; Rana Muhammad Aadil; Marwa Ezz El-Din Ibrahim; Jun-Hu Cheng; Xie-Ling He; Hou-Gang Zhou; Hong-Ying Guo (Food Research International, 2026)

Optimization of ohmic-assisted thermochemical pretreatment of empty fruit bunch for enhanced hydrogen production and fermentation kinetics - Izzah Farhana Ab Aziz; Hasfalina Che Man; Muhammad Hazwan Hamzah; Rozita Omar; Nur Syakina Jamali; Ibrahim B. Dalha (Biomass and Bioenergy, 2026)

Development and Characterization of Exosomes Mediated Transdermal Gel for Enhanced Delivery of Hydroxyurea - Wajeeha Khalid; Rabia Gul; Muhammad Sarfraz; Hamid Bashir; Nadeem Ahmad; Nayab Tahir; Aneela Javed; Muhammad Asad; Ahsan Ibrahim; Aamra Imtiaz; Imran Nazir; Muhammad Imran Amirzada (Journal of Pharmaceutical Innovation, 2026)

Predation, prey preference and switching behaviour of the soil predatory mite Blattisocius mali (Mesostigmata: Blattisociidae) on immature stages of Drosophila hydei - Muhammad Arslan Ibrahim; Katarzyna Michalska; Marcin Studnicki (Experimental and Applied Acarology, 2026)
Blattisocius mali is a soil predatory mite known to disperse phoretically on adult drosophilid fruit flies and feed ectoparasitically on them during transport. Despite this association, its behavioural and trophic interactions with immature drosophilid stages remain poorly understood. This study analysed B. mali ’s ability to prey on Drosophila hydei immature stages and examined the effects of prior rearing diet on predation, prey preference, and switching. Two types of predatory mite were compared: (1) fly-reared (FR) and (2) mite-reared (MR), raised on fruit flies or acarid mites, respectively. Predator females successfully attacked all developmental stages, except pupae, during 24 h of exposure in our assay. In non-choice tests, mean predation rates were highest on first-instar (L1), followed by eggs, second-instar (L2), and third-instar larvae (L3). FR predators, as compared to MR predators, showed the highest predation rates on all prey stages except L3. Feeding on fly eggs, B. mali exhibited significantly higher fecundity, laying nearly twice as many eggs compared to when they were fed on L1. Their oviposition declined markedly on L2 and L3. In two-choice and three-choice assays, B. mali showed a clear preference for eggs over larval instars in both predator types. FR predators preferred L1 over L2, while, conversely, MR predators preferred L2. Furthermore, B. mali females displayed different behaviour depending on the proportion of fly eggs and/or larvae available, including no switching, switching, or counter-switching. These findings improve understanding of trophic interactions between mesostigmatic mites and drosophilid flies and highlight the role of dietary experience in shaping predator foraging behaviour.

Assessment of the impact of treated wastewater discharge on the water quality of drainage systems in Egypt’s eastern Nile delta - M. M. Ibrahim; Aiman El Saadi; E. Sh. Muhammad; Abeer Samy (Euro-Mediterranean Journal for Environmental Integration, 2026)

Microplastics in Urban Wastewater: A Vector for Chemical and Biological Pollutants with Emerging Health Risks - Mamoona Sadia; Abid Mahmood; Muhammad Ibrahim; Bilal Aslam (Environmental Research, 2026)

Genetic variation of grey pomfret Pampus cinereus along the Bangladesh and Malaysia coastlines with phylogeography in the Indo-West Pacific based on mitochondrial COI and Cyt β - M.M. Mahbub Alam; Md. Moshiur Rahman; Jayed Mahbub Aomio; Nur Asma Ariffin; Mohammad Asmat-Ullah; Shamima Nasren; Sarker Mohammed Ibrahim Khalil; Md. Abdullah-Al Mamun; Muhammad Anamul Kabir; Ahasan Habib (Ecological Genetics and Genomics, 2026)

Impact of Land Use Change on Water Quality: Toward Sustainable Ecosystem Management in the Nenggiri River Basin - Ismafatin Nabilah Ismail; Mohd Khairul Amri Kamarudin; Mohamad Hafis Amat Simin; Asmawi Ibrahim; Wan Nor Azilawanie Tun Ismail; Ahmad Shakir Mohd Saudi; Mohd Ekhwan Toriman; Sunardi Sunardi; Firdaus Muhammad-Sukki (Water, Air, & Soil Pollution, 2026)

Multiscale spatiotemporal analysis and predictability of long-term meteorological drought in the Kaduna river basin (1901–2024) - Muhammad Lawal Abubakar; Saadatu Umaru Baba; Sidikatu Aliyu; Habiba Ibrahim Mohammed; Hindatu Abdulkadir; Muhammad Sambo Ahmed; Madinatu Ahmad; Auwal F. Abdussalam (Theoretical and Applied Climatology, 2026)

Risk of gastrointestinal bleeding with gabapentin versus duloxetine in older adults with neuropathic pain: a target trial emulation cohort study - Nirav Agrawal; Akshay Sharma; Aditya Chandrashekar; Muhammad Ali Ibrahim Kazi; Mitchell Karpman; Sanmeet Singh; Nargiz Muganlinskaya (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Corrigendum to “Exploring the impact of seasonal variation on the toxicological profile of Σ2PFAS in surface water bacterioplankton communities” [J Hazard Mater 500 (2025) 140464]. - Yiping Li; Muhammad Ibrahim; Cheng Yue; Yaning Wang; Pan Hongzhe; Abdulhakim Wagini Hassan; Yan Chunmin (Journal of Hazardous Materials, 2026)

Heterogeneous catalysts' physicochemical influences on CO2 desorption for amine absorbents regeneration - Abdulrahim Ibrahim; Muhammad Imran–Shaukat; Bin Liu; Min Xiao; Hongxia Gao; Zhiwu Liang; Paitoon Tontiwachwuthikul; Teerawat Sema (Journal of Environmental Chemical Engineering, 2026)

Advancing heat pump dryers for agricultural products processing: A critical review of drying chambers and systems - Muhammad Aqil Afham Rahmat; Ubaidah Syafiq; Muhammad Hazwan Hamzah; Nazmi Mat Nawi; Hasila Jarimi; Adnan Ibrahim (International Journal of Refrigeration, 2026)

Digital twin-centered food safety management systems: A review of IoT, AI, and blockchain integration for bacterial pathogen control - Balarabe B. Ismail; Abdulrazaq Hassan Abba; Abdulrashid Ibrahim Sanka; Aliyu Idris Muhammad; Wenjun Wang; Donghong Liu (Food Research International, 2026)

MOF-based composite catalysts for CO2 reduction: Recent advances and perspectives - Asad Ur Rehman; Syed Shoaib Ahmad Shah; Sami Ullah; Arooj Fatima; Ibrahim A. Shaaban; Muhammad Sufyan Javed; Awais Ahmad; Muhammad Altaf Nazir (Environmental Research, 2026)

Boiling for micro(nano)plastic mitigation in drinking water: Chemical interactions, potential risks, and research gaps - Abdul Qadeer; Xiang Tu; Muhammad Anis; EH. Ibrahim; Zeeshan Ajmal; Kun Wang; Xia Jiang; Weng Shuhang (Chemical Engineering Journal, 2026)

Early winter precipitation variability over Pakistan and associated ENSO teleconnections - Romesa Najeeb; Irfan Ur Rashid; Rehan Ahmed; Muhammad Adnan Abid; Elham Ghasemifar; Ibrahim Alsafari (Theoretical and Applied Climatology, 2026)

Spatiotemporal Assessment of Agricultural Drought in Semiarid Northern Nigeria Using MODIS Data and Explainable Random Forest (2000–2025) - Muhammad Lawal Abubakar; Asmau M. Ahmed; Sidikatu Aliyu; Saadatu Umaru Baba; Muhammad Sambo Ahmed; Khalid Ibrahim Richifa (Pure and Applied Geophysics, 2026)

Potential Application of Tamarind Seed Extract as Coagulant Aid in Alum-Based Removal of Polyamide Microplastics - Muhammad Adli Hanif; Naimah Ibrahim; Man Yung Ho; Masitah Hasan; Farrah Aini Dahalan; Nabilah Aminah Lutpi; Norzila Othman; Mohamed Hasnain Isa (International Journal of Environmental Research, 2026)

Immunoinformatics-driven multi-epitope vaccine design as a promising strategy against multidrug-resistant pathogens: a comprehensive review - Rameen Nasir; Muhammad Mutayyab Javaid; Raheen Rahman; Rimsha Abbasi; Muneeb Khalid; Muhammad Arslan; Muhammad Amjad Sajjad; Ahsan Ibrahim (Folia Microbiologica, 2026)

Biological and synthetic biology strategies for polystyrene degradation: mechanisms, microbial advances, and circular economy perspectives - Mehar Nazir; Asma Rehman; Ahmad H. Ibrahim; Sawsan S. Al-Rawi; Manahil Akmal; Ghazala Iram; Faiza Manzoor; Sadia Aziz; Muhammad Shehroz Zafar; Muhammad Adnan Iqbal (Biodegradation, 2026)

Parental Iron Deficiency Programs Oxidative Stress and Epigenetic Demethylase Dysregulation (TET and KDM2) in Drosophila melanogaster Offspring - Farida Bashar; Kasimu Ghandi Ibrahim; Abdullahi Yahaya Abbas; Muhammad Bashir Bello; Mustapha Umar Imam; Aliu Abdulhameed Zubair (Biological Trace Element Research, 2026)

Microalgae-based bioplastics from wastewater: a bibliometric, technological, and sustainability review - Koko Iwan Agus Kurniawan; Muhammad Naufal Rauf Ibrahim; Laila Dina Amalia Purba; Aisyah Hanifah; Budi Mandra Harahap; Mikihide Demura; Ryozo Noguchi (Environmental Science and Pollution Research, 2026)

Development of dry and oil-based formulations of Metarhizium anisopliae using carrier materials for effective control of red flour beetle, Tribolium castaneum (Coleoptera: Tenebrionidae) - Nahdia Perveen; Abu Bakar Muhammad Raza; Muhammad Arshad; Panagiotis Eliopoulos; Samah F. Ibrahim; Mustafa Shukry; Samy Sayed; Hanan M. A. Hamada (BioControl, 2026)

Exploiting the biocontrol potential of Chaetomium globosum against Fusarium solani root rot in wheat: climate-responsive phytohormonal regulation, genetic diversity, and sustainable management - Marwa S. Fouad; Khaled M. A. Ramadan; Hisham A. Mohamed; Mohamed Abou-Zeid; Shafik D. Ibrahim; Muhammad Munir; Eslam S. A. Bendary; Mohamed M. Aboul Fotouh; Sallah A. Al Hashedi; Adil AlShoaibi; Zafar Iqbal; Ahmed M. Ismail; et al. (European Journal of Plant Pathology, 2026)

Eco-friendly tick control using Pakistani bee propolis: Behavioral and acaricidal effects against Rhipicephalus microplus and Hyalomma marginatum - Shahid Nazeer; Shahid Ullah Khan; Shamsheer Khan; Malik Muhammad Sohail Elahi; Syed Ishtiaq Anjum; Khalil ur Rehman; Ruoa Saleh Almahallawi; Amal Abdullah Aboras; Nada Ibrahim Alribdi; Umber Zaman (Veterinary Parasitology, 2026)

Unveiling genetic diversity in Egyptian Arabian horses (Equus caballus) through cytogenetic and ISSR marker analysis - Muhammad A. Ibrahim; Magda M. Noshy; Hanan R.H. Mohamed; Mona E.H. Abd El-Gawad (Research in Veterinary Science, 2026)

Provenance, tectonic settings, depositional conditions, and diagenetic features of the late Cretaceous (Coniacian–Santonian) Fika Shale, Upper Benue Trough, Northeastern Nigeria: Implications for hydrocarbon potential - Abdulwahab Bello; Musa B. Usman; Shehu Mukkafa; Ibrahim A. Kwami; Usman Abubakar; Abduljamiu O. Amao; Anas M. Salisu; Khalid Al-Ramadan; Muhammad A. Ismail; Abubakar S. Maigari; Ahmed I. Haruna; Bandar D. Al-Otaibi; et al. (Journal of African Earth Sciences, 2026)

Bismuth nanostructures: catalytic pathways to sustainable technologies - Muhammad Khan; Mohamed Hassan Eisa; Xiaohui Sun; Muffarih Shah; Suleiman M. Suleiman; Abdul Hameed; Ilyas Khan; Xiangsheng Chen; Nasir A. Ibrahim; Ashraf A. Qurtam; Zainuriah Hassan; Katabathini Narasimharao; et al. (Fuel, 2026)

Botulinum toxin from foodborne hazard to aesthetic and biomedical tool: mechanisms, applications, detection strategies, and future perspectives - Muhammad Adnan; Muhammad Waqar; Rais Ahmed; Haroon Afzal; Muhammad Abdullah Mueen; Urooj Qayyum; Farhang Hameed Awlqadr; Muhammad Talha Yaqoob; Sabrin R. M. Ibrahim; Gamal A. Mohamed; Iqra Rafiq; Hagar M. Mohamed (Archives of Microbiology, 2026)

A new ecological index for assessing benthic invertebrate assemblages in tropical coral reef ecosystems - Hadiyanto Hadiyanto; Indra Bayu Vimono; Hendrik Alexander William Cappenberg; Ludi Parwadani Aji; Teddy Triandiza; Ana Setyastuti; Ismiliana Wirawati; Ernawati Widyastuti; Rianta Pratiwi; Putri Saphira Ibrahim; Tyani Fitrian; Allsay Kitsash Addifisyukha Cintra; et al. (Aquatic Sciences, 2026)

Correction: Molecular characterization and green synthesis of iron oxide nanoparticles from Ureibacillus chungkukjangi for methylene blue degradation - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Shumaila Ibrahim; Maida Salah Ud Din; Maryam M. Alomran; Ashwag Shami; Fakhria A. Al-Joufi; Ahmad A. Alghamdi; Abdullah A. Alqasem; Ahmed M. Basri; Majid Alhomrani (Antonie van Leeuwenhoek, 2026)

Corrigendum to “A Source-Environment-Response (SER) approach for solving Spatio-temporal radon transport in different media” [J. Atmos. Sol. Terr. Phys.- 282, May (2026), 106796] - Ahmad Muhammad; Ibrahim Yahaya Muhammad; Ahmed H. Ali; Muhammad Abubakar Isah; Salim Jibrin Danbatta; Ahmed Sait Alali (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Thermal analysis of nonsymmetric stress tensor on a partially ionized viscoelastic non-Newtonian fluid flow with convective boundary conditions (A numerical study) - Muhammad Naveed Khan; Aamir Abbas Khan; Haifaa F. Alrihieli; Walid Abdelfattah; Ibrahim E. Elseesy (Dynamics of Atmospheres and Oceans, 2026)

Preparation, characterization and flocculation performance of fungi-nanoparticle conjugates for efficient harvest of Chlorella vulgaris - Muhammad Hizbullahi Usman; Abdulrahman Sahabi; Muhammad Bello; Aliyu Ibrahim Dabai (Bioresource Technology Reports, 2026)

Deciphering organ-specific chemistry and bioactivities of Plumeria rubra L. via integrated metabolomics, biological evaluation, and molecular docking studies - Rana M. Ibrahim; Shymaa I.A. Abdel-dayem; Florbela Pereira; Fatema R. Saber; Łukasz Kulinowski; Benita Hryć; Gokhan Zengin; Muhammad A. Alsherbiny; Krystyna Skalicka-Woźniak (Biocatalysis and Agricultural Biotechnology, 2026)

Safety and tolerability of the ACE-inhibitor lisinopril among Nigerian adults with HIV: preliminary pilot data from a randomized clinical trial - Faisal S. Dankishiya; Hamza Muhammad; Usman J. Wudil; Baba M. Musa; Liping Du; Ibrahim A. Adam; Aima A. Ahonkhai; Anna M. Burgner; Aishatu M. Nalado; Mahmoud U. Sani; Aliyu Abdu; Bryan E. Shepherd; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

“Ondansetron augmentation for obsessive–compulsive disorder: A systematic review and meta-analysis of randomized placebo-controlled trials” - Anas Mohammad; Mohammad Ibrahim; Aneeq Mahmood Khan; Usama Pervaiz; Sarah Aijaz; Muhammad Hassnain Nasrullah; Hammad Jamil (European Journal of Clinical Pharmacology, 2026)

Boosting Sustainability: Integrating Green Practices With the Circular Economy - Abdul Rehman; Muhammad Ibrahim Shahid; Sajjad Ahmad Baig; Fariha Fatima (Circular Economy and Sustainability, 2026)

Comprehensive in-vitro study of anticholinesterase, anti-inflammatory, and antidiabetic properties of congress grass (Parthenium hysterophorus) methanolic extract - Abdur Rauf; Muhammad Ibrahim; Yahya S. Al-Awthan; Omar S. Bahattab; Hassan A. Hemeg; Anees Ahmed Khalil; Ahood Khalid; Samiah Shahid; Hina Gull; Muhammad Saeed Jan; Dorota Formanowicz; Marcello Iriti (Plant Biosystems, 2026)

Integrated modelling application for assessing impacts of climate and land use change on water balance in Hadejia river basin Northwestern Nigeria - Da’u Abba Umar; Mohammad Firuz Ramli; Amir Kamal Hamidon; Ruhil Amal Adnan; Shaharin Ibrahim; Muhammad Amar bin Zaudi; AbdulJalal AbdulSalam (Arabian Journal of Geosciences, 2026)

Slow-Release DAP Fertilizer Coated with Bacillus velezensis FB2 and Polyvinyl Alcohol for Sustainable Maize Production - Zumrah Rehman; Muhammad Bilal Khan Niazi; Zaib Jahan; Ghulam Abbas Shah; Hazrat Ali; Zia Ur Rahman Farooqi; Waqas Mohy-Ud-Din; Qasim Ali; Gamal Awad El-Shaboury; Haitham Ibrahim El-Mekkawy (Journal of Soil Science and Plant Nutrition, 2026)

Remote-sensing technologies for air pollution monitoring in the USA: a comprehensive review - Santosh Sapkota; Gamal El Afandi; Chastity Bradford; Muhammad Irfan; Salem Ibrahim; Amira Moustafa; Reda Algendy (Environmental Monitoring and Assessment, 2026)

Air pollution-related health impacts from domestic waste burning and associated interventions: the merits of a traditional versus machine learning scoping review methodology - Thandi Kapwata; Candice Webster; Wen Guan Gavin Chen; Muhammad Ibrahim Suder; Devon Jarvis; Alex Vogt; Nomfundo Mahlangeni; Tracey Laban; Natasha Naidoo; Pierpaolo Mudu; Kerolyn Shairsingh; Caradee Y. Wright (Environmental Monitoring and Assessment, 2026)
Regularly updating repositories of air pollution impacts on health is essential for evidence-based policies, interventions, and progress monitoring. However, this is often time-consuming and labour-intensive. Automation can ensure up-to-date evidence; reduce retrieval, screening time, and costs; and make information accessible to non-academic stakeholders. This study investigated whether a machine learning approach can perform any stages of a traditional scoping review on the health impacts, policies, and interventions related to air pollution due to domestic waste burning. A traditional approach was conducted in parallel with machine learning methods enabling a comparison of the efficiency and quality of the partially automated approach against the manual review. Findings from the two approaches were compared and the final set of included articles were considered for (1) reported impacts of waste burning on health outcomes and (2) recommendations on solutions and interventions to prevent/reduce adverse effects on health from waste burning. We found a range of health impacts associated with waste burning, including low birth weight, hypertensive disorders of pregnancy, adverse respiratory outcomes like asthma and wheeze, cancer risk, and mortality. Few studies proposed solutions or evaluated the effectiveness of interventions. The ML approach showed a tendency towards false positives, which are preferable to false negatives (where relevant papers were excluded). Results showed that the model can conduct initial searches and decisions for the review. However, the articles included in the model should be screened manually for final acceptance. Therefore, we propose a hybrid approach be used until the automated model can be further refined.

UAV-based crop reconstruction and trait estimation using RGB imagery without external geospatial infrastructure - Muhammad Hussain Habib Chaudhry; Muhammad Ibrahim Rana; Hassan Jaleel (Computers and Electronics in Agriculture, 2026)

Structural equation modelling for sustainable land management: Assessing ridge-furrow rainwater harvesting and chopped straw effects on soil moisture dynamics and sainfoin yield in semi-arid slopes - Ibrahim Awuku; Abdul Qadeer; Xiaole Zhao; Rizwan Azim; Qi Wang; Wen Ma; Fujia Li; Muhammad Ishfaq; Xuchun Li; Bing Liu (Computers and Electronics in Agriculture, 2026)

Corrigendum to “Predicting blue carbon sequestration in Sundarban coastal mangroves: A spatially explicit approach with INVEST and machine learning to advance climate resilience and UN SDG-aligned nature-based climate solutions” [Mar. Pollut. Bull. 226 (2026) 119387] - Ismail Mondal; SK Ariful Hossain; Muhammad Tauhidur Rahman; Wafeek Mohamed Ibrahim; Mukhiddin Juliev (Marine Pollution Bulletin, 2026)

Predicting blue carbon sequestration in Sundarban coastal mangroves: A spatially explicit approach with INVEST and machine learning to advance climate resilience and UN SDG-aligned nature-based climate solutions - Ismail Mondal; SK Ariful Hossain; Muhammad Tauhidur Rahman; Wafeek Mohamed Ibrahim; Mukhiddin Juliev (Marine Pollution Bulletin, 2026)

Genetic basis of breed variation: Genome wide selection signature of neighboring sheep breeds - Muhammad Ibrahim; Muhammad Yaqoob; Mehmood Alam Khan; Irfan Ullah Wazir; Meshari Mohsen Alwazae; Sohail Ahmad (Small Ruminant Research, 2026)

SARS-CoV-2 antibody responses during the omicron wave in kano, nigeria: Implications for strengthening future vaccine strategies - Bilkisu Ahmed; Jamilu Abubakar Bala; Taysir Ramadan Hafiz; Isah Abubakar Aliyu; Abdulhadi Sale Kumurya; Ibrahim Muhammad Badamasi; Hayatu Saidu; Muhammad Adamu Abbas; Auwal Idris Kabuga; Alhassan Sharif Abdullahi; Bashiru Garba; Al-Mukhtar Yahuza Adamu; et al. (Next Research, 2026)

The binding effect of biochar with polycyclic aromatic hydrocarbons and their derivatives: Role in carbon sequestration and pollutant removal efficiency - Muhammad Fawad; Lingyu Zhang; Abdelrahman Ibrahim; Xinyi Xu; Tong Wu; Miao Han; Vishnu D. Rajput; Chao Qin; Wanting Ling (Journal of Environmental Management, 2026)

A Source-Environment-Response (SER) approach for solving Spatio-Temporal Radon Transport in Different Media - Ahmad Muhammad; Ibrahim Yahaya Muhammad; Ahmet H. Ali; Muhammad Abubakar Isah; Salim Jibrin Danbatta; Ahmet Ali Sait (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Machine learning and design of experiment for enhanced biomass using N2 and CO2-enriched biochar at different pyrolysis temperatures - Muhammad Aasim; Ebubekir Siddik Aydin; Ibrahim Korkut; Başak Temur Ergan; Ahmet Say; Salma Naimatullah Soomro; Sabeen Rehman Soomro; Seyid Amjad Ali; Sezai Ercişli; Ramazan Katırcı (Biomass and Bioenergy, 2026)

Synergistic Degradation and Cytotoxicity Mitigation of Meloxicam Using UV/Perovskite/H₂O₂ and Gamma/H₂O₂: A Comparative Study - Muhammad Asad Khan; Mohamed A. Habib; Muhammad Imran Kanjal; Majid Muneer; Muhammad Asghar Jamal; Tanveer Hussain Bokhari; Usman Irshad; Ahmed B. M. Ibrahim (Water, Air, & Soil Pollution, 2026)

The biological synthesis of iron oxide nanomaterials and their possible physiological and biochemical toxicities in Cyprinus carpio - Nadia Bibi; Nishita Narwal; Muhammad Anees; Huma Ayub; Mian Adnan Kakakhel; Tawaf Ali Shah; Ashraf Khalifa; Imran Ibrahim Shaikh (Ecotoxicology, 2026)

Unraveling survival disparities in primary central nervous system (CNS) lymphoma: an analysis of race, socioeconomic factors, and treatment outcomes using the surveillance, epidemiology, and end results program (2000–2021) - Shahzaib Maqbool; Mohammad Ebad Ur Rehman; Ramesha Tahir; Hafsa Arshad Azam Raja; Mouzma Ali; Muhammad Ibrahim; Jacob Guerrero; Abdur Rehman; Imran Khan; Abat Khan; Jose D. Sandoval-Sus (Cancer Causes & Control, 2026)

Data-driven explainable artificial intelligence models for predicting CO2 uptake in metal–organic frameworks - Mohd Azfar Shaida; Laiba Saleem; Syed Ali Waqas Ahmad; Saad Shamim Ansari; Syed Muhammad Ibrahim (Environmental Science and Pollution Research, 2026)

A review of floating renewable energy technologies for sustainable development - Mir Murtaza Zangejo; Muhammad Ismail Jamali; Mohsin Ali Koondhar; Abdul Sattar Saand; Ibrahim Mahariq; Ezzeddine Touti (Ocean Engineering, 2026)

Advances in membrane bioreactor and IFAS-MBR systems for treatment of wastewater containing pharmaceuticals - Ratri Rachmawati; Ibrahim Maina Idriss; Zubair Hashmi; Nova Kurnia; Indah Prihatiningtyas; Asim Laeeq Khan; Muhammad Roil Bilad (Journal of Environmental Chemical Engineering, 2026)

Fermentation optimization improves antifungal metabolite production of Letendraea sp. SX 36 against Colletotrichum nymphaeae - Xiaoxu Sun; Muhammad Ibrahim; Xiaomei Wang (Fungal Biology, 2026)

Mxene-chitosan composites in wastewater treatment: From adsorption and separation to catalytic remediation - Muhammad Khan; Mohamed Hassan Eisa; Abdul Hameed; Xiaohui Sun; Suleiman M. Suleiman; Muffarih Shah; Noor Majeed; Xiangsheng Chen; Nasir A. Ibrahim; Ashraf A. Qurtam; Katabathini Narasimharao; Zainuriah Hassan (Carbohydrate Polymers, 2026)

Facile and Low Cost Synthesis of NiFe-LDH/ZnO Composites for Efficient Photodegradation of MB in Aqueous Solution Under the Illumination of Natural Sunlight - Ramsha Saleem; Humera Shaikh; Muhammad Saajan Barhaam; Qurban Ali Shah; Baradi Waryani; Mazhar Ali Abbasi; Imran Ali Halepoto; Nek Muhammad Shaikh; Muhammad Ali Bhatti; Rafat M. Ibrahim; Elmuez Dawi; Aneela Tahira; et al. (Water, Air, & Soil Pollution, 2026)

Impact of heat stress on outdoor labor productivity in peninsular malaysia: a spatio-temporal assessment - Najeebullah Khan; Rajab Houmsi; Muhammad Shazril I. Ibrahim; Shamsuddin Shahid (Natural Hazards, 2026)

Hydro-geochemistry and simulation for the sub subsurface environment of groundwater of Shahdara, Pakistan - Muhammad Irfan Jalees; Iqra Younis; Ahmad Ibrahim; Madeeha Batool; Imran Kalim (Modeling Earth Systems and Environment, 2026)

Impact of genetic composition on cows’ metabolic and fertility responses to thermal stress - Ihsan Ullah; Muhammad Subhan Qureshi; Raed M. Al-Atiyat; Shah Murad Khan; Ihtesham Ul Haq; Shabana Naz; Rifat Ullah Khan; Babar Maqbool; Marco Ragni; Ibrahim A. Alhidary (International Journal of Biometeorology, 2026)

Involvement of the PD-1 pathway in the modulation of immune responses during allergic diseases - Asma’a Hassan Mohamed; Rithab Ibrahim Al-Samawi; Mohammad Chand Jamali; Sana Abdul-Jabbar Ali; Ayyub Ali Patel; Alam Eldin Musa Mustafa; Abdulrahman Samir Khairallah; Nasrin Mansuri; Ashit Kumar Dutta; Muhammad Zulfiqah Sadikan; Zaid H. Mahmoud (Inflammation Research, 2026)

Harnessing novel biosynthesized ZrO₂ biochar nanocomposites for reactive orange 16 dye adsorption: kinetic modeling and cytotoxicity insights - Mubashara Fayyaz; Mohamed A. Habib; Syed Kashif Ali; Saif Ullah; Muhammad Imran Kanjal; Tahreem Saleem; Rana Muhammad Zulqarnain; Ahmed B. M. Ibrahim (Biodegradation, 2026)

Silver nanoparticles in water disinfection: a comprehensive overview on their mechanisms, benefits, and limitations - Muhammad Shehroz Zafar; Sana Ejaz; Farhan Ahmad; Ahmad H. Ibrahim; Sawsan S. Al-Rawi; Faiza Manzoor; Sadia Aziz; Saima Iqbal; Muhammad Adnan Iqbal (Archives of Microbiology, 2026)

Structural equation modeling revealed optimized ridge-furrow configuration integrated with straw-soil crust enhancing carbon sequestration and sainfoin yield in semiarid agroecosystems - Abdul Qadeer; Qi Wang; Rizwan Azim; Xiaole Zhao; Wen Ma; Ibrahim Awuku; Fujia Li; Qinglin Liu; Yanping Liu; Bing Liu; Xuchun Li; Muhammad Sanaullah; et al. (Computers and Electronics in Agriculture, 2026)

Synergistic effects of multi-frequency ultrasonication on starch-gum interactions for sialorrhea management: Implications for structural, functional, digestibility properties, and molecular docking studies - Muhammad Awais; Wenjiang Dong; Baoguo Xu; Qiufang Liang; Lin Xiangyu; Yufan Sun; Mingming Zhong; Mohamed Ibrahim Younis; Husnain Raza; Ekram Abd El-Salam; Xiaofeng Ren (Food Hydrocolloids, 2026)

Investigation of heat and mass transfer in an electromagnetically driven ionized tri-hybrid nanofluids flow over a convectively heated cylinder - Muhammad Naveed Khan; Shafiq Ahmad; Aamir Abbas Khan; Mounirah Areshi; Ibrahim E. Elseesy (Dynamics of Atmospheres and Oceans, 2026)

Nonlinear analysis of thermo-magneto slip flow of Jeffery fluid in a wavy curved channel - Maham Mujahid; Mounirah Areshi; Zaheer Abbas; Muhammad Yousuf Rafiq; Ibrahim E. Elseesy (Dynamics of Atmospheres and Oceans, 2026)

A Comprehensive Study on Radiation-Assisted Detoxification of Hazardous Industrial Effluents: A Statistical Approach - Saif Ullah; Mohamed A. Habib; Majid Muneer; Muhammad Imran Kanjal; Gulraiz Ahmad; Ahmed B. M. Ibrahim; Rana Muhammad Zulqarnain; Lotfi Mouni (Water, Air, & Soil Pollution, 2026)

Improving growth traits in rabbits: a comparative study of Gabali, New Zealand White, and their hybrids using 18S rDNA sequencing - Hairul Islam Mohamed Ibrahim; Abdullah Sheikh; Roshmon Thomas Mathew; Muhammad Munir; Gamal Bekhet; El-Sayed Hemdan Eissa; Sameh A. Abdelnour; Mohamed D. Mahran (Tropical Animal Health and Production, 2026)

Isolation and molecular characterization of plant growth-promoting rhizobacteria for biocontrol of Fusarium head blight in wheat - Syed Jehangir Shah; Somaira Bibi; Safira Attacha; Syed Tanveer Shah; Noreen Asim; Waqas Ahmad; Muhammad Sayyar Khan; Ishrat Naz; Muhammad Ibrahim; Aftab Jamal (Cereal Research Communications, 2026)

Correction: Hormetic Priming of Sorghum Water Extract Imparts Drought Tolerance and Mediated Antioxidative Defense in Wheat - Muhammad Usman Ibrahim; Abdul Khaliq; Basmah M. Alharbi; Shehnaz kousar; Hayam A. Alwabsi; A. Altalhi; Abdulrahman Saad Aldawood; Khawaja Ghulam Rasool (Agricultural Research, 2026)

Hormetic Priming of Sorghum Water Extract Imparts Drought Tolerance and Mediated Antioxidative Defense in Wheat - Muhammad Usman Ibrahim; Abdul Khaliq; Basmah M. Alharbi; Shehnaz kousar; Hayam A. Alwabsi; A. Altalhi; Abdulrahman Saad Aldawood; Khawaja Ghulam Rasool (Agricultural Research, 2026)

Health risk assessment of radon exposure through drinking water in Iluagba, Kogi State, Nigeria - Ibrahim Ayodeji Bello; Abdullahi Muhammad Vatsa; Hameed Adavize Momoh; Taiwo Abadunmi; A. A. Bello (Isotopes in Environmental and Health Studies, 2026)

Hydrogen production from hydrogen sulfide via a uniquely designed electrolysis process: experimental investigation - Muhammad Ishaq; Ibrahim Dincer (Fuel, 2026)

MOF/Graphene interfaces in catalytic water splitting: Recent breakthroughs and future outlook - Asad Ur Rehman; Muhammad Asghar; Abdul Rauf; Tayyaba Najam; Ibrahim A. Shaaban; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Fuel, 2026)

Solar-Driven Photocatalytic Degradation of Organic Pollutants by I-MnO₂/PTh Nanocomposite: Mechanisms, Kinetics, and Implications for Advanced Environmental Remediation - Muhammad Nayab; Ahmad Farhan; Muhammad Zahid; Zulfiqar Ahmad Rehan; Asim Jilani; Rafa Almeer; Hussameldin Ibrahim; Nabil Al-Zaqri (International Journal of Environmental Research, 2026)

Drimiopsis maculata methanol extract attenuates inflammation in experimental rat model of polyarthritis: a biochemical and molecular insight - Malik Saadullah; Farwa Tahir; Maryam Farrukh; Samina Afzal; Rabia Munir; Usman Ashraf; Uzma Saleem; Muhammad Ajmal Shah; Ibrahim Aljaezi; Ana Sanchez Silva; Norah K. Algarzae; Musaad Bedah Alsahly (Inflammopharmacology, 2026)

Towards harmonized soil intelligence: insights from a multi-country survey of mediterranean soil information systems - Jawad T. Al-Bakri; Mais Atiyat; Muhammad Rasool Al-Kilani; Areej Al-Khreisat; Ibrahim Farhan; Claudio Zucca (Euro-Mediterranean Journal for Environmental Integration, 2026)

Harnessing Paramecium primaurelia for polyhydroxyalkanoate production: optimization of carbon sources for sustainable bioplastic synthesis - Ayesha Arshad; Itrat Zahra; Awais Ibrahim; Usama Shabbir; Shahid Nawaz; Ayesha Liaqat; Roohi Ijaz; Tuba Arooj; Sammi Rasheed; Ayesha Ghauri; Bushra Muneer; Amor Hedfi; et al. (Biologia, 2026)

Beyond limitations: Integrating advanced analytical techniques for a new era of soil organic matter characterization - Adnan MUSTAFA; Qudsia SAEED; Lasisi H. TOBILOBA; Yakov KUZYAKOV; Muhammad NAVEED; Mohammad T.K. NEZHAD; Muhammed M. IBRAHIM; Jan FROUZ; Martin BRTNICKY; Jiri KUCERIK; Xiankai LU (Pedosphere, 2026)

C-Phycocyanin-mediated photoactivation versus Er: YAG laser irradiation for ceramic bracket surface conditioning: Influence on bonding efficacy of sepiolite nanoparticle-modified adhesive - Salem Almoammar; Muhammad Abdullah Kamran; Abdulrahman Alshehri; Wael Awadh; Amyrah Musafir Alshehrany; Ibrahim Alshahrani (Journal of Photochemistry and Photobiology B: Biology, 2026)

Exploring microbiological transformation of glutamate to γ-aminobutyric acid unleashed by a potential Lactobacillus spp. isolated from commercial cheese samples - Sikander Ali; Taha Shafi; Iram Liaqat; Muhammad Usman Ahmad; Ifrah Shabbir; Tariq Aziz; Maha Alharbi; Ashwag Shami; Fahad Al-Asmari; Ibrahim Faisal Halawani; Abdullah A. Alqasem; Reham M. Mashat; et al. (International Dairy Journal, 2026)

Dual photo/electrocatalytic CO2 reduction by porphyrin based metal organic framework under visible light and electrochemical bias - Mamuna Aslam; Uzma Saleem; Ibrahim A. Shaaban; Tahani Rahil Aldhafeeri; Ataf Ali Altaf; Muzammil Iqbal; Muhammad Tariq; Mohammed A. Assiri; Shahid Hussain; Hafiz Muhammad Asif (Fuel, 2026)

Comparison of various heat stress indices for spatial representation of human thermal discomfort events in Nigeria - Mohammed Abdu Nasara; Ibrahim Mohammed Lawal; Najeebullah Khan; Amyrhul Abu Bakar; Ahmed Hussaini Jagaba; Labib Sharrar; Mohd Khairul Idlan Muhammad; Shamsuddin Shahid (Theoretical and Applied Climatology, 2026)
Nigeria is experiencing rising temperatures, frequent heat extremes, and increasing exposure to thermal stress. This study is the first to offer a comprehensive, long-term (1950–2023), and spatially comparative analysis of heat stress in Nigeria using four globally recognized thermal indices, Humidex (HD), Normal Effective Temperature (NET), Wet Bulb Globe Temperature (WBGTs), and Universal Thermal Climate Index (UTCI), enabling a more nuanced understanding of regional and index-specific sensitivities to heat extremes across diverse climatic zones. Heatwave events were analyzed based on durations (1-day, 3-day, and 5-day) and periods (daytime, nighttime, and 24-hour mean) for four stress categories: moderate, strong, severe, and extreme. Findings reveal significant variations in heat stress frequency across indices, regions, and event durations. NET consistently recorded the highest number of heat stress events, particularly in northern and highland areas, highlighting its sensitivity to topographical influences. For 1-day nighttime events, NET identified up to 40 strong occurrences in southern Nigeria, while WBGTs recorded over 25 moderate cases in both regions. In consecutive 3-day events, NET reported up to 20 severe cases in northern and southern Nigeria, while WBGTs captured up to 16 extreme daytime events. For prolonged 5-day heatwaves, NET and WBGTs detected up to 12 extreme events, underscoring their responsiveness to extended heat exposure. Conversely, UTCI remained the most conservative for all durations, reflecting its strict physiological threshold. Regional analysis confirms that northern Nigeria experiences a higher frequency of severe and extreme heat stress due to its arid climate and prolonged exposure to solar radiation. Additionally, highland regions, such as Mambila and Plateau, consistently reported elevated event counts by NET and UTCI, demonstrating their effectiveness in capturing microclimatic variations. These results highlight the growing prevalence of heat stress events across Nigeria and the need for tailored heat risk assessments.

Investigating the Wound Healing Potential of CuCO3 Nanoparticles in Alloxan-Induced Diabetic Albino Mice: An Experimental and In Silico Approach - Muhammad Saqib Rafiq; Jabbir Ali Khan; Ashfaq Ahmad Shah Bukhari; Samra Shafqat; Ahmad Waheed; Muhammad Yasir Abbas; Muhammad Waseem Aslam; Imran Ibrahim Shaikh; Khalid S. Almaary; Muhammad Saleem Khan (Biological Trace Element Research, 2025)

Synergistic effects of Trichoderma spp. and sodium silicate against Fusarium wilt of tomato: in vitro and greenhouse evaluation - Kamal A. M. Abo-Elyousr; Najeeb M. Almasoudi; Magdi A. A. Mousa; Omer H. M. Ibrahim; Mansour M. El-Fawy; Muhammad Imran; Nashwa M. A. Sallam (Journal of Plant Pathology, 2025)

NMR-based metabolic profiling and antioxidant activity of Eleutherine bulbosa bulb ethanol extract - Islamudin Ahmad; Lizma Febrina; Baso Didik Hikmawan; Junaidin Junaidin; Herman Herman; Muhammad Faisal; Erwin Samsul; Iswahyudi Iswahyudi; Arsyik Ibrahim; Reza Yuridian Purwoko; Tia Okselni; Marissa Angelina; et al. (Natural Product Research, 2025)

Molecular detection of helicobacter pylori amongst patients with peptic ulcer disease in Nigeria - Idayat Omotayo Oduola; Abubakar Basiru; Kabiru Mohammed; Asiya Umar; Abdulbariu Ogirima Uhuami; Lubabatu Ibrahim; Abdurrauf Auwal Muhammad; Kaisong Huang; Abdurrahman Hassan Jibril (Next Research, 2025)

Porosity estimation using deep learning and ImageJ: Implications for reservoir characterization in Central Luconia Miocene carbonates - Abdulrahman Danlami Isa; Haylay Tsegab Gebretsadik; Abdulrahman Muhammad; Hassan Salisu Mohammed; Ibrahim Muhammad Kurah; Adamu Kamaliddeen Salisu (Marine and Petroleum Geology, 2025)

Hydrothermal synthesis and in-situ polymerization of PPy@MnCo₂O₄ nanohybrids for fast visible-light photocatalytic degradation of ibuprofen - Muhammad Aadil; Mohamed Abdel Rafea; Magdi E.A. Zaki; Mohamed Ibrahim Attia; Mohamed R. El-Aassar; Abdullah K. Alanazi; Sonia Zulfiqar; Sidra Mubeen (Journal of Water Process Engineering, 2025)

Biphasic synthesis of Pd/Ovs-TiO₂ (black) for efficient moxifloxacin degradation and toxicity mitigation - Muhammad Imran Kanjal; Iram Yasmin; Syed Kashif Ali; Muhammad Wasim Afzal; Muhammad Irfan Ahamad; Mohamed A. Habib; Ahmed B.M. Ibrahim; Rana Muhammad Zulqarnain (Journal of Water Process Engineering, 2025)

Orange peel derived biochar assisted rGO@MoS₂ composite for visible light driven ciprofloxacin degradation and hydrogen evolution - Asim Jilani; Mohsin Raza Dustgeer; Mohammad Omaish Ansari; Alishbah Zaka; Muhammad Adil Mansoor; Ammar A. Melaibari; Hussameldin Ibrahim (Journal of Water Process Engineering, 2025)

Exploring the impact of seasonal variation on the toxicological profile of Σ2PFAS in surface water bacterioplankton communities - Yiping Li; Muhammad Ibrahim; Cheng Yue; Yaning Wang; Pan Hongzhe; Abdulhakim Wagini Hassan; Yan Chunmin (Journal of Hazardous Materials, 2025)

Innovative Fe-F-Co-doped NiO nanoarrays: Pioneering high-efficiency electrochemical nitrate reduction to ammonia - Anum Bilal; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Ibrahim Khan; Imran Mahmood Khan; Muhammad Sajjad; Shahid Ali; Nicholas M. Musyoka; Guocong Liu; Abd-ElAziem Farouk; Nouf M. Alyami (Journal of Environmental Chemical Engineering, 2025)

Physicochemical characterization, lipid-modulating effects, and proteomic insights of Malaysian Sacha Inchi (Plukenetia volubilis L.) seed oil in HepG2 cells - Mariam Fardush; Norsyahida Mohd Fauzi; Ho Wen Yan; Armania Nurdin; Ibrahim Jantan; Nor Azlan bin Nor Muhammad; Siti Nurlisa Hazim; Sarmila Hanim binti Mustafa; Kimberlyn Feguro (Food Bioscience, 2025)

Growth phenology, cambial activity, and formation of secondary vascular tissues in Juniperus procera trees - Pervaiz R. Khan; Rahmah N Al-Qthanin; Ibrahim M. Aref; Muhammad Iqbal (Flora, 2025)

Energy transport in ternary hybrid nanofluid with variable thermal conductivity under the combined effects of electroviscous, electric potential, and heat generation - Shafiq Ahmad; Aamir Abbas Khan; Muhammad Naveed Khan; Salah Knani; N. Ameer Ahammad; Ibrahim E. Elseesy (Dynamics of Atmospheres and Oceans, 2025)

Integrating a hybrid statistical Downscaling-based HMM-RF model for enhanced rainfall prediction in Selangor - Noor Hamizah Mohamad Sani; Shazlyn Milleana Shaharudin; Muhammad Safwan Ibrahim; Upmanu Lall; Mou Leong Tan (Stochastic Environmental Research and Risk Assessment, 2025)
Accurate rainfall prediction is crucial for effective weather forecasting and climate modeling. This study aims to assess the effectiveness of a novel hybrid Statistical Downscaling-based Hidden Markov Model-Random Forest Model (SD-based HMM-RF) for rainfall prediction in Selangor, Malaysia. It also examines the best imputation methods for handling missing data, selects predictors for statistical downscaling by reducing dimensionality, and addresses uncertainties in zero-bounded rainfall data. The study utilized observed data (predictand) from 33 rainfall stations and atmospheric data (predictor), covering the period from 2008 to 2018. Seven imputation methods were tested: Mean Imputation (MeI), Median Imputation (MI), Expectation-Maximization (EM) Algorithm, Markov Chain Monte Carlo (MCMC), k-Nearest Neighbor (kNN), Non-iterative Partial Least Square (NIPALS), and Random Forest (RF). Principal Component Analysis (PCA) was used to manage high-dimensional data and select predictors, while HMM was applied to address uncertainties in zero-bounded rainfall data. Five hybrid models: Random Forest (SD-based HMM-RF), Support Vector Machine (SD-based HMM-SVM), Decision Tree (SD-based HMM-DT), k-Nearest Neighbors (SD-based HMM-KNN), and Artificial Neural Networks (SD-based HMM-ANN) were evaluated. Performance metrics, including Root Mean Square Error (RMSE), Mean Absolute Error (MAE), Mean Forecast Error (MFE), Nash-Sutcliffe Efficiency (NSE), Kling-Gupta Efficiency (KGE), and Rank Correlation Coefficient (ρ), were used to identify the most accurate rainfall prediction model. MI emerged as the best-performing method, achieving the lowest RMSE (0.146) and MAE (0.021), along with the highest NSE (1.000) and Pearson correlation coefficient, r (1.000) for all stations. PCA identified five principal components (PC1–PC5) with a cumulative variance of up to 93.254%. HMM analysis determined that three hidden states (K = 3) at iteration 2000 were optimal, with the lowest Bayesian Information Criterion (BIC) of 260,018.30. Among the models, SD-based HMM-RF consistently outperformed others, showing superior accuracy and reliability in rainfall prediction, as indicated by its RMSE (2.298), NSE (0.752), MAE (1.900), near-zero MFE (-0.049), KGE (0.526), and ρ (0.898). By improving rainfall prediction accuracy, the novel hybrid model can enhance early warning systems, inform infrastructure planning, and reduce the economic impact of future flooding events, thereby contributing to more resilient urban development in the region.

Sustainable Modeling and Optimization of Green-Synthesized ZnO Nanoparticles and Humic-Citric Amendments: Enhancing Growth, Nutrient Uptake, and Flowering of Solidago in Saline Soils - Khaled M.A. Ramadan; Hisham Mohamed; Muhammad Munir; Samah M. Youssef; Hossam S. El-Beltagi; Hani S. Saudy; Sallah A. Al Hashedi; Muhammad Naeem Sattar; Ahmed S. Abdelbaky; Ibrahim A. A. Mohamed; Mohamed M. El-Mogy; Wael M. Semida; et al. (Journal of Soil Science and Plant Nutrition, 2025)

TIPE2 deficiency amplifies inflammation and immune dysregulation in MASH through modulating hepatic lipid metabolism and immune cell function - Lawan Rabiu; Pengchao Zhang; Zhongming Liu; Yexiao Tang; Khalid I. Gidado; Abdulrahman Ibrahim; Muhammad A. Saliu; Hafiza Kashaf Tariq; Xiaochun Wan; Shu Xu; Zhiming Xu; Guizhong Zhang (Inflammation Research, 2025)

Rosa moschata leaf extract modulates complete freund’s adjuvant-induced polyarthritis in Wistar rats via regulation of pro-inflammatory and inflammatory biomarkers - Amr S. Abouzied; Uzma Saleem; Maryam Farrukh; Umme Farwa; Areej M. Alsolami; Fatima A. Jaber; Tourki A. S. Baokbah; Ibrahim Aljaezi; Nouf Abdullah Alharbi; Muhammad Ajmal Shah; Ana Sanchez Silva; Norah K. Algarzae (Inflammopharmacology, 2025)

Ethnobotanical inventory and threat assessment of medicinal plants in Lajbouk Valley, Khyber Pakhtunkhwa, Pakistan - Shaha Buddin; Syed Mukaram Shah; Muhammad Ibrahim; Mohsin Ullah; Waseem Ahmed Khattak; Muhammad Anas; Asif Kamal (Genetic Resources and Crop Evolution, 2025)

A genome-wide approach to the comprehensive analysis of the serine carboxypeptidase-like protein family in Solanum lysopersicum L. - Arshad Jamil; M. A. Habib; Ahmed B. M. Ibrahim; Bushra Ahmad; Muhammad Zulfiqar Ahmad; Jamal Abdul Nasir (Genetic Resources and Crop Evolution, 2025)

Microplastic Pollution: Sources, Degradation Mechanisms, Analytical Advances, and Mitigation Strategies for Environmental Sustainability - Najwa Ibrahim; Amir Muhammad Noh Amin Abdul Rahman; Mohamad Danial Shafiq; Zainovia Lockman; Mariatti Jaafar; Yutaka Kameda (Reviews of Environmental Contamination and Toxicology, 2025)

Sustainable integration of aquaculture wastewater treatment using Chlorococcum sp. in photobioreactor systems: Evaluation of nutrient removal, biomass productivity, and operational performance - Zubair Hashmi; Ibrahim Maina Idriss; Rieza Zulrian Aldio; Nur Aqidah Donglah; Juliana Zaini; Yusuf Wibisono; Muhammad Roil Bilad (Algal Research, 2025)

Computational optimization of MALT1 inhibitors against DLBCL: a QSAR-guided molecular docking and dynamics study - Josiah Joseph Isah; Adamu Uzairu; Sani Uba; Muhammad Tukur Ibrahim (In Silico Pharmacology, 2025)

Hemisynthesis of lupeol and betulin derivatives and their in vitro antimalarial activity against Plasmodium falciparum FCR3 - Ibrahim Dankane Bafarawa; Muhammad Solehin Abd Ghani; Arba Pramundita Ramadani; Shofiatul Fuadah; Muhammad Bisyrul Hafi Othman; Mohammad Nasir Ibrahim; Sook Yee Liew; Mohammad Tasyriq Che Omar; Habibah A. Wahab; Mohamad Nurul Azmi (Natural Product Research, 2025)

Magnetic MOF-Based Immunosensing Strategy with Quantum Dot Labeling for Efficient Electro-chemiluminescent Detection of Alpha-fetoprotein - Mariyam Fatima; Muhammad Faizan; Iqra Jabeen; Muhammad Fiaz; Ansar Ali; Syed Kashif Ali; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Ibrahim Jafri; Abd-ElAziem Farouk (Journal of Fluorescence, 2025)

Reservoir water-level operations to manage biogeochemical turnover - Yiping Li; Yaning Wang; Xiaodong Hu; Yue Cheng; Ya Zhu; Yuxuan Zhou; Hongzhe Pan; Ronghui Li; Muhammad Ibrahim; Carlo Gualtieri (Water Research, 2025)

In silico identification of GTPase inhibitors from selected anti-gonorrheal plants against Neisseria gonorrhoeae - Blessing O. Awoyemi; Badmus Jamiu Damilare; Abdullahi Tunde Aborode; Che Muhammad Khairul Hisyam Ismail; Abdulqohar Adebayo; Haruna Isiyaku Umar; Ibrahim Akindeji Makinde; Ridwan Opeyemi Bello; Sodiq Fakorede; Mohammed M. Alshehri; Ahmed F. Alanazi (The Nucleus, 2025)

Physalis peruviana and Lactobacillus lysates as modulators of lipid metabolism and oxidative stress: a natural alternative to statin therapy - Manal Mused Almatrafi; Alaa H. Nada; Ahmed S. Doghish; Dalia Elebeedy; Aml Ghanem; Eman Fayad; Haitham Ibrahim El-Mekkawy; Osama A. Mohammed; Samy Y. Elkhawaga; Dalal Sulaiman Alshaya; Fatimah Hadadi; Ahmad F. Alhomodi; et al. (Folia Microbiologica, 2025)

Computer-aided design process of possible antisickling agents using molecular docking, pharmacokinetic assessment, homology modeling, and molecular dynamic studies targeting Hba protein - Stephen Ejeh; Habiba Asipita Otaru; Muhammad Tukur Ibrahim; Abdullahi Bello Umar; John Enyi Ejeh; Abduljelil Ajala; Samuel Ndaghiya Adawara; Ramith Ramu; Fabian Audu Ugbe; Joshua John; Idongesit Bassey Anweting (In Silico Pharmacology, 2025)

First report of Alternaria alternata causing leaf blotch and fruit spot of apple in Pakistan - Sami Ullah; Samiullah; Naseer Ahmed; Muhammad Kamran; Muhammad Ibrahim; Safdar Ali; Adnan Kashif (New Zealand Journal of Botany, 2025)

From shadow to sustainability: How informality, environmental taxes, and green innovation reshape carbon and biodiversity futures in the G7 countries - Sami Ur Rahman; Imran Ali Khan; Fariha Sami; Javed Hussain; Muhammad Ibrahim Khan (Journal of Environmental Management, 2025)

An innovative integrated system developed for hydrogen fuel production and sulfur recovery from acid gas streams for sustainable development - Muhammad Ishaq; Ibrahim Dincer (Journal of Environmental Chemical Engineering, 2025)

Electro-microbial destruction of ‘forever chemicals’: Recent advances and imminent challenges - Muhammad Hassan; Miao Lv; Jedsada Chuiprasert; Zhiqi Zou; Ibrahim Abusallout; Sikai Chen; Hugo Olvera-Vargas; Ghulam Abbas Ashraf; Hisham S.M. Abd-Rabboh; Suwanna Kitpati Boontanon (Chemical Engineering Journal, 2025)

Low-Level Arsenic Removal from Drinking and Wastewater Using La@MOF-808 in Lahore, Pakistan - Hassan Nawaz; Muhammad Ibrahim; Hirra Anjum; Abid Mahmood; David V. P. Sanchez (International Journal of Environmental Research, 2025)

Assessing the genetic structure of olive cultivars in Mansehra, Pakistan for improved crop production - Ibrahim Khan; Shabnam Niaz; Muhammad Zafar; Salman Majeed; Eman Alhomaidi; Maha Aljabri; Trobjon Makhkamov; Nasibakhon Naraliyeva; Akramjon Yuldashev; Dilnoza Sotiboldiyeva; Zulunov Islom; Aneta A. Ptaszyńska (Genetic Resources and Crop Evolution, 2025)

Palynology as a taxonomic tool in the identification of riparian Moraceae species - Muhammad Rizwan Khan; Muhammad Zafar; Salman Majeed; Trobjon Makhkamov; Nasibakhon Naraliyeva; Inomjon Bakhramov; Sobhay M. Ibrahim; Munira Inomova; Bakhtiyor Rakhimov; Aneta A. Ptaszyńska (Genetic Resources and Crop Evolution, 2025)

Advancements in photobioreactor systems: Optimizing operations for enhanced microalgal growth and bioremediation - Zubair Hashmi; Ibrahim Maina idriss; Juliana Zaini; Muhammad Saifullah Abu Bakar; Muhammad Roil Bilad (Algal Research, 2025)

A systematic review on the development and efficacy of nano-based vaccine in aquaculture - Shamsu Ibrahim Ishaq; Muhammad Salahudin Kheirel Anuar; Abdulwakil Olawale Saba; Ina Salwany Md Yasin; Che Azurahanim Che Abdullah; Annas Salleh; Muhammad Farhan Nazarudin; Mohd Termizi Yusof; Mohammad Noor Amal Azmai (Aquaculture International, 2025)

Molecular characterization and green synthesis of iron oxide nanoparticles from Ureibacillus chungkukjangi for methylene blue degradation - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Shumaila Ibrahim; Maida Salah Ud Din; Maryam M. Alomran; Ashwag Shami; Fakhria A. Al-Joufi; Ahmad A. Alghamdi; Abdullah A. Alqasem; Ahmed M. Basri; Majid Alhomrani (Antonie van Leeuwenhoek, 2025)

First report of Schistocerca gregaria oil fractions against multidrug-resistant Pseudomonas aeruginosa clinical isolates - Tariq Mohammed Abdulazeez; Abdullateef Yusuf; John Sow Gudzan; Hussaini Ibrahim Mohammed; Muhammad Tukur Ibrahim; Helena Fodeke; Norashiqin Misni (Natural Product Research, 2025)

Insect-based biofuels and animal feed additives: A sustainable energy and agricultural solution for Africa's future - Abdulbariu Ogirima Uhuami; Hadiza Aliyu; Badiat Jamila Danjumma; Saadatu Mohammed Bawa; Aminu Muhammad Lawal; Shamsudeen Umar Dandare; Aliyu Ibrahim Dabai (Next Research, 2025)

Optimizing diagnostic & management strategies for common arrhythmias in critically Ill surgical patients: A scoping review - Philip M. Lee; Kirk D. Dourvetakis; Andrew Ford; Minna Haddadi; Muhammad Usman Awan; Alexander Brown; Joseph Ibrahim; Adel Elkbuli (Next Research, 2025)

Roles of Fox gene in the development and reproduction of diamondback moth - Anam Noreen Abbas; Mubashir Tariq; Faisal Munir; Uroosa Zaheer; Ibrahim Adam; Muhammad Asad; Guang Yang (Journal of Insect Physiology, 2025)

Heavy metals contamination in water-sediment systems of a large drinking water reservoir in southern China: Large-scale assessment and risk-based management - Yiping Li; Ya Zhu; Yu Chen; Can Wang; Guoli Zhao; Haiping Pan; Chuer Wang; Hangtong Bao; Muhammad Ibrahim; Eyram Norgbey (Journal of Cleaner Production, 2025)

Ultrasound-assisted dispersive solidified floating organic drop microextraction based on a novel thiazolyl azo deep eutectic solvent for antimony determination in water and food samples - Ebaa Adnan Azooz; Shaimaa Rahim Hussein; Ibrahim A. Naguib; Muhammad Farooque Lanjwani; Mustafa Tuzen (Food Chemistry, 2025)

Tropical-extratropical interactions: the atmospheric dynamics behind Dubai's extreme precipitation in April 2024 - Muhammad Latif; Muhammad Usman; Abdul Malik; Sateesh Masabathini; Burhan Ahmad; Luqman Atique; Fatima Alhammadi; Ibrahim Hoteit (Natural Hazards, 2025)

The Role of Silver Nanoparticles and Bacillus subtilis in Modulating Morpho–Physio–Biochemical Responses in Wheat (Triticum aestivum L.) Under Arsenic Stress - Mohammad K. Okla; Sadia Javed; Muhammad Faran Tahir; Ibrahim A. Saleh; Muhammad Anas; Muhammad Hamzah Saleem; Temoor Ahmed; Abdulrahman Abdullah Alatar; Bandar M. AlMunqedhi; Shafaqat Ali (Journal of Soil Science and Plant Nutrition, 2025)
Soil contamination with toxic heavy metals [such as arsenic (As)] is becoming a serious global problem because of the rapid development of the social economy. Although plant growth-promoting rhizo-bacteria (PGPR) and nanoparticles (NPs) are the major protectants to alleviate metal toxicity, the study of these chemicals in combination to ameliorate the toxic effects of As is limited. Therefore, the present study was conducted to investigate the effects of different levels of Bacillus subtilis (5 and 10 mg L –1 ) and silver (Ag)–NPs (10 and 20 mg kg –1 ) on morpho-physiological and antioxidative defense attributes, which was spiked with different levels of As [0 mM (i.e., no As), 100, and 200 mg kg –1 ] in wheat ( Triticum aestivum L.) seedlings. Results from the present study showed that the increasing levels of As in the soil significantly ( P < 0.05) decreased plant growth and biomass, photosynthetic pigments, gas exchange attributes, sugars, and nutritional contents from the roots and shoots of the plants. In contrast, increasing levels of As in the soil significantly ( P < 0.05) increased oxidative stress indicators in term of malondialdehyde (MDA), hydrogen peroxide (H 2 O 2 ), and electrolyte leakage (EL), and also increased organic acid exudation patter in the roots of T. aestivum . The negative impact of As toxicity can overcome the application of B . subtilis and Ag − NPs, which ultimately increased plant growth and biomass by capturing the reactive oxygen species (ROS), and decreased oxidative stress in T. aestivum by decreasing the As contents in the roots and shoots of the plants. Research findings, therefore, suggest that the combined application of B . subtilis and Ag − NPs can ameliorate As toxicity in T. aestivum , resulting in improved plant growth and composition under metal stress, as depicted by balanced exudation of organic acids. Graphical Abstract

Immuno-nutritional therapy in experimental autoimmune encephalomyelitis: a translational pathway to multiple sclerosis management - Mansur Aliyu; Ali Akbar Saboor-Yaraghi; Muhammad Ibrahim Getso; Fatema Tuz Zohora (Inflammopharmacology, 2025)

Efficacy and safety of colchicine post myocardial infarction: a systematic review, meta-analysis and meta-regression analysis of randomized clinical trials - Farhan Naeem; Shehroze Tabassum; Muhammad Burhan; Elsayed Balbaa; Ahmed Ibrahim; Shrouk Ramadan; Usama Qamar; Fatima Saeed; Mohamed Abuelazm; Dmitry Abramov; Timir K. Paul; Yasar Sattar (European Journal of Clinical Pharmacology, 2025)

Geostatistical and multivariate analysis of phosphate evolution and its relationship with heavy metals in shallow groundwater in a Semi-Arid Basin - Saadu Umar Wali; Noraliani Binti Alias; Abdulqadir Abubakar Usman; Abdullahi Umar; Nasiru Muhammad; Ismail Usman Kaoje; Buhari Samaila; Basiru Aliyu; Habiba Muhammad Ladan; Mudassiru Atiku; Sa’ad Ibrahim (Earth Science Informatics, 2025)

Dispersal of Per- and polyfluoroalkyl substances (PFASs) and toxic metals: a probable influence of inorganic fluoride and ionic strength in the Shiqi River Basin of Nanjing City, South-Eastern China - Muhammad Ibrahim; Yiping Li; Xiaolin Zhu; Yaning Wang; Yan Chunmin; Hafsat Alhassan Danjaji; Abdulhakim Wagini Hassan; Adam Umar Jibo (Clean Technologies and Environmental Policy, 2025)

Synthesis, Spectroscopic, Electronic and Molecular Docking Studies of Pyrazole Based Chalcones as Potential Anticancer Agents - Noreen Aslam; Muhammad Ibrahim; Afifa Yousuf; Muhammad Arif Ali; Jonathan M. White; Ansa Madeeha Zafar; Mussarat Jabeen; Misbahul Ain Khan (Journal of Fluorescence, 2025)

Reaction and transformation behaviors of ferric oxides and titanium oxide in diasporic bauxite during an alkaline hydrothermal process - Muhammad Ibrahim; Yanjun Ou; Shuhua Ma; Xiaohui Wang (Hydrometallurgy, 2025)

Evaluation of the Water Quality Index of some Drains Linked to the Bahr El-Baqar Drain and Study of Heavy Metals in Vegetables Grown Around Them and Their Potential Risks to the Health - Haifa A. S. Alhaithloul; Khalid G. Soliman; Ahmed H. Ibrahim; Awatif M. Abdulmajeed; Alaa Muqbil Alsirhani; Mohamed A. Abdein; Mesfer M. Alqahtani; Fauzeya Mateq Albalwe; Muhammad Tahir; Maha M. Elshamy; Elmadawy G. A. Kedra; Gamal A. Zayed; et al. (Water, Air, & Soil Pollution, 2025)

A Bayesian framework for crop model calibration: A case study in the US Corn Belt - Matteo G. Ziliani; Muhammad U. Altaf; Trenton E. Franz; Bangyou Zheng; Scott Chapman; Justin Sheffield; Ibrahim Hoteit; Matthew F. McCabe (European Journal of Agronomy, 2025)

Drug-eluting stent versus bare metal stent for symptomatic intracranial stenosis: a comparative systematic review and meta-analysis study - Mohammad Sina Mirjani; Pouria Delbari; Muhammad Hussain Ahmadvand; Saba Sabet; Zahra Ardestani; Mohammad Emad Sharifi; Sina Hatami; Mansoureh Jabari; Amirali Barkhordarioon; Mohammad Taha Akbari Javar; Amirmohammad Bahri; Sina Ahmadi; et al. (European Journal of Clinical Pharmacology, 2025)

Virtual screening and molecular dynamic simulations of Desulfovibrio vulgaris dissimilatory sulfite reductase inhibitors for the control of sulphate reducing bacteria - Oluwafemi Adebayo Oyewole; Rahma Muhammad Adamu; Umar Saidu; Sekelwa Cosa; Mthokozisi B. C. Simelane; Md. Atiar Rahman; Mohammed Auwal Ibrahim (In Silico Pharmacology, 2025)

Quantum Chemical Insights into Metal-Ion Enhanced NLO Response of a Fluorescent Probe for Advanced Sensing Application - Asad Ullah; Muhammad Arif Ali; Sabir Ali Siddique; Muhammad Ibrahim; Hong Liang Xu; Abdul Rauf; Amal M. Al-Mohaimeed; Wedad A. Al-onazi; Muhammad Arshad (Journal of Fluorescence, 2025)

Utilizing silica-rich waste material for enhancing the properties of concrete and its environmental assessment - Mohammed Ibrahim; Muhammad Kalimur Rahman; Ashraf A. Bahraq (Environmental Science and Pollution Research, 2025)

Catharanthus roseus (L.) G. Don: A herb with the potential for curing breast cancer - Syeda Syesha Saman; Aqsa Hanif; Sawsan S. Al-Rawi; Ahmad H. Ibrahim; Muhammad Adnan Iqbal; Sabha Khalid; Adnan Majeed; Athar Mahmood; Farhan Ahmad (Next Research, 2025)

Talaromyces purpureogenus-mediated mycosynthesis of aluminium oxide nanoparticles and characterization of the physicochemical properties at different calcination temperatures - Muhammad Salahudin Kheirel Anuar; Che Azurahanim Che Abdullah; Muhammad Farhan Nazarudin; Shamsu Ibrahim Ishaq; Mohammad Noor Amal Azmai; Annas Salleh; Ina Salwany Md Yasin; Mohd Termizi Yusof (Fungal Biology, 2025)

Recent advances in synthesis and modulation of 2D heterostructures for sensing and detection applications - Rumaisa Tariq; Waseem Raza; Karma M. Albalawi; Arshad Hussain; Munir Ahmad; Muhammad Asim Mushtaq; Mohamed H. Helal; Ibrahim A. Shaaban; Shaukat Khan; Muhammad Sufyan Javed (Chemical Engineering Journal, 2025)

Interesterification of waste cooking oil via microwave irradiation for glycerol-free biodiesel production - Muhammad Umer Qadeer; Muhammad Ayoub; Muhammad Hamza Nazir; Muhammad Asad Javed; Zulqarnain; Imtisal Zahid; Mariam Ameen; Farooq Sher; Alhassan Ibrahim (Biomass and Bioenergy, 2025)

Investigation of Photocatalytic and Antibacterial Study of Mo doped ZnCo2O4/rGO Nanohybrid Under Visible Light - Maria Zulfiqar; Gaber A. M. Mersal; Ahmed M. Fallatah; Mohamed M. Ibrahim; Hafiz Muhammad Tahir Farid; Muhammad Aslam; Zeinhom M. El-Bahy (Water, Air, & Soil Pollution, 2025)

Epigallocatechin 3-gallate-induced neuroprotection in neurodegenerative diseases: molecular mechanisms and clinical insights - Md. Rezaul Islam; Abdur Rauf; Sumiya Akter; Happy Akter; Md. Ibrahim Khalil Al-Imran; Samiul Islam; Meherun Nessa; Chaity Jahan Shompa; Md. Nabil Rihan Shuvo; Imtiaz Khan; Waleed Al Abdulmonem; Abdullah S. M. Aljohani; et al. (Molecular and Cellular Biochemistry, 2025)
Neurodegenerative diseases (NDs) are caused by progressive neuronal death and cognitive decline. Epigallocatechin 3-gallate (EGCG) is a polyphenolic molecule in green tea as a neuroprotective agent. This review evaluates the therapeutic effects of EGCG and explores the molecular mechanisms that show its neuroprotective properties. EGCG protects neurons in several ways, such as by lowering oxidative stress, stopping Aβ from aggregation together, changing cell signaling pathways, and decreasing inflammation. Furthermore, it promotes autophagy and improves mitochondrial activity, supporting neuronal survival. Clinical studies have demonstrated that EGCG supplementation can reduce neurodegenerative biomarkers and enhance cognitive function. This review provides insights into the molecular mechanisms and therapeutic potential of EGCG in treating various NDs. EGCG reduces oxidative stress by scavenging free radicals and enhancing antioxidant enzyme activity, aiding neuronal defense. It also protects neurons and improves cognitive abilities by inhibiting the toxicity and aggregation of Aβ peptides. It changes important cell signaling pathways like Nrf2, PI3K/Akt, and MAPK, which are necessary for cell survival, cell death, and inflammation. Additionally, it has strong anti-inflammatory properties because it inhibits microglial activation and downregulates pro-inflammatory cytokines. It improves mitochondrial function by reducing oxidative stress, increasing ATP synthesis, and promoting mitochondrial biogenesis, which promotes neurons’ survival and energy metabolism. In addition, it also triggers autophagy, a cellular process that breaks down and recycles damaged proteins and organelles, eliminating neurotoxic aggregates and maintaining cellular homeostasis. Moreover, it holds significant promise as an ND treatment, but future research should focus on increasing bioavailability and understanding its long-term clinical effects. Future studies should focus on improving EGCG delivery and understanding its long-term effects in therapeutic settings. It can potentially be a therapeutic agent for managing NDs, indicating a need for further research.

Innovative drought monitoring: development and application of the multi-regional aggregated standardized drought index (MRASDI) - Asad Ellahi; Ibrahim A. Nafisah; Mohammed M. A. Almazah; Nafisa A. Abasheir; Ijaz Hussain; Muhammad Mubashar Dogar (Earth Science Informatics, 2025)

Endophytes of Zingiberaceae: distribution and bioactivity of their bioactive metabolites - Nor Hazwani Mohd Hasali; Muhammad Shahbaz; Jaya Seelan Sathiya Seelan; Nazirul Azam Ibrahim; Christophe Wiart; Nivaarani Arumugam; Mohammed Abdus Salam; Muneeb M. Musthafa; Suganthi Appalasamy (Archives of Microbiology, 2025)

Retraction notice to “Biodiesel synthesis from Prunus bokhariensis non-edible seed oil by using green silver oxide nanocatalyst” [Chemosphere 291, Part 2, March 2022, 132780] - Sumreen Dawood; Mushtaq Ahmad; Muhammad Zafar; Saira Asif; Jiří Jaromír Klemeš; Awais Bokhari; Muhammad Mubashir; Ning Han; Mohamed M. Ibrahim; Zeinhom M. El-Bahy; Kuan Shiong Khoo (Chemosphere, 2025)

Towards greener metal production: A life cycle assessment model for copper-gold-silver mining and mineral processing operations - Muhammad Burhan Memon; Ming Tao; Tufail Ahmed; Zheng Yang; Muhammad Ibrahim; Sami Ullah (Process Safety and Environmental Protection, 2025)

Impact of irrigation schedule and integrated nutrient management on wheat yield and nutrients uptake under semi-arid regions - Murad Ali; Abdul Bari; Muhammad Ibrahim; Iftikhar Ahmed; Uzair Ahmed; Rabia Zafar; Waqas Ahmad; Muhammad Saeed; Muhammad Khalid (Irrigation Science, 2025)

Life cycle assessment of turning hydrogen sulfide recovered from sea waters into clean hydrogen - Muhammad Ishaq; Ibrahim Dincer (Resources, Conservation and Recycling, 2025)

An improved sulfur iodine cycle for sour gas purification and hydrogen fuel production for better environment - Muhammad Ishaq; Ibrahim Dincer (Journal of Environmental Management, 2025)

Superhydrophilic wettability porous materials from construction tooil/water separation applications - Muhammad Naseem; Mansoor Sultan; Mazhar ul Islam; Abdul Kareem; Nisar Ali; Ibrahim Khan; Shakeel Ahmad; Farooq nawaz; Adnan Khan; Farman Ali; Rayya Ahmed Al Balushi; Mohammad M. Al-Hinaai; et al. (Fuel, 2025)

Exploring the Mechanisms of Halophilic Bacterium SPSB2 and Mannitol in Mitigating Sodium Chloride and Arsenic Stress in Solanum Lycopersicum - Lubna; Muhammad Aizaz; Shima Ahmed Ali Alrumaidhi; Rawan Ahmed Mohammed Alhinai; Reem Saif Mohammed A. L. Kalbani; Ibrahim Khan; Saqib Bilal; Sajjad Asaf; Ahmed AL-Harrasi (Journal of Crop Health, 2025)

A novel CLRN2 variant: expanding the mutation spectrum and its critical role in isolated hearing impairment - Farooq Ahmad; Arif Mahmood; Ibrahim Abdullah Almazni; Afnan Mohammed Shakoori; Fatemah Alhakami; Qamre Alam; Muhammad Ismail; Muhammad Umair (Genes & Genomics, 2025)

Rheological and chemical properties of reclaimed asphalt pavement using polyethylene terephthalate (PET) additive as a modifier - Christiana Adebola Odubela; Haryati Yaacob; Muhammad Naqiuddin Bin Mohd Warid; Khairil Juhanni Abd Karim; Nurul Hidayah Binti Mohd Kamaruddin; Zaid Hazim Al-Saffar; Muhammad Ibrahim Khalili Rahim (Environmental Science and Pollution Research, 2025)

Foaming in wastewater treatment plants: Deciphering biological foaming and challenges in MBR systems - Muhammad Ibrahim; Narada Dayarathne; Jun Wei Lim; Shukra Raj Paudel; Muhammad Kashif Shahid; Bandita Mainali (Journal of Water Process Engineering, 2025)

Supplementing high-fiber olive pomace and multi-enzymes to broiler chicken’s diet can improve health and performance - Osama Rahman Ghaffar; Dastan Mohammed Khoshnaw; Omer Rasool Ahmed; Sarwar Omer Aziz; Asrin Abdollahi; Nihayat Ibrahim Mohammed; Karzan Kareem Saleh; Niga Rzgar Ahmad; Mzhda Mohammed Majeed; Shiraz Ismail Muhammad; Srwsht Farhad Osman; Hawkar Azad Khdir (Tropical Animal Health and Production, 2025)

Organic Amendments Enhanced Phytoremediation, Physio-Chemical Functions, Growth and Productivity of Zea mays L. in Diesel-Contaminated Soil - Muhammad Sarfraz Ahmad; Ghazala; Fahd Rasul; Muhammad Ibrahim; Abid Mahmood (Journal of Soil Science and Plant Nutrition, 2025)

Explainable artificial intelligence-based compressive strength optimization and Life-Cycle Assessment of eco-friendly sugarcane bagasse ash concrete - Varisha Rizwan; Syed Muhammad Ibrahim; Mohd Moonis Zaheer; Ateekh ur Rehman (Environmental Science and Pollution Research, 2025)

Exogenous application of melatonin and jasmonic acid protects the sugar beet from heat stress by modulating the enzymatic antioxidants deference mechanism and accumulation of organic osmolytes - Muhammad Irfan; Ahmed Abou El-Yazied; Muhammad Sheeraz; Shabir Hussain; Abdul Sattar; Qasim Ali; Hany G. Abd El-Gawad; Fahad Mohammed Alzuaibr; Maha Mohammed Alharbi; Siham M. Al-Balawi; Doaa Bahaa Eldin Darwish; Eldessoky S. Dessoky; et al. (Acta Physiologiae Plantarum, 2025)

Citrus phytochemicals as potential therapeutics against asiatic citrus psyllid and Candidatus Liberibacter asiaticus: targeting the tripartite interaction - Muhammad Awais; Muhammad Ali; Mohsin Javed; Faisal Hanif; Muhammad Nouman; Ammar Zidan; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Abd-ElAziem Farouk; Ibrahim Jafri (Journal of Plant Pathology, 2025)

Heavy metals pollution in riverine sediments: Distribution, source, and environmental implications - Kifayatullah Khan; Muhammad Younas; Muhammad Yaseen; Hassan Sher; Afsheen Maryam; Sobhy M. Ibrahim; Adnan Adnan; Ahmad Ali; Muhammad Fawad; Akhtar Zeb Khan; Nasrullah Khan; Izaz Ali Shah (Environmental Monitoring and Assessment, 2025)

T-2 mycotoxin: From occurrence and toxicokinetics to recent advances in aptasensor-based detection strategies and future perspectives for enhanced food safety - Ali Raza; Sobia Niazi; Muhammad Shoaib; Imran Mahmood Khan; Faizan Ul Haq; Khubaib Ali; Ibrahim Khan; Yin Zhang; Zhouping Wang (Trends in Food Science & Technology, 2025)

Novel mutations in exon 2 of follistatin (FST) gene associated with wool fiber diameter in sheep - Tahira Mir; Muhammad Ibrahim; Muhammad Siraj; Sajid Ali Khan Bangash; Sher Hayat Khan; Majid Khan; Muhammad Tayyab; Sohail Ahmad (Small Ruminant Research, 2025)

Prevalence and herd-level risk factors associated with Brucella infection in smallholders keeping large ruminants - Abrar Hussain; Sabir Hussain; Mamoona Chaudhry; Muhammad Asif Ali; Ibrahim Elsohaby; Ubaid-ur-Rehman Zia; Olivier Sparagano (Research in Veterinary Science, 2025)

Comprehensive analysis of leak impacts on liquid-gas multiphase flow using statistical, wavelet transform, and machine learning approaches - Hicham Ferroudji; Muhammad Saad Khan; Abinash Barooah; Wahib A. Al-Ammari; Ibrahim Hassan; Rashid Hassan; Ahmad K. Sleiti; Sina Rezaei Gomari; Matthew Hamilton; Mohammad Azizur Rahman (Process Safety and Environmental Protection, 2025)

Linking provenance and diagenesis to reservoir quality evolution of sandstones: The Paleocene-Eocene Kerri-Kerri Formation, northeastern Nigeria - Abdulwahab M. Bello; Musa B. Usman; Abduljamiu O. Amao; Anas M. Salisu; Khalid Al-Ramadan; Usman Abubakar; Shehu Mukkafa; Ibrahim A. Kwami; Lukman U. Chiroma; Murtada Al-Hashem; Abubakar Yusuf; Abubakar S. Maigari; et al. (Marine and Petroleum Geology, 2025)

3LATNet: Attention based deep learning model for global Chlorophyll-a retrieval from GCOM-C satellite - Muhammad Salah; Salem Ibrahim Salem; Nobuyuki Utsumi; Hiroto Higa; Joji Ishizaka; Kazuo Oki (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Mathematical analysis of chickenpox population dynamics unveiling the impact of booster in enhancing recovery of infected individuals - Kabiru Garba Ibrahim; James Andrawus; Abbas Abubakar; Abdullahi Yusuf; Stephen Ishaya Maiwa; Kefas Bitrus; Muhammad Sani; Ibrahim Abdullahi; Sunday Babuba; Joseph Jonathan (Modeling Earth Systems and Environment, 2025)

Computer-aided rational design of a mRNA vaccine against Guanarito mammarenavirus - Mohibullah Shah; Asifa Sarfraz; Muhammad Shehroz; Asia Perveen; Samavia Jaan; Aqal Zaman; Umar Nishan; Arlindo A. Moura; Riaz Ullah; Zafar Iqbal; Mohamed A. Ibrahim (Biotechnology Letters, 2025)

Navigating Climate Change: Exploring the Dynamics Between Plant–Soil Microbiomes and Their Impact on Plant Growth and Productivity - Murad Muhammad; Abdul Wahab; Abdul Waheed; Khalid Rehman Hakeem; Heba Ibrahim Mohamed; Abdul Basit; Muhammad Danish Toor; Yong‐Hong Liu; Li Li; Wen‐Jun Li (Global Change Biology, 2025)
Understanding the intricate interplay between plant and soil microbiomes and their effects on plant growth and productivity is vital in a rapidly changing climate. This review explores the interconnected impacts of climate change on plant–soil microbiomes and their profound effects on agricultural productivity. The ongoing rise in global temperatures, shifting precipitation patterns and extreme weather events significantly affect the composition and function of microbial communities in the rhizosphere. Changes in microbial diversity and activity due to rising temperatures impact nutrient cycling, microbial enzyme synthesis, soil health and pest and disease management. These changes also influence the dynamics of soil microbe communities and their capability to promote plant health. As the climate changes, plants' adaptive capacity and microbial partners become increasingly crucial for sustaining agriculture. Mitigating the adverse effects of climate change on plant growth and agricultural productivity requires a comprehensive understanding of the interconnected mechanisms driving these processes. It highlights various strategies for mitigating and adapting to environmental challenges, including soil management, stress‐tolerant crops, cover cropping, sustainable land and water management, crop rotation, organic amendments and the development of climate‐resilient crop varieties. It emphasises the need for further exploration of plant–soil microbiomes within the broader context of climate change. Promising mitigation strategies, including precision agriculture and targeted microbiome modifications, offer valuable pathways for future research and practical implementation of global food security and climate change.

Prediction of CO2 uptake in bio-waste based porous carbons using model agnostic explainable artificial intelligence - Mohd Azfar Shaida; Saad Shamim Ansari; Raeesh Muhammad; Syed Muhammad Ibrahim; Izharul Haq Farooqi; Abdulkarem Amhamed (Fuel, 2025)

Investigating the impact of enzyme diversity in producing edible bird nest protein hydrolysates: Techno-functional, structural, molecular docking, and in vitro digestibility - Rabia Kanwal; Abdur Rehman; Muhammad Irfan; Mian Shamas Murtaza; Tabussam Tufail; Mian Anjum Murtaza; Tawfiq Alsulami; Ibrahim Khalifa; Song Miao (Food Structure, 2025)

Co-encapsulation of borage seed oil and peppermint oil blends within ultrasound-assisted soy protein isolate/purity gum ultra complex nanoparticles: Fabrication, structural interaction mechanisms, and in vitro digestion studies - Abdur Rehman; Ibrahim Khalifa; Hafiz Abdul Rasheed; Muhammad Waheed Iqbal; Muhammad Shoaib; Junxia Wang; Yongjun Zhao; Qiufang Liang; Mingming Zhong; Yufan Sun; Tawfiq Alsulami; Xiaofeng Ren; et al. (Food Chemistry, 2025)

Progressive Approaches in Ni(II) Contaminated Water Treatment: A Review of Adsorbent Strategies - Adnan Ahmed; Aidi Huo; Muhammad Ibrahim (Water, Air, & Soil Pollution, 2025)

Environmental Conditions Modulate Warming Effects on Plant Litter Decomposition Globally - Sarah Schwieger; Ellen Dorrepaal; Matteo Petit Bon; Vigdis Vandvik; Elizabeth le Roux; Maria Strack; Yan Yang; Susanna Venn; Johan van den Hoogen; Fernando Valiño; Haydn J. D. Thomas; Mariska te Beest; et al. (Ecology Letters, 2025)
Empirical studies worldwide show that warming has variable effects on plant litter decomposition, leaving the overall impact of climate change on decomposition uncertain. We conducted a meta‐analysis of 109 experimental warming studies across seven continents, using natural and standardised plant material, to assess the overarching effect of warming on litter decomposition and identify potential moderating factors. We determined that at least 5.2° of warming is required for a significant increase in decomposition. Overall, warming did not have a significant effect on decomposition at a global scale. However, we found that warming reduced decomposition in warmer, low‐moisture areas, while it slightly increased decomposition in colder regions, although this increase was not significant. This is particularly relevant given the past decade's global warming trend at higher latitudes where a large proportion of terrestrial carbon is stored. Future changes in vegetation towards plants with lower litter quality, which we show were likely to be more sensitive to warming, could increase carbon release and reduce the amount of organic matter building up in the soil. Our findings highlight how the interplay between warming, environmental conditions, and litter characteristics improves predictions of warming's impact on ecosystem processes, emphasising the importance of considering context‐specific factors.

Fluorescence Analysis of Antibacterial Activity of ZnO/TiO2 Electrospun Nanofibers: A Molecular Approach to Reveals the Insights of Physiochemical Interactions of Materials with Bacteria - Ali Hassan; Shahzad Anwar; Rashad Rashid; Rafaqat Ali Khan; Saba Ibrahim; Bisma Khanam; Attaullah Shah; Muhammad Raffi (Journal of Fluorescence, 2024)

The role of selenium and biochar nanoparticles in alleviating cadmium stress in wheat (Triticum aestivum L.) examined via morphophysiological traits and organic acid exudation patterns - Mohammad K. Okla; Sahar Mumtaz; Sadia Javed; Muhammad Hamzah Saleem; Ibrahim A. Saleh; Naser Zomot; Yasmeen A. Alwasel; Mostafa A. Abdel-Maksoud; Muhammad Adnan; Shafaqat Ali (South African Journal of Botany, 2024)

Individual and combinatorial application of nanosilica and carbon nanoparticles alleviate nickel stress in barley (Hordeum vulgare L.): Impacts on gene expression, AsA − GSH cycle, cellular fractionation, and proline metabolism - Zhanbin Luo; Manar Fawzi Bani Mfarrej; Muhammad Hamzah Saleem; Jing Ma; Ibrahim A. Saleh; Mostafa A. Abdel-Maksoud; Adel M. Zakri; Fu Chen; Leobardo Manuel Gómez Oliván (Science of The Total Environment, 2024)

A new system using refuse-derived fuel as a feedstock for hydrogen and power co-generation: A techno-environmental assessment - Muhammad Ishaq; Ibrahim Dincer (Process Safety and Environmental Protection, 2024)

Highly competent elimination of diverse toxic heavy metal oxo-anions by novel 2D guanidinium-based ionic covalent organic framework - Jerosha Ifthikar; Eman A. Gendy; Imran Mahmood Khan; Ibrahim Khan; Muhammad Sajjad (Next Research, 2024)

Machine learning integration with response surface methodology to enhance the removal efficacy of arsenate (V) through sulfur-functionalized mxene coated QPPO/PVA AEM - Nimra Saher Zain; Ibrahim A. Shaaban; Farhan Zafar; Hafiz Muhammad Asif; Muhammad Tariq; Muhammad Ali Khan; Naeem Akhtar; Hafsa Kainat; Mohammad A. Assiri (Journal of Environmental Management, 2024)

Characterization and identification of the key volatile and non-volatile substances of Vangueria madagascariensis J.F. Gmel fruits (Kirkir) and exploration of their binding interactions with olfactory and taste receptors using computational chemistry methodology - Haroon Elrasheid Tahir; Sulafa B.H. Hashim; Muhammad Arslan; Gustav Komla Mahunu; Mohammad Rezaul Islam Shishir; Li Zhihua; Suliman Khan; Abdalbasit Adam Mariod; Hamza A.M. Abaker; Howida Elkheir Ibrahim; Hesham R. El-Seedi; Zou Xiaobo (Food Chemistry, 2024)

Machine learning trained poly (3,4-ethylenedioxythiophene) functionalized carbon matrix suspended Cu nanoparticles for precise monitoring of nitrite from pickled vegetables - Waseem Abbas; Farhan Zafar; Manal F. Abou Taleb; Mavra Ameen; Abdul Sami; Muhammad Ehsan Mazhar; Naeem Akhtar; Muhammad Waseem Fazal; Mohamed M. Ibrahim; Zeinhom M. El-Bahy (Food Chemistry, 2024)

Fabrication and characterization of bioactive curdlan and sodium alginate films for enhancing the shelf life of Volvariella volvacea - Asif Ali Khan; Feng-Jie Cui; Muhammad Wajid Ullah; Abdul Qayum; Ibrahim Khalifa; Syed Asim Shah Bacha; Zheng-Zi Ying; Ismail Khan; Umar Zeb; Abdullah A. Alarfaj; Mohammad Javed Ansari; Yan Yang; et al. (Food Bioscience, 2024)

Structure-property relationship of ultrasound-assisted nanoemulsion-impregnated bioactive polysaccharide films for enhanced shelf life of mushrooms - Asif Ali Khan; Muhammad Wajid Ullah; Abdul Qayum; Ibrahim Khalifa; Mazhar Ul-Islam; Syed Asim Shah Bacha; Umar Zeb; Fang-Jie Yao; Sulaiman Ali Alharbi; Mansour Shrahili; Yan Yang; Wei Jia; et al. (Food Packaging and Shelf Life, 2024)

Energy use behavior research: A scientometric evaluation and critical synthesis - Bushra Jan; Muhammad Asif; Ibrahim Yahaya Wuni (Energy and Buildings, 2024)

An advanced design to generate power and hydrogen with CO2 capturing and storage for cleaner applications - Muhammad Ishaq; Ibrahim Dincer (Chemical Engineering Journal, 2024)

Empagliflozin-activated AMPK elicits neuroprotective properties in reserpine-induced depression via regulating dynamics of hippocampal autophagy/inflammation and PKCζ-mediated neurogenesis - Radwa N. Muhammad; Mohammed A. Albahairy; Mai A. Abd El Fattah; Weam W. Ibrahim (Psychopharmacology, 2024)
Rationale Major depression has been an area of extensive research during the last decades, for it represents a leading cause of disability and suicide. The stark rise of depression rates influenced by life stressors, economic threats, pandemic era, and resistance to classical treatments, has made the disorder rather challenging. Adult hippocampal neurogenesis and plasticity are particularly sensitive to the dynamic interplay between autophagy and inflammation. In fact, the intricate balance between the two processes contributes to neuronal homeostasis and survival. Objectives Having demonstrated promising potentials in AMPK activation, a major metabolic sensor and autophagy regulator, empagliflozin (Empa) was investigated for possible antidepressant properties in the reserpine rat model of depression. Results While the reserpine protocol elicited behavioral, biochemical, and histopathological changes relevant to depression, Empa outstandingly hindered these pathological perturbations. Importantly, hippocampal autophagic response markedly declined with reserpine which disrupted the AMPK/mTOR/Beclin1/LC3B machinery and, conversely, neuro-inflammation prevailed under the influence of the NLRP3 inflammasome together with oxidative/nitrative stress. Consequently, AMPK-mediated neurotrophins secretion obviously deteriorated through PKCζ/NF-κB/BDNF/CREB signal restriction. Empa restored hippocampal monoamines and autophagy/inflammation balance, driven by AMPK activation. By promoting the atypical PKCζ phosphorylation (Thr403) which subsequently phosphorylates NF-κB at Ser311, AMPK successfully reinforced BDNF/CREB signal and hippocampal neuroplasticity. The latter finding was supported by hippocampal CA3 toluidine blue staining to reveal intact neurons. Conclusion The current study highlights an interesting role for Empa as a regulator of autophagic and inflammatory responses in the pathology of depression. The study also pinpoints an unusual contribution for NF-κB in neurotrophins secretion via AMPK/PKCζ/NF-κB/BDNF/CREB signal transduction. Accordingly, Empa can have special benefits in diabetic patients with depressive symptoms. Limitations The influence of p -NF-κB (Ser311) on NLRP3 inflammasome assembly and activation has not been investigated, which can represent an interesting point for further research. Graphical abstract

Pangenome analysis of five representative Tropheryma whipplei strains following multiepitope-based vaccine design via immunoinformatic approaches - Ahmad Hasan; Muhammad Ibrahim; Wadi B. Alonazi; Rongrong Yu; Bin Li (Molecular Genetics and Genomics, 2024)

Identification and mechanism determination of the efflux pump subunit amrB gene mutations linked to gentamicin susceptibility in clinical Burkholderia pseudomallei from Malaysian Borneo - Ainulkhir Hussin; Sheila Nathan; Muhammad Ashraf Shahidan; Mohd Yusof Nor Rahim; Mohamad Yusof Zainun; Nurul Aiman Nafisah Khairuddin; Nazlina Ibrahim (Molecular Genetics and Genomics, 2024)

MicroRNA expression profiling of ovine epithelial cells stimulated with the Staphylococcus aureus in vitro - Ghulam Asghar Sajid; Muhammad Jasim Uddin; Saif Adil Abbood Al-Janabi; Abdiaziz Nur Ibrahim; Mehmet Ulas Cinar (Mammalian Genome, 2024)

Virtual screening and molecular dynamics studies of novel small molecules targeting Schistosoma mansoni DHODH: identification of potential inhibitors - Saudatu Chinade Ja’afaru; Adamu Uzairu; Vipin Kumar Mishra; Muhammed Sani Sallau; Muhammad Tukur Ibrahim; Amit Dubey (In Silico Pharmacology, 2024)

Diagenesis and reservoir quality evolution of estuarine sandstones: Insights from the Cenomanian-Turonian Yolde Formation, northern Benue Trough, NE Nigeria - Abdulwahab M. Bello; Musa B. Usman; Abduljamiu O. Amao; Khalid Al-Ramadan; Murtada Al-Hashem; Aliyuda Kachalla; Usman Abubakar; Anas M. Salisu; Shehu Mukkafa; Ibrahim A. Kwami; Oluwafemi E. Aro; Muhammad Naveed Butt; et al. (Marine and Petroleum Geology, 2024)

A cradle-to-gate life cycle assessment for clean hydrogen gas production pathway using the CeO2/Ce2O3-based redox thermochemical cycle - Muhammad Ishaq; Ibrahim Dincer (Gas Science and Engineering, 2024)

Effects of substitution of crude palm oil with palm-pressed fibre oil on the laying hen’s performance, egg production and egg quality traits - Mookiah Saminathan; Muhammad Amirul Fuat; Wan Nooraida Wan Mohamed; ‘Abidah Md Noh; Nur Atikah Ibrahim (Tropical Animal Health and Production, 2024)

Electrospun bio-polymeric nanofibrous membrane for membrane distillation desalination application - Muhammad Omer Aijaz; Mohd Hafiz Dzarfan Othman; Mohammad Rezaul Karim; Asmat Ullah Khan; Abdullah Najib; Abdulaziz K. Assaifan; Hamad F. Alharbi; Ibrahim Abdullah Alnaser; Mohd Hafiz Puteh (Desalination, 2024)

Machine learning modeling and statistical optimization of dye removal from contaminated water using CTAB-functionalized graphene oxide - Sally AlNaimat; Usman M. Ismail; Ahmed I. Ibrahim; Abdimalik Muse; Kashif Faheem; Mohamed Mustafa; Muhammad S. Vohra; Sagheer A. Onaizi (Water, Air, & Soil Pollution, 2024)

Eco-toxicological impacts of industrial wastewater and the role of bio-electrochemical systems (BES) in remediation: a review - Muhammad Usman; Zhenhua Zhao; Olive Mekontchou Yemele; Muhammad Ibrahim; Waleed Raza; Zia Ur Rehman; Abduelrahman Adam Omer; Mir Moazzam Ali Talpur; Mouna Jeridi; Ghulam Abbas Ashraf; Hafsat Alhassan Danjaji (Clean Technologies and Environmental Policy, 2024)

Exogenous application of glutathione induces wheat tolerance to heavy metal stress by modulating the antioxidative enzymatic defenses - Khalid Iqbal; Muhammad Ibrahim; Anam Khattak; Sarah Ali Khan; Ghazala Nawaz (Acta Physiologiae Plantarum, 2024)

Retraction Note: Inquiring asymmetric effects of oil prices, money supply, and domestic debt on consumer prices: an empirical evidence from Pakistan - Muhammad Shahid Hassan; Najam ul Hassan; Rukhsana Kalim; Muhammad Ibrahim Saeed; Haider Mahmood (Environmental Science and Pollution Research, 2024)

Efficacy of Fe-Mg-bimetallic biochar in stabilization of multiple heavy metals-contaminated soil and attenuation of toxicity in spinach (Spinacia oleracea L.) - Muhammad Kashif Irshad; Jong Cheol Lee; Muhammad Aqeel; Wasim Javed; Ali Noman; Su Shiung Lam; Ali El Naggar; Nabeel Khan Niazi; Hun Ho Lee; Muhammad Ibrahim; Sang Soo Lee (Chemosphere, 2024)

Novel zirconium phosphate/MXene/ionic liquid membranes for PEM fuel cells operating up to 145°C - Amani Al-Othman; Muhammad Tawalbeh; Ahmad Ka’aki; Ibrahim Shomope; Muhammad Faheem Hassan (Process Safety and Environmental Protection, 2024)

Harnessing bacterial endophytes for environmental resilience and agricultural sustainability - Murad Muhammad; Abdul Wahab; Abdul Waheed; Heba Ibrahim Mohamed; Khalid Rehman Hakeem; Li Li; Wen-Jun Li (Journal of Environmental Management, 2024)

Punching shear strength of fiber-reinforced polymer concrete slabs: Database-driven assessment of parameters and prediction models - Aroob Alateyat; Raghad Awad; Basil Ibrahim; Muhammad-Talha Junaid; Salah Altoubat; Mohamed Maalej; Samer Barakat (Engineering Structures, 2024)

Biofortification of Iron in Potato Through Rhizobacteria and Plant Growth Regulator - Zain Mushtaq; Ibrahim Al-Ashkar; Muhammad Habib-ur-Rahman; Ayman El Sabagh; Predrag Ilić (Potato Research, 2024)

Analyses of oxidative DNA damage among coal vendors via single cell gel electrophoresis and quantification of 8-hydroxy-2’-deoxyguanosine - Ali Sani; Ibrahim Lawal Abdullahi; Muhammad Idrees Khan; ChengXi Cao (Molecular and Cellular Biochemistry, 2024)

First report of Pythium aphanidermatum causing coriander damping-off in district Hyderabad, Sindh, Pakistan - Ghulam Sarwar Shah; Jamal-U-Ddin Hajano; Rehana Naz Syed; Muhammad Ibrahim Khaskheli; Manzoor Ali Abro; Muhammad Ali Khanzada; Abdul Mubeen Lodhi (Journal of Plant Pathology, 2024)

Artificial neural network modeling for the prediction, estimation, and treatment of diverse wastewaters: A comprehensive review and future perspective - Muhammad Ibrahim; Adnan Haider; Jun Wei Lim; Bandita Mainali; Muhammad Aslam; Mathava Kumar; Muhammad Kashif Shahid (Chemosphere, 2024)

Neurotoxic snakebites in Africa: Clinical implications, therapeutic strategies, and antivenom efficacy - Abdulbaki Alfa-Ibrahim Adio; Ibrahim Malami; Nafiu Lawal; Amina Yusuf Jega; Bilyaminu Abubakar; Muhammad Bashir Bello; Kasimu Ghandi Ibrahim; Murtala Bello Abubakar; Abdussamad Abdussamad; Mustapha Umar Imam (Toxicon, 2024)

A novel integrated gas-cooled fast nuclear reactor and vanadium chloride thermochemical cycle for sustainable fuel production - Muhammad Ishaq; Ibrahim Dincer (Journal of Cleaner Production, 2024)

Analyzing Agricultural Land Use with Cellular Automata-MARCOV and Forecasting Future Marine Water Quality Index: A Case Study in East Coast Peninsular Malaysia - Mohd Saiful Samsudin; Azman Azid; Muhammad Amar Zaudi; Mohd Ridhwan Adam; Muhamad Shirwan Abdullah Sani; Shazlyn Millenana Saharuddin; Aminu Ibrahim; Mohd Fahmi Mohd Nasir; Mou Leong Tan; Nurul Izzati Mohd Ali (Water, Air, & Soil Pollution, 2024)

Life cycle assessment model for small-scale coal mining operations with equivalent coal output: a greener perspective towards coal mining - Muhammad Burhan Memon; Ming Tao; Zheng Yang; Tufail Ahmed; Muhammad Ibrahim (Environment, Development and Sustainability, 2024)

A Comprehensive on Synthesis and Antimicrobial Evaluation of Substituted-Arylideneamino-5-(5-Chlorobenzofuran-2-yl)-1, 2, 4-Triazole-3-Thiol Derivatives/ Schiff Bases - Muhammad Rizwan; Sobia Noreen; Sadia Asim; Zohaib Liaqat; Hina Ibrahim; Rimsha Talib (Journal of Fluorescence, 2024)

Updated review on current approaches and challenges for poly- and perfluoroalkyl substances removal using activated carbon-based adsorbents - Farahin Mohd Jais; Muhammad Shazril Idris Ibrahim; Ahmed El-Shafie; Choe Earn Choong; Minhee Kim; Yeomin Yoon; Min Jang (Journal of Water Process Engineering, 2024)

HPTLC quantification of quercetin from leaf extracts of C. occidentalis L. and its inhibitory activity against protease enzyme of P. falciparum - Ibrahim Isyaku Muhammad; Devendra Kumar Pandey (Vegetos, 2024)

Early detection of deep-seated smouldering fires in wood waste storage using ERT - Muhammad Asim Ibrahim; Nabeel Afzal Butt; Simon Rejkjær; Torleif Dahlin; Dan Madsen; Konard Wilkens Flecknoe-Brown; Thomas Günther (Waste Management, 2024)

Bio-formulated chitosan nanoparticles enhance disease resistance against rice blast by physiomorphic, transcriptional, and microbiome modulation of rice (Oryza sativa L.) - Rahila Hafeez; Junning Guo; Temoor Ahmed; Hubiao Jiang; Mubashar Raza; Muhammad Shahid; Ezzeldin Ibrahim; Yanli Wang; Jiaoyu Wang; Chengqi Yan; Qianli An; Jason C. White; et al. (Carbohydrate Polymers, 2024)

Salmonella serovars trend in poultry Malaysia from 2011 to 2020 - Muhammad Marwan Ibrahim; Mohammad Bohari Jusoh; Farid Zamani Che Rose; Mohammad Masrin Azami; Roseliza Roslee (Veterinary Research Communications, 2024)

In-silico functional and molecular phenotypic analysis of NFKBIE (V194A), and PADI4 (G55S, V82A,G112A) gene mutations in rheumatoid arthritis - Fazal Shan; Irshad Ahmad; Muhammad Ibrahim Rashid (Journal of Proteins and Proteomics, 2024)

The fate of flaxseed-lignans after oral administration: A comprehensive review on its bioavailability, pharmacokinetics, and food design strategies for optimal application - Abdul Mueed; Muhammad Ibrahim; Sahar Shibli; Philippe Madjirebaye; Zeyuan Deng; Muhammad Jahangir (Critical Reviews in Food Science and Nutrition, 2024)

Methane emissions in cattle production: biology, measurement and mitigation strategies in smallholder farmer systems - Akeem Sikiru; Akinsola Oludayo Michael; Makinde Olayinka John; Stephen Sunday Acheneje Egena; Vivian U. Oleforuh-Okoleh; Munirat Isiaka Ambali; Ibrahim R. Muhammad (Environment, Development and Sustainability, 2024)

Integrative transcriptomic and metabolomic analyses reveals the toxicity and mechanistic insights of bioformulated chitosan nanoparticles against Magnaporthe oryzae - Rahila Hafeez; Junning Guo; Temoor Ahmed; Ezzeldin Ibrahim; Md. Arshad Ali; Muhammad Rizwan; Munazza Ijaz; Qianli An; Yanli Wang; Jiaoyu Wang; Bin Li (Chemosphere, 2024)

Optimal environment control and fruits delivery tracking system using blockchain for greenhouse - Atif Rizwan; Anam Nawaz Khan; Muhammad Ibrahim; Rashid Ahmad; Naeem Iqbal; Do Hyeun Kim (Computers and Electronics in Agriculture, 2024)

Investigation of a tri-renewable energy system coupled with battery and hydrogen storages for a sustainable city - Muhammad Ishaq; Ibrahim Dincer (Sustainable Cities and Society, 2024)

Dynamic linkages between financial development, economic growth, urbanization, trade openness, and ecological footprint: an empirical account of ECOWAS countries - Nazir Muhammad Abdullahi; Adamu Ali Ibrahim; Qiangqiang Zhang; Xuexi Huo (Environment, Development and Sustainability, 2024)

Visible light-activated curcumin-doped zinc oxide nanoparticles integrated into orthodontic adhesive on Micro-tensile bond strength, degree of conversion, and antibacterial effectiveness against Staphylococcus Aureus. An investigation using scanning electron microscopy and energy-dispersive X-ray spectroscopy - Abdullah A. Alnazeh; Muhammad Abdullah Kamran; Salem Almoammar; Mohammed Mohsen Al Jearah; Muhammad Qasim; Ibrahim Alshahrani (Journal of Photochemistry and Photobiology B: Biology, 2024)

Preharvest Application of Hydrogen Sulfide and Nitric Oxide Improves Floral Traits and Postharvest Performance of Cut Gladiolus Inflorescences - Faisal Zulfiqar; Anam Moosa; Anastasios Darras; Muhammad Nafees; Muhammad Ashraf; Ibrahim Al-Ashkar; Ayman El Sabagh; John T. Hancock (Journal of Plant Growth Regulation, 2024)

Hydrochemical, hydrogeological, and cancer health risk analysis of groundwater due to anthropogenic activities, Hasilpur, Pakistan - Muhammad Irfan Jalees; Muhammad Atiq; Muhammad Umar Farooq; Ghulam Hussain; Mehwish Anis; Qurat Ul Ain; Maira Kaleem; Ahmad Ibrahim (Environmental Monitoring and Assessment, 2024)

Identification of potential inhibitors of shikimate kinase from Mycobacterium tuberculosis using in silico approach - Mustafa Alhaji Isa; Mohammed Mustapha Mohammed; Muhammad Musa Ibrahim; Falmata Audu Gubio; Fatimah Buba; Somia Shehzadi (Journal of Proteins and Proteomics, 2024)

Enhancing the proficiency of heat pump-driven humidification‐dehumidification desalination systems using eco-environmentally friendly organic mixtures - Tao Hai; Bhupendra Singh Chauhan; Muammer Aksoy; Ibrahim Mahariq; Wael Al-Kouz; Taseer Muhammad; Hedi ELmonser; Huynh Nhang (Process Safety and Environmental Protection, 2024)

Thermal stratification and mixing processes response to meteorological factors in a monomictic reservoir - Yaning Wang; Yiping Li; Yue Cheng; Yu Wang; Ya Zhu; Ronghui Li; Kumud Acharya; Muhammad Ibrahim (Journal of Environmental Management, 2024)

Does financial sector is helpful for curbing carbon emissions through the investment in green energy projects: evidence from MMQR approach - Muhammad Farhan Basheer; Ahsan Anwar; Saria Ghulam Hassan; Ibrahim Tawfeeq Alsedrah; Phan The Cong (Clean Technologies and Environmental Policy, 2024)

Dynamic impact of demographic features, FDI, and technological innovations on ecological footprint: evidence from European emerging economies - Florian Nuta; Muhammad Shahbaz; Itbar Khan; Ibrahim Cutcu; Hayat Khan; Mehmet Vahit Eren (Environmental Science and Pollution Research, 2024)

Green absorptive capacity and environmental performance: a perspective of SMEs’ relational capability and green supply chain management practices - Muhammad Ibrahim; Rosli Mahmood; Hishamuddin Md Som (Environment, Development and Sustainability, 2024)

Correction to: Alleviation of cadmium toxicity in pea (Pisum sativum L.) through Zn−Lys supplementation and its effects on growth and antioxidant defense - Muhammad Hamzah Saleem; Abida Parveen; Shagufta Perveen; Naheed Akhtar; Fozia Abasi; Maria Ehsan; Habib Ali; Mohammad K. Okla; Ibrahim A. Saleh; Naser Zomot; Yasmeen A. Alwasel; Mostafa A. Abdel-Maksoud; et al. (Environmental Science and Pollution Research, 2024)

Wound healing, antioxidant and antibacterial activities of polyphenols of Psidium guajava L. leaves - Kainat Bilal; Fatima Mehboob; Nosheen Akhtar; Irfan Ali Mirza; Muhammad K. Okla; M. Junaid Dar; Ibrahim A. Saleh; Naser Zomot; Humaira Fatima (South African Journal of Botany, 2024)

Waste cellulose acetate-based dynamic membrane for NOM-containing river water filtration - Ibrahim Maina Idriss; Nurul Fadillah; Norazanita Shamsuddin; Muhammad Saifullah Abu Bakar; Sutarat Thongratkaew; Kajornsak Faungnawakij; Wahyunanto Agung Nugroho; Yusuf Wibisono; Asep Bayu Dani Nandiyanto; Muhammad Roil Bilad (Journal of Environmental Chemical Engineering, 2024)

Marine Streptomyces sp. PGC 39: A treasure trove of new antimicrobial agents, macrolidycin, and pyrachlomycin - Rabbia Ahmad; Muhammad Imran Tousif; Mamona Nazir; Asma Yaqoob; Syed Adnan Ali Shah; Gokhan Zengin; Abdullahi Ibrahim Uba; Shabbir Muhammad (Food Bioscience, 2024)

COVID-19 associated mucormycosis (CAM) in Kashan, Iran: clinical presentations, risk factors, management, and outcomes - Mahzad Erami; Omid Raiesi; Mansooreh Momen-Heravi; Hossein Mirhendi; Shima Aboutalebian; Muhammad Ibrahim Getso; Amir Hassan Matini; Amir Hossein Ahsaniarani; Mohsen Ganjizadeh; Hajar Hassani Josheghani; Sasan Amiri; Reza Pakzad; et al. (Infectious Diseases, 2024)

A comparison of experimental and computational methods for circular footing response on lime-treated geotextile reinforced silty sand - Syed Md Yousuf; Mehboob Anwar Khan; Syed Muhammad Ibrahim; Anil Kumar Sharma; Furquan Ahmad; Pramod Kumar (Modeling Earth Systems and Environment, 2024)

Response to carvacrol monoterpene in the emergence of Allium cepa L. seeds exposed to salt stress - Larisse Bernardino dos Santos; Jailson Renato de Lima Silva; Amanda Maria Tavares Moreira; Jean Paul Kamdem; Momin Khan; Niaz Muhammad; Abdullah F. AlAsmari; Fawaz Alasmari; Antonia Eliene Duarte; Mohammad Ibrahim (Environmental Science and Pollution Research, 2024)

Alleviation of cadmium toxicity in pea (Pisum sativum L.) through Zn−Lys supplementation and its effects on growth and antioxidant defense - Muhammad Hamzah Saleem; Abida Parveen; Shagufta Perveen; Naheed Akhtar; Fozia Abasi; Maria Ehsan; Habib Ali; Mohammad K. Okla; Ibrahim A. Saleh; Naser Zomot; Yasmeen A. Alwasel; Mostafa A. Abdel-Maksoud; et al. (Environmental Science and Pollution Research, 2024)

Unpacking the impact of financialization and globalization on environmental degradation in BRICS economies - Yanjie Gao; Hang Chen; Muhammad Zubair Tauni; Ibrahim Alnafrah; Jiaqi Yu (Resources Policy, 2024)

Protein extracted from Moringa oleifera Lam. Leaves: Bio-evaluation and characterization as suitable plant-based meat-protein alternative - Muhammad Sameem Javed; Smara Qaiser Alvi; Adnan Amjad; Hasan Sardar; Muhammad Junaid Anwar; Asma Javid; Sami Abou Fayssal; Pankaj Kumar; Tracy Abou Fayssal; Saikh M. Wabaidur; Mohammad K. Okla; Ibrahim A. Saleh; et al. (Regulatory Toxicology and Pharmacology, 2024)

Serological detection of important pepper viruses and characterisation of pepper mild mottle virus in Saudi Arabia - Zaheer Khalid; Mahmoud Ahmed Amer; Muhammad Amir; Khadim Hussain; Ibrahim Al-Shahwan; Mohammed Ali Al-Saleh (Australasian Plant Pathology, 2024)

A meta‐analysis of aquaculture technical efficiency studies - Narimah Samat; Kim Huat Goh; Kok Fong See; Rabiatul Adawiyah Ibrahim; Ngai Weng Chan; Mou Leong Tan; Lai Kuan Lee; Ta Wee Seow; Muhammad Azizan Sabjan (Reviews in Aquaculture, 2024)
As the world population grows, the aquaculture sector faces challenges in the use of production systems to ensure the adequacy of the food supply. Technical efficiency analysis has been shown to be useful for improving resource management and production. This study provides a literature update and uses meta‐regression analysis to examine the variations in aquaculture mean technical efficiency (MTE) scores based on 101 studies published from 1998 to 2023. The findings show that studies with larger model dimensions, different output measures, an input‐oriented model specification and that analyse the exogenous variables of efficiency scores, freshwater aquaculture, and European data produce a narrower variance in MTE scores. In contrast, studies that use panel data and nonparametric data envelopment analysis (DEA) generate wider variance in MTE scores. As a result of these investigations, the findings suggest the importance of selecting appropriate variables and sample sizes for efficiency estimates. Robustness checks of efficiency scores from the DEA and stochastic frontier analysis (SFA) approaches are recommended for future studies. Different policies and regulations should be implemented in different countries and across different farming systems.

Kinetics and thermodynamic analysis of palm oil decanter cake and alum sludge combustion for bioenergy production - Kunmi Joshua Abioye; Noorfidza Yub Harun; Suriati Sufian; Mohammad Yusuf; Muhammad Irfan Khan; Ahmad Hussaini Jagaba; Surajudeen Sikiru; Sharjeel Waqas; Hesam Kamyab; Abdullah M. Al-Enizi; Satbir S. Sehgal; Manish Gupta; et al. (Sustainable Chemistry and Pharmacy, 2023)

Hepatic β-arrestins: potential roles in liver health and disease - Alzahraa Muhammad Eissa; Mohamed H. Hassanin; Islam A. A. E. H. Ibrahim (Molecular Biology Reports, 2023)
Β-arrestins are intracellular scaffolding proteins that have multifaceted roles in different types of disorders. In this review article, we gave a summary about the discovery, characterization and classification of these proteins and their intracellular functions. Moreover, this review article focused on the hepatic expression of β-arrestins and their hepatocellular distribution and function in each liver cell type. Also, we showed that β-arrestins are key regulators of distinct types of hepatic disorders. On the other hand, we addressed some important points that have never been studied before regarding the role of β-arrestins in certain types of hepatic disorders which needs more research efforts to cover.

Exogenous Application of Silicon and Sulfate Improved Drought Tolerance in Sunflowers Through Modulation of Morpho-physiological and Antioxidant Defense Mechanisms - Muhammad Nisar; Muhammad Aqeel; Abdul Sattar; Ahmad Sher; Muhammad Ijaz; Sami Ul-Allah; Umair Rasheed; Salem Mesfir Al-Qahtani; Nadi Awad Al-Harbi; Fahad Mohammed Alzuaibr; Mohamed F. M. Ibrahim (Journal of Soil Science and Plant Nutrition, 2023)

Analysis of land use and land cover change using machine learning algorithm in Yola North Local Government Area of Adamawa State, Nigeria - Auwal Aliyu; Muhammad Isma’il; Sule Muhammad Zubairu; Ibrahim Yahaya Gwio-kura; Abubakar Abdullahi; Babakaka Abdulsalam Abubakar; Muntaka Mansur (Environmental Monitoring and Assessment, 2023)

Exploring soil radon (Rn) concentrations and their connection to geological and meteorological factors - Ahmad Muhammad; Salim Jibrin Danbatta; Ibrahim Yahaya Muhammad; Ibrahim Isah Nasidi (Environmental Science and Pollution Research, 2023)

Characterization for optimizing the integrated management of solid waste for energy recovery and circular economy - Fariha Jabeen; Muhammad Adrees; Muhammad Ibrahim; Muhammad Waqas; Abid Mahmood; Uzma Noreen; Afifa Aslam (Environmental Science and Pollution Research, 2023)

National strategy for climate change adaptability: a case study of extreme climate-vulnerable countries - Noman Arshed; Muhammad Ibrahim Saeed; Sultan Salem; Uzma Hanif; Manzir Abbas (Environment, Development and Sustainability, 2023)

DNA base analysis: An effective tool to resolve taxonomic uncertainty and establish phylogenetic relationship in cryptic genotypes of Pyrus (pear), Rosaceae - Muhammad Saeed Akhtar; Shahid Ullah Khan; Ebraheem Abdu Musad Saleh; Said Muhammad; Mohammad Islam; Umber Zaman; Khalil ur Rehman; Gul Nawab; Muhammad Naveed Akhtar; Nabil A. Alhakamy; M.K. Rasha Ibrahim; Ehab A. Abdelrahman (South African Journal of Botany, 2023)

Renewable hydrogen production via biological and thermochemical routes: Nanomaterials, economic analysis and challenges - Fazil Qureshi; Mohammad Yusuf; Muhammad Tahir; Moinul Haq; Montaha Mohamed Ibrahim Mohamed; Hesam Kamyab; Hong-Ha T. Nguyen; Dai-Viet N. Vo; Hussameldin Ibrahim (Process Safety and Environmental Protection, 2023)

The impact of CO2 saturated brine temperature on wormhole generation and rock geomechanical and petrophysical properties - Abdullah Al-Dhafeeri; Murtada Saleh Aljawad; Mustafa Al Ramadan; Ahmed Farid Ibrahim; Muhammad M. Al Majid; Zuhair Al-Yousef; Ahmed Al-Yaseri (Gas Science and Engineering, 2023)

Thermochemical conversion of agricultural waste to hydrogen, methane, and biofuels: A review - Ahmed Khan; Muhammad Bilal Khan Niazi; Reema Ansar; Zaib Jahan; Farhan Javaid; Rafiq Ahmad; Hirra Anjum; Muhammad Ibrahim; Awais Bokhari (Fuel, 2023)

Response of mineral market to renewable energy production in the USA: Where lies the sustainable energy future - Shujaat Abbas; Avik Sinha; Tanaya Saha; Muhammad Ibrahim Shah (Energy Policy, 2023)

The role of miR-433-3p in vascular calcification in type 2 diabetic patients: targeting WNT/β-Catenin and RANKL/RANK/OPG signaling pathways - Amira M. Elshamy; Yasser Mostafa Hafez; Mohamed A. E. Safa; Hoda A. Ibrahim; Mohamed Khalfallah; Fatma H. Rizk; Eman F. Eltabaa; Muhammad T. Abdel Ghafar; Marwa Mohamed Atef (Molecular Biology Reports, 2023)
Background Vascular calcification (VC) is a major predictor of cardiovascular diseases that represent the principal cause of mortality among type-2 diabetic patients. Accumulating data suggest the vital role of some microRNAs on vascular calcification as an epigenetic regulator. Thus, we assessed herein, the role of serum miR-433-3p in vascular calcification in type-2 diabetic patients. Methods Twenty healthy subjects (control group) and forty diabetic patients (20 without VC and 20 with VC) were involved in the study. miR-433-3p gene expression was measured. Runx2, Dickkopf-1 (DKK1), β-catenin, Receptor activator of nuclear factor kappa-B ligand (RANKL), and osteoprotegerin (OPG) levels in serum were assessed by ELISA technique. Results Diabetes patients had significantly lower levels of miR-433-3p expression in comparison to the control group, with the lowest levels being found in diabetic patients with VC. Furthermore, Runx2, β-catenin, and RANKL levels were significantly increased with concomitant lower DKK1 and OPG levels detected in the two diabetic groups especially those with VC. Conclusion Collectively, the study documented that down-regulation of miR-433-3p may contribute to the development of VC through activating WNT/β-Catenin and RANKL/RANK/OPG signaling pathways.

Technology advancement and international law in marine policy, challenges, solutions and future prospective - Muhammad Bilawal Khaskheli; Shumin Wang; Xin Zhang; Imran Haider Shamsi; Chenghuan Shen; Sanober Rasheed; Zakir Ibrahim; Dost Muhammad Baloch (Frontiers in Marine Science, 2023)
The use of technology and international law in marine policy is becoming increasingly vital as we seek to address the challenges facing our oceans. Technology has revolutionized our ability to monitor, understand, and manage marine ecosystems, providing valuable tools for data collection, analysis, and decision-making. International law, ocean governance ensuring marine environment represented by the frameworks such as the United Nations Convention on the Law of the Sea (UNCLOS), plays a crucial role in governing the use of technology and establishing guidelines for the sustainable management of marine resources. This paper explores the intersection of technology and international law in marine policy, highlighting the transformative impact of technology on our understanding of the oceans and the legal frameworks that shape our approach to marine conservation. It examines the benefits of technology in enabling evidence-based decision-making and fostering international collaboration, while also addressing the legal and regulatory complexities that arise. The paper emphasizes the need for ongoing dialogue and the development of international legal frameworks to adapt to emerging technologies and discourse ethical considerations, and by harnessing the power of technology and international law, we can work towards effective marine policies that ensure the conservation and sustainable use of our oceans for future generations.

Sustainable remediation of dye-contaminated wastewater using novel cross-linked Hex-CCP-co-PPT microspheres - Sahid Mehmood; Fazal Haq; Mehwish Kiran; Ibrahim A. Shaaban; Mohammed A. Assiri; Muhammad Haroon; Muhammad Yasin; Arshad Farid; Alam Nawaz; Majid Majeed Akbar; Zeinhom M. El-Bahy (Chemosphere, 2023)

Nanoparticle-laden contact lens for controlled release of vancomycin with enhanced antibiotic efficacy - Woei Yenn Tong; Wen-Nee Tan; Muhammad Afif Kamarul Azizi; Chean Ring Leong; Islam H. El Azab; Jun Wei Lim; M.H.H. Mahmoud; Daniel Joe Dailin; Mohamed M. Ibrahim; Lai Fatt Chuah (Chemosphere, 2023)

Do stochastic risks flow between industrial and precious metals, Islamic stocks, green bonds, green stocks, clean investments, major foreign exchange rates, and Bitcoin? - Mahdi Ghaemi Asl; Ibrahim D. Raheem; Muhammad Mahdi Rashidi (Resources Policy, 2023)

Neutralizing the surging emissions amidst natural resource dependence, eco-innovation, and green energy in G7 countries: Insights for global environmental sustainability - Rabia Akram; Ridwan Lanre Ibrahim; Zhen Wang; Tomiwa Sunday Adebayo; Muhammad Irfan (Journal of Environmental Management, 2023)

RETRACTED ARTICLE: Inquiring asymmetric effects of oil prices, money supply, and domestic debt on consumer prices: an empirical evidence from Pakistan - Muhammad Shahid Hassan; Najam ul Hassan; Rukhsana Kalim; Muhammad Ibrahim Saeed; Haider Mahmood (Environmental Science and Pollution Research, 2023)

Oilseed meals into foods: an approach for the valorization of oilseed by-products - Gita Addelia Nevara; Shafa’atu Giwa Ibrahim; Sharifah Kharidah Syed Muhammad; Norhasnida Zawawi; Nor Afizah Mustapha; Roselina Karim (Critical Reviews in Food Science and Nutrition, 2023)

Mitracarpus hirtus (L.) DC.: is a potential source for the exploitation of anticancer agents - Ibrahim Malami; Muhammad Muhammad Batako; Alhasan Muhammad Alhasan; Ibrahim Babangida Abubakar (Natural Product Research, 2023)

Exergoeconomic and environmental analyses of a geothermal-powered tri-generation system: A study of CO2 emission reduction - Fulai Liu; Muhammad Asadollahzadeh; Bhupendra Singh Chauhan; Ibrahim Elbadawy; Mohamed Abouelela; Bashir Salah; Huynh Nháng (Process Safety and Environmental Protection, 2023)

Linking diagenesis and reservoir quality to depositional facies in marginal to shallow marine sequence: An example from the Campano-Maastrichtian Gombe Sandstone, Northern Benue Trough, NE Nigeria - Abdulwahab M. Bello; Musa B. Usman; Muhammad A. Ismail; Shehu Mukkafa; Usman Abubakar; Ibrahim A. Kwami; Khalid Al-Ramadan; Abduljamiu O. Amao; Murtada Al-Hashem; Anas M. Salisu; Aliyuda Kachalla; Muhammad B. Abubakar; et al. (Marine and Petroleum Geology, 2023)

Strategic resources alignment for sustainability: The impact of innovation capability and intellectual capital on SME's performance. Moderating role of external environment - Muhammad Zulqarnain Arshad; Darwina Arshad; Hendrik Lamsali; Ahmad Said Ibrahim Alshuaibi; Mohammad Said Ibrahim Alshuaibi; Gadah Albashar; Awais Shakoor; Lai Fatt Chuah (Journal of Cleaner Production, 2023)

Coumarin regulated redox homeostasis to facilitate phytoremediation of saline and alkaline soils by bitter gourd (Momordica charantia L.) - Kamila Iram; Muhammad Arslan Ashraf; Sobhy M. Ibrahim; Rizwan Rasheed; Shafaqat Ali (Environmental Science and Pollution Research, 2023)

Fabrication and Evaluation of Anticancer Potential of Eugenol Incorporated Chitosan-Silver Nanocomposites: In Vitro, In Vivo, and In Silico Studies - Hamid Saeed Shah; Sumera Zaib; Muhammad Sarfraz; A. Alhadhrami; Mohamed M. Ibrahim; Aamir Mushtaq; Faisal Usman; Memoona Ishtiaq; Muhammad Sajjad; Hafiz Muhammad Mazhar Asjad; Umar Farooq Gohar (AAPS PharmSciTech, 2023)

Dynamics of negotiated use of public open spaces between children and adults in an African city - Aliyu Salisu Barau; Ismaila Rimi Abubakar; Kamil Muhammad Kafi; Kemi Hamdat Olugbodi; Jibrin Ibrahim Abubakar (Land Use Policy, 2023)

Anti-Inflammatory, Antioxidant, Metabolic and Gut Microbiota Modulation Activities of Probiotic in Cardiac Remodeling Condition: Evidence from Systematic Study and Meta-Analysis of Randomized Controlled Trials - Nurpudji Astuti Taslim; Muhammad Yusuf; Ade Meidian Ambari; Imke Maria Del Rosario Puling; Filzatuz Zahro Ibrahim; Hardinsyah Hardinsyah; Rudy Kurniawan; William Ben Gunawan; Nelly Mayulu; Victor F. F. Joseph; Nindy Sabrina; Mochammad Rizal; et al. (Probiotics and Antimicrobial Proteins, 2023)
Heart failure (HF) is a global pandemic with increasing prevalence and mortality rates annually. Its main cause is myocardial infarction (MI), followed by rapid cardiac remodeling. Several clinical studies have shown that probiotics can improve the quality of life and reduce cardiovascular risk factors. This systematic review and meta-analysis aimed to investigate the effectiveness of probiotics in preventing HF caused by a MI according to a prospectively registered protocol (PROSPERO: CRD42023388870). Four independent evaluators independently extracted the data using predefined extraction forms and evaluated the eligibility and accuracy of the studies. A total of six studies consisting of 366 participants were included in the systematic review. Probiotics are not significant in intervening left ventricular ejection fraction (LVEF) and high-sensitivity C-reactive protein (hs-CRP) when compared between the intervention group and the control group due to inadequate studies supporting its efficacy. Among sarcopenia indexes, hand grip strength (HGS) showed robust correlations with the Wnt biomarkers ( p < 0.05), improved short physical performance battery (SPPB) scores were also strongly correlated with Dickkopf-related protein (Dkk)-3, followed by Dkk-1, and sterol regulatory element-binding protein 1 (SREBP-1) ( p < 0.05). The probiotic group showed improvement in total cholesterol ( p = 0.01) and uric acid ( p = 0.014) compared to the baseline. Finally, probiotic supplements may be an anti-inflammatory, antioxidant, metabolic, and intestinal microbiota modulator in cardiac remodeling conditions. Probiotics have great potential to attenuate cardiac remodeling in HF or post-MI patients while also enhancing the Wnt signaling pathway which can improve sarcopenia under such conditions.

Effectiveness of sequence-related amplified polymorphism (SRAP) markers to assess the geographical origin and genetic diversity of collected lentil genotypes - Nabil A. Mohammed; Muhammad Afzal; Sulieman A. Al-Faifi; Muhammad A. Khan; Yahya A. Refay; Bazel H. AL-Samin; Salem S. Alghamdi; Abdullah Ibrahim (Plant Biotechnology Reports, 2023)

Identification and genome-wide analysis provide insights into the genetic diversity and biotechnological potentials of novel cold-adapted Acinetobacter strain - Hajra Kayani; Muhammad Asif Rasheed; Wadi B. Alonazi; Farrukh Jamil; Annam Hussain; ChangHui Yan; Raza Ahmed; Muhammad Ibrahim (Extremophiles, 2023)

Anar Phali (Opuntia ficus) juice extract as a novel pollution-free source of natural betalain dye for wool yarn - Yousra Riaz; Samra Barkaat; Shahid Adeel; Fazal-ur-Rehman; Muhammad Ibrahim; Muhammad Zuber; Meral Ozomay; Shahnaz Parveen Khattak (Environmental Science and Pollution Research, 2023)

Effect of seed priming by taurine on growth and chromium (Cr) uptake in canola (Brassica napus L.) under Cr stress - Muhammad Arslan Ashraf; Sobhy M. Ibrahim; Rizwan Rasheed; Muhammad Rizwan; Iqbal Hussain; Shafaqat Ali (Environmental Science and Pollution Research, 2023)

Iron deficiency and its epigenetic effects on iron homeostasis - Bashar Farida; Kasimu G. Ibrahim; Bilyaminu Abubakar; Ibrahim Malami; Muhammad B. Bello; Murtala B. Abubakar; Abdullahi Y. Abbas; Mustapha U. Imam (Journal of Trace Elements in Medicine and Biology, 2023)

Heavy Metal Occurrence, Pathways, and Associated Socio-ecological Risks in Riverine Water: Application of Geographic Information System, Multivariate Statistics, and Risk Assessment Models - Kifayatullah Khan; Muhammad Younas; Muhammad Sajawal Khan; Xu Li; Muhammad Fawad; Noor Samad Shah; Jafar Ali; Sana Ullah; Muhammad Ayaz; Afsheen Maryam; Asmat Ali; Akhtar Zeb Khan; et al. (Water, Air, & Soil Pollution, 2023)

Mg-Fe-LDH for Aquatic Selenium Treatment: Adsorption, RSM Modeling, and Machine Learning Neural Network - Ahmed I. A. Ibrahim; Muhammad S. Vohra (Water, Air, & Soil Pollution, 2023)

Evaluation of quality and hydrogeochemistry of rock aquifers in Jurong Formation at Southern Johor Bahru, Malaysia - Vynotdni Rathinasamy; Edy Tonnizam Mohamad; Ibrahim Komoo; Mariatul Kiftiah Ahmad Legiman; Nurul Amaniyah Romanah; Muhammad Nassir Bin Hanapi (Environmental Monitoring and Assessment, 2023)

Assessing the role of green supply chain management in enhancing Pakistan manufacturers’ performances - Muhammad Ibrahim Tariq; Kashif Abbass; Kaouther Chebbi; Yasir Hussain (Environmental Science and Pollution Research, 2023)

A critical review and prospect of NO2 and SO2 pollution over Asia: Hotspots, trends, and sources - Most. Mastura Munia Farjana Jion; Jannatun Nahar Jannat; Md. Yousuf Mia; Md. Arfan Ali; Md. Saiful Islam; Sobhy M. Ibrahim; Subodh Chandra Pal; Aznarul Islam; Aniruddha Sarker; Guilherme Malafaia; Muhammad Bilal; Abu Reza Md Towfiqul Islam (Science of The Total Environment, 2023)

Corrigendum to “How do green energy technology investments, technological innovation, and trade globalization enhance green energy supply and stimulate environmental sustainability in the G7 countries?” [Gondwana Res. 112 (2022) 105–115] - Zahoor Ahmed; Mahmood Ahmad; Muntasir Murshed; Muhammad Ibrahim Shah; Haider Mahmood; Shujaat Abbas (Gondwana Research, 2023)

Corrigendum to “The effects of environmental degradation on agriculture: Evidence from European countries” [Gondwana Res. 106 (2022) 92–104] - Duojiao Tan; Festus Fatai Adedoyin; Rafael Alvarado; Muhammad Ramzan; Md Safiullah Kayesh; Muhammad Ibrahim Shah (Gondwana Research, 2023)

Correction to: Analysing the Impact of Carbon Emissions and Non-Renewable Energy Use on Infant and Under-5 Mortality Rates in Europe: New Evidence Using Panel Quantile Regression - Bosede Ngozi Adeleye; Aviral Kumar Tiwari; Muhammad Ibrahim Shah; Saif Ullah (Environmental Modeling & Assessment, 2023)

Analysing the Impact of Carbon Emissions and Non-Renewable Energy Use on Infant and Under-5 Mortality Rates in Europe: New Evidence Using Panel Quantile Regression - Bosede Ngozi Adeleye; Aviral Kumar Tiwari; Muhammad Ibrahim Shah; Saif Ullah (Environmental Modeling & Assessment, 2023)

Environmental sustainability in Vietnam: evaluating the criticality of economic globalisation, renewable energy, and natural resources - Abraham Ayobamiji Awosusi; Huseyin Ozdeser; Opeoluwa Seun Ojekemi; Ibrahim Adeshola; Muhammad Ramzan (Environmental Science and Pollution Research, 2023)

Interactions between marine megafauna and plastic pollution in Southeast Asia - Lucy C.M. Omeyer; Emily M. Duncan; Neil Angelo S. Abreo; Jo Marie V. Acebes; Lea A. AngSinco-Jimenez; Sabiqah T. Anuar; Lemnuel V. Aragones; Gonzalo Araujo; Luis R. Carrasco; Marcus A.H. Chua; Muhammad R. Cordova; Lantun P. Dewanti; et al. (Science of The Total Environment, 2023)

Corrigendum to “The role of renewable energy and natural resources for sustainable agriculture in ASEAN countries: Do carbon emissions and deforestation affect agriculture productivity?” [Resour. Pol. (2022) 102578] - Ritika Chopra; Cosimo Magazzino; Muhammad Ibrahim Shah; Gagan Deep Sharma; Amar Rao; Umer Shahzad (Resources Policy, 2023)

Corrigendum to “An empirical investigation of resource curse hypothesis for cobalt” [Resour. Pol. (2022) 102843] - Veli Yilanci; N. Ceren Turkmen; Muhammad Ibrahim Shah (Resources Policy, 2023)

Bioactive Peptides from African Yam (AVIAIMF and GPADPF) and Taro (NGDF and NGNW) Reveal Multifunctional Antidiabetic Effects Using Biochemical and Cellular Models - Mohammed Auwal Ibrahim; June Cheptoo Serem; Aliyu Dantani Abdullahi; Suleiman Aminu; Abubakar Babando Aliyu; Aliyu Muhammad Musa; Bashir Musa; Megan J. Bester; Anabella R. M. Gaspar (International Journal of Peptide Research and Therapeutics, 2023)

An insight into the mechanisms of action of selected bioactive compounds against epigenetic targets of prostate cancer: implications on histones modifications - Babangida Sanusi Katsayal; Gilead Ebiegberi Forcados; Abdurrahman Pharmacy Yusuf; Yunus Aisha Lawal; Shehu Aisha Jibril; Hussaini Nuraddeen; Musa Mubarak Ibrahim; Idris Zubairu Sadiq; Murtala Bello Abubakar; Ibrahim Malami; Ibrahim Babangida Abubakar; Aliyu Muhammad (In Silico Pharmacology, 2023)

Microplastics in facial cleanser: extraction, identification, potential toxicity, and continuous-flow removal using agricultural waste–based biochar - Muhammad Adli Hanif; Naimah Ibrahim; Farrah Aini Dahalan; Umi Fazara Md. Ali; Masitah Hasan; Ayu Wazira Azhari; Aishah Abdul Jalil (Environmental Science and Pollution Research, 2023)

Weak base-modulated synthesis of bundle-like carbon superstructures from metal-organic framework for high-performance supercapacitors - Zu-Shun Fan; Yusuf Valentino Kaneti; Silvia Chowdhury; Xiohan Wang; Muhammad Rezaul Karim; Ibrahim Abdullah Alnaser; Fei-Bao Zhang (Chemical Engineering Journal, 2023)

Recent Innovations in Non-dairy Prebiotics and Probiotics: Physiological Potential, Applications, and Characterization - Fasiha Fayyaz Khan; Asma Sohail; Shakira Ghazanfar; Asif Ahmad; Aayesha Riaz; Kashif Sarfraz Abbasi; Muhammad Sohail Ibrahim; Mohammad Uzair; Muhammad Arshad (Probiotics and Antimicrobial Proteins, 2023)

Identifying the roles of energy and economic factors on environmental degradation in MINT economies: a hesitant fuzzy analytic hierarchy process - Veli Yilanci; Gökçe Candan; Muhammad Ibrahim Shah (Environmental Science and Pollution Research, 2023)

Impact of differential occupational LPG exposure on cardiopulmonary indices, liver function, and oxidative stress in Northwestern city of Nigeria - Abubakar Usman Ismail; Salisu Ahmed Ibrahim; Mahdi Dissi Gambo; Ramlah Farouq Muhammad; Murtala Muhammad Badamasi; Ibrahim Sulaiman (Science of The Total Environment, 2023)

A three-dimensional active biochar for sintering in steel industry and remove methylene blue by synergistic activation of H3PO4 and ZnCl2 - Yu Zhang; Boxiong Shen; Muhammad Sajjad Ahmad; Wenjun Zhou; Rana Rehan Khalid; Muhammad Ibrahim; Awais Bokhari (Fuel, 2023)

A comprehensive study for Al2O3 nanofluid cooling effect on the electrical and thermal properties of polycrystalline solar panels in outdoor conditions - Ali Ibrahim; Muhammad Raafat Ramadan; Abd EL-Monem Khallaf; Muhammad Abdulhamid (Environmental Science and Pollution Research, 2023)
Photovoltaic (PV) technology is considered one of the most effective and promising renewable sources of energy. The PV system’s efficiency strongly depends on its operating temperature, which acts as a defect to the electrical efficiency by increasing over 25 °C. In this work, a comparison was performed between three traditional polycrystalline solar panels simultaneously at the same time and under the same weather conditions. The electrical and thermal performances of the photovoltaic thermal (PVT) system integrated with a serpentine coil configured sheet with a plate thermal absorber setup are evaluated using water and aluminum oxide nanofluid. For higher mass flow rates and nanoparticle concentrations, an improvement in the PV modules short-circuit current ( I sc ) and open-circuit voltage ( V oc ) yield and electrical conversion efficiency is achieved. The enhancement in the PVT electrical conversion efficiency is 15.5%. For 0.05% volume concentration of Al 2 O 3 and flow rate of 0.07 kg/s, an enhancement of 22.83% of the temperature of PVT panels’ surface over the reference panel has been obtained. An uncooled PVT system reached a maximum panel temperature of 75.5 °C at noontime and obtained an average electrical efficiency of 12.156%. Water and nanofluid cooling reduce the panel temperature by 10.0 °C and 20.0 °C at noontime, respectively.

Cellulose/inorganic nanoparticles-based nano-biocomposite for abatement of water and wastewater pollutants - Zhen Zhang; Abdulrazaq Ibrahim Said Ahmed; Muhammad Zeeshan Malik; Nisar Ali; Adnan khan; Farman Ali; Mohamed Osman Hassan; Badr A. Mohamed; Jakub Zdarta; Muhammad Bilal (Chemosphere, 2023)

Mixed micellar solubilization for procion blue MxR entrapment and optimization of necessary parameters for micellar enhanced ultrafiltration - Amnah Yusaf; Muhammad Usman; Muhammad Ibrahim; Asim Mansha; Atta ul Haq; Hafiza Fatima Rehman; Majid Ali (Chemosphere, 2023)

Influence of hydraulic properties to residual soil - Aniza Ibrahim; Muhammad Mukhlisin; Rohaya Alias (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Effect of waste cooking oil on warm mix asphalt block pavement – A comprehensive review - Yusuf Babangida Attahiru; Azman Mohamed; Ahmed Eltwati; Aliyu Abubakar Burga; Abubakar Ibrahim; Abdullahi Muhammad Nabade (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

The potential of shear wave velocity as an erosion risk index - Norinah Abd Rahman; Muhammad Ali Rehman; Nur Afiqah Zahari; Aizat Mohd Taib; Wan Hanna Melini Wan Mohtar; Ahmad Bukhari Ramli; Aniza Ibrahim; Dayang Zulaika Abang Hasbollah; Sadia Mannan Mitu; Mohamad Faizal Nurddin (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Critical insight into sediment microbial fuel cell: Fundamentals, challenges, and perspectives as a barrier to black-odor water formation - Umar Abdulbaki Danhassan; Hongjian Lin; Ibrahim Lawan; Xin Zhang; Mahmoud H. Ali; Aliyu Idris Muhammad; Kuichuan Sheng (Journal of Environmental Chemical Engineering, 2023)

A multifunctional key to open a new window on the path to natural resources-lessons from a study on chemical composition and biological capability of Paeonia mascula L. from Turkey - İnci Kurt-Celep; Gokhan Zengin; Engin Celep; Stefano Dall’Acqua; Stefania Sut; Irene Ferrase; Gunes Ak; Abdullahi Ibrahim Uba; Rıdvan Polat; Deniz Canlı; Ekrem Darendelioglu; Muhammad Zakariyyah Aumeeruddy; et al. (Food Bioscience, 2023)

An assessment of the efficacy of biochar and zero-valent iron nanoparticles in reducing lead toxicity in wheat (Triticum aestivum L.). - Muhammad Nauman Mahamood; Sihang Zhu; Ali Noman; Abid Mahmood; Sana Ashraf; Muhammad Aqeel; Muhammad Ibrahim; Sobia Ashraf; Rock Keey Liew; Su Shiung Lam; Muhammad Kashif Irshad (Environmental Pollution, 2023)

Centella asiatica (L.) Urb. Extract ameliorates branched-chain amino acid (BCAA) metabolism in acute reserpine-induced stress zebrafish model via 1H Nuclear Magnetic Resonance (NMR)-based metabolomics approach - Fauziahanim Zakaria; Muhammad Tayyab Akhtar; Wan Ibrahim Wan Norhamidah; Abu Bakar Noraini; Azira Muhamad; Shamarina Shohaimi; Maulidiani; Hafandi Ahmad; Intan Safinar Ismail; Nor Hadiani Ismail; Khozirah Shaari (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Alleviation of drought stress and mediated antioxidative defense in wheat through moringa leaf extract hormesis - Muhammad Usman Ibrahim; Abdul Khaliq; Saddam Hussain; Muhammad Zia Ul Haq (Arabian Journal of Geosciences, 2023)

Correction to: Does political risk spur environmental issues in China? - Dervis Kirikkaleli; Muhammad Ibrahim Shah; Tomiwa Sunday Adebayo; Mehmet Altuntaş (Environmental Science and Pollution Research, 2023)

Correction to: Exploring the linkage between export diversification and ecological footprint: evidence from advanced time series estimation techniques - Shahid Ali; Muhlis Can; Muhammad Ibrahim Shah; Junfeng Jiang; Zahoor Ahmed; Muntasir Murshed (Environmental Science and Pollution Research, 2023)

Correction to: Inequality consequences of natural resources, environmental vulnerability, and monetary‑fiscal stability: a global evidence - Muhammad Ibrahim Shah; Muhammad Shehu Shuaibu; Hauwah K. K. AbdulKareem; Zulfiqar Khan; Shujaat Abbas (Environmental Science and Pollution Research, 2023)

Correction to: Tourism adaptability amid the climate change and air pollution in BRICS: a method of moments quantile regression approach - Muhammad Ibrahim Shah; Zulfiqar Khan; Minani Leon Moise; Shujaat Abbas (Environmental Science and Pollution Research, 2023)

Correction to: Nexus between environmental vulnerability and agricultural productivity in BRICS: what are the roles of renewable energy, environmental policy stringency, and technology? - Muhammad Ibrahim Shah; Muhammad Usman; Hephzibah Onyeje Obekpa; Shujaat Abbas (Environmental Science and Pollution Research, 2023)

Correction to: Quantifying the effect of waste on soil health in European Union: what are the roles of technology, natural capital, and institutional quality? - Muhammad Ibrahim Shah; Abdulrasheed Zakari; Siddharth Kumar; Shujaat Abbas; Muhammad Sheraz (Environmental Science and Pollution Research, 2023)

Biocatalytic degradation of reactive blue 221 and direct blue 297 dyes by horseradish peroxidase immobilized on iron oxide nanoparticles with improved kinetic and thermodynamic characteristics - Umme Kalsoom; Nasira Khalid; Affaf Ibrahim; Syed Salman Ashraf; Haq Nawaz Bhatti; Zainab Ahsan; Jakub Zdarta; Muhammad Bilal (Chemosphere, 2023)

Efficient application of newly synthesized green Bi2O3 nanoparticles for sustainable biodiesel production via membrane reactor - Sawaira; Mabkhoot Alsaiari; Mushtaq Ahmad; Mamoona Munir; Muhammad Zafar; Shazia Sultana; Sumreen Dawood; Abdulaziz Ibrahim Almohana; Al-Marzouki Hassan M.H; Abdulrahman Faraj Alharbi; Zubair Ahmad (Chemosphere, 2023)

Analysis of industrial symbiosis case studies and its potential in Saudi Arabia - Zaid Ahsan Khan; Saidur R. Chowdhury; Bijoy Mitra; Mohammad Sayem Mozumder; Alaeldeen Ibrahim Elhaj; Babatunde A. Salami; Muhammad Muhitur Rahman; Syed Masiur Rahman (Journal of Cleaner Production, 2023)

Functionalized graphene oxide-zinc oxide hybrid material and its deployment for adsorptive removal of levofloxacin from aqueous media - Nimra Ismail; Muhammad Imran; Muhammad Ramzan; Ayesha Anwar; Ibrahim A. Alsafari; Muhammad Asgher; Hafiz M.N. Iqbal (Environmental Research, 2023)

Health impacts from TRAPs and carbon emissions in the projected electric vehicle growth and energy generation mix scenarios in Malaysia - Soo Chen Kwan; Sazalina binti Zakaria; Mohd Faiz Ibrahim; Wan Rozita Wan Mahiyuddin; Nurzawani Md Sofwan; Muhammad Ikram A Wahab; Radin Diana R. Ahmad; Ahmad Rosly Abbas; Wei Kian Woon; Mazrura Sahani (Environmental Research, 2023)

Synthetic star shaped tetra-tailed biocompatible supramolecular amphiphile as an efficient nanocarrier for Amphotericin B - Imdad Ali; Samiullah Burki; Jawad ur Rehman; Shafi Ullah; Ibrahim Javid; Magda H. Abdellattif; Muhammad Raza Shah (Chemistry and Physics of Lipids, 2023)

Naturally occurring plant-based anticancerous candidates as prospective ABCG2 inhibitors: an in silico drug discovery study - Mahmoud A. A. Ibrahim; Alaa H. M. Abdelrahman; Esraa A. A. Badr; Nahlah Makki Almansour; Othman R. Alzahrani; Muhammad Naeem Ahmed; Mahmoud E. S. Soliman; Mohamed Ahmed Naeem; Ahmed M. Shawky; Peter A. Sidhom; Gamal A. H. Mekhemer; Mohamed A. M. Atia (Molecular Diversity, 2022)
ATP-binding cassette transporter G2 (ABCG2) is an efflux transporter related to the clinical multidrug resistance (MDR) phenomenon. Identifying ABCG2 inhibitors could help discover extraordinary curative strategies for carcinoma remediation. Hitherto, there is no medication drug inhibiting ABCG2 transporter, notwithstanding that a considerable number of drugs have been submitted to clinical-trial and investigational phases. In the search for unprecedented chemical compounds that could inhibit the ABCG2 transporter, an in silico screening was conducted on the Naturally Occurring Plant-based Anticancer Compound-Activity-Target (NPACT) database containing 1574 compounds. Inhibitor-ABCG2 binding affinities were estimated based on molecular docking and molecular minimization (MM) calculations and compared to a co-crystallized inhibitor (BWQ) acting as a reference inhibitor. Molecular dynamics (MD) simulations pursued by molecular mechanics-generalized Born surface area (MM-GBSA) binding energy estimations were further executed for compounds with MM-GBSA//MM binding energies lower than BWQ (calc. − 60.5 kcal/mol). NPACT00968 and NPACT01545 demonstrated auspicious inhibitory activities according to binding affinities (Δ G binding ) over the 100 ns MD simulations that were nearly one and a half folds compared to BWQ (− 100.4, − 94.7, and − 62.9 kcal/mol, respectively). Throughout the 100 ns MD simulations, structural and energetical analyses unveiled outstanding stability of the ABCG2 transporter when bound with NPACT00968 and NPACT01545. In silico calculations hold a promise for those two inhibitors as drug candidates of ABCG2 transporter and emphasize that further in vitro and in vivo experiments are guaranteed. Graphical abstract

BoT-Net: a lightweight bag of tricks-based neural network for efficient LncRNA–miRNA interaction prediction - Muhammad Nabeel Asim; Muhammad Ali Ibrahim; Christoph Zehe; Johan Trygg; Andreas Dengel; Sheraz Ahmed (Interdisciplinary Sciences: Computational Life Sciences, 2022)
Background and objective: Interactions of long non-coding ribonucleic acids (lncRNAs) with micro-ribonucleic acids (miRNAs) play an essential role in gene regulation, cellular metabolic, and pathological processes. Existing purely sequence based computational approaches lack robustness and efficiency mainly due to the high length variability of lncRNA sequences. Hence, the prime focus of the current study is to find optimal length trade-offs between highly flexible length lncRNA sequences. Method The paper at hand performs in-depth exploration of diverse copy padding, sequence truncation approaches, and presents a novel idea of utilizing only subregions of lncRNA sequences to generate fixed-length lncRNA sequences. Furthermore, it presents a novel bag of tricks-based deep learning approach “Bot-Net” which leverages a single layer long-short-term memory network regularized through DropConnect to capture higher order residue dependencies, pooling to retain most salient features, normalization to prevent exploding and vanishing gradient issues, learning rate decay, and dropout to regularize precise neural network for lncRNA–miRNA interaction prediction. Results BoT-Net outperforms the state-of-the-art lncRNA–miRNA interaction prediction approach by 2%, 8%, and 4% in terms of accuracy, specificity, and matthews correlation coefficient. Furthermore, a case study analysis indicates that BoT-Net also outperforms state-of-the-art lncRNA–protein interaction predictor on a benchmark dataset by accuracy of 10%, sensitivity of 19%, specificity of 6%, precision of 14%, and matthews correlation coefficient of 26%. Conclusion In the benchmark lncRNA–miRNA interaction prediction dataset, the length of the lncRNA sequence varies from 213 residues to 22,743 residues and in the benchmark lncRNA–protein interaction prediction dataset, lncRNA sequences vary from 15 residues to 1504 residues. For such highly flexible length sequences, fixed length generation using copy padding introduces a significant level of bias which makes a large number of lncRNA sequences very much identical to each other and eventually derail classifier generalizeability. Empirical evaluation reveals that within 50 residues of only the starting region of long lncRNA sequences, a highly informative distribution for lncRNA–miRNA interaction prediction is contained, a crucial finding exploited by the proposed BoT-Net approach to optimize the lncRNA fixed length generation process. Availability: BoT-Net web server can be accessed at https://sds_genetic_analysis.opendfki.de/lncmiRNA/. Graphic Abstract

The roles of organic farming, renewable energy, and corruption on biodiversity crisis: a European perspective - Qingran Guo; Muhammad Ibrahim Shah; Siddharth Kumar; Hauwah K. K. AbdulKareem; Nasiru Inuwa (Environmental Science and Pollution Research, 2022)

Tourism adaptability amid the climate change and air pollution in BRICS: a method of moments quantile regression approach - Muhammad Ibrahim Shah; Zulfiqar Khan; Minani Leon Moise; Shujaat Abbas (Environmental Science and Pollution Research, 2022)

Causal nexus in industrialization, urbanization, trade openness, and carbon emissions: empirical evidence from OPEC economies - Muhammad Azam; Zia Ur Rehman; Yusnidah Ibrahim (Environment, Development and Sustainability, 2022)

The roles of energy, natural resources, agriculture and regional integration on CO2 emissions in selected countries of ASEAN: does political constraint matter? - Muhammad Ibrahim Shah; Hauwah K. K. AbdulKareem; Balogun Daud Ishola; Shujaat Abbas (Environmental Science and Pollution Research, 2022)

Evaluation of agro-morphological traits, seed characterization and genetic diversity of local rice (Oryza sativa L.) varieties of Pakistan - Urooj Fazal; Israr Ud Din; Amir Muhammad Khan; Fahim Ullah Khan; Mudassar Nawaz Khan; Navid Iqbal; Muhammad Ibrahim; Sajid Ali Khan Bangash (Genetic Resources and Crop Evolution, 2022)

Engineered and green natural pozzolan-nano silica-based alkali-activated concrete: shrinkage characteristics and life cycle assessment - Babatunde Abiodun Salami; Mohammed Ibrahim; Mohammed A. Al-Osta; Muhammad Nasir; Mohammed Rizwan Ali; Ashraf A. Bahraq; Alimi Wasiu (Environmental Science and Pollution Research, 2022)

Sub-acute toxicity study on hydromethanolic leaves extract of Combretum hypopilinum (Combretaceae) Diels in Wistar rats - Mubarak Hussaini Ahmad; Abdulkadir Umar Zezi; Sherifat Bola Anafi; Omar Yahya Alshargi; Mustapha Mohammed; Sagir Mustapha; Auwal Adam Bala; Surajuddeen Muhammad; Sa’adatu Muhammad Julde; Abubakar Sadiq Wada; Abubakar Ibrahim Jatau (Toxicological Research, 2022)

Correction to: Role of casting and curing conditions on the strength and drying shrinkage of greener concrete - Muhammad Nasir; Adeyemi Adesina; Mohammed Ibrahim; Muhammad Umar Khan; Omar S. Baghabra Al‑Amoudi; Syed Imran Ali; Mohammed Maslehuddin; Khalid Saqer Alotaibi (Environmental Science and Pollution Research, 2022)

Quantifying the effect of waste on soil health in European Union: what are the roles of technology, natural capital, and institutional quality? - Muhammad Ibrahim Shah; Abdulrasheed Zakari; Siddharth Kumar; Shujaat Abbas; Muhammad Sheraz (Environmental Science and Pollution Research, 2022)

Role of casting and curing conditions on the strength and drying shrinkage of greener concrete - Muhammad Nasir; Adeyemi Adesina; Mohammed Ibrahim; Muhammad Umar Khan; Omar S. Baghabra Al-Amoudi; Syed Imran Ali; Mohammed Maslehuddin; Khalid Saqer Alotaibi (Environmental Science and Pollution Research, 2022)

Nexus between environmental vulnerability and agricultural productivity in BRICS: what are the roles of renewable energy, environmental policy stringency, and technology? - Muhammad Ibrahim Shah; Muhammad Usman; Hephzibah Onyeje Obekpa; Shujaat Abbas (Environmental Science and Pollution Research, 2022)

Inequality consequences of natural resources, environmental vulnerability, and monetary-fiscal stability: a global evidence - Muhammad Ibrahim Shah; Muhammad Shehu Shuaibu; Hauwah K. K. AbdulKareem; Zulfiqar Khan; Shujaat Abbas (Environmental Science and Pollution Research, 2022)

Correction to: Genotoxic and cytotoxic effects of pethoxamid herbicide on Allium cepa cells and its molecular docking studies to unravel genotoxicity mechanism - Recep Liman; Muhammad Muddassir Ali; Erman Salih Istifli; İbrahim Hakkı Ciğerci; Elena Bonciu (Environmental Science and Pollution Research, 2022)

Genotoxic and cytotoxic effects of pethoxamid herbicide on Allium cepa cells and its molecular docking studies to unravel genotoxicity mechanism - Recep Liman; Muhammad Muddassir Ali; Erman Salih Istifli; İbrahim Hakkı Ciğerci; Elena Bonciu (Environmental Science and Pollution Research, 2022)

Does political risk spur environmental issues in China? - Dervis Kirikkaleli; Muhammad Ibrahim Shah; Tomiwa Sunday Adebayo; Mehmet Altuntaş (Environmental Science and Pollution Research, 2022)

Heavy metal pollution in the soil of a riverine basin: distribution, source, and potential hazards - Kifayatullah Khan; Abdul Mohsin; Hafiz Muhammad Adeel Sharif; Afsheen Maryam; Jafar Ali; Xu Li; Sobhy Mostafa Ibrahim; Muhammad Ayaz; Yunqiao Zhou; Muhammad Younas (Environmental Monitoring and Assessment, 2022)

Design considerations of variable rate liquid fertilizer applicator for mature oil palm trees - Muhammad Yamin; Wan Ishak bin Wan Ismail; Samsuzana Abd Aziz; Muhamad Saufi bin Mohd Kassim; Farah Naz Akbar; Muhammad Ibrahim (Precision Agriculture, 2022)

Cowpea induced physicochemical and biological rhizosphere changes in hydrocarbon contaminated soil - A. A. Farouq; H. Y. Ismail; A. B. Rabah; A. B. Muhammad; U. B. Ibrahim; A. Y. Fardami (Plant and Soil, 2022)

Pollution of heavy metal threat posed by e-waste burning and its assessment of human health risk - Ahmed Abubakar; Aminu Sulaiman Zangina; Ahmed Ibrahim Maigari; Murtala Muhammad Badamasi; Mohd Yusoff Ishak; Amina Sheikh Abdullahi; Jamilu Adamu Haruna (Environmental Science and Pollution Research, 2022)

Short-term dynamics and long-term relationship between natural gas consumption and economic growth in Nigeria: an ARDL approach with breaks - Mukhtar Danladi Galadima; Abubakar Wambai Aminu; Ibrahim Muhammad Adam; Ibrahim Mohammed Adamu; Hassan Hassan Suleiman (Environmental Science and Pollution Research, 2022)

Mass spectrometry in research laboratories and clinical diagnostic: a new era in medical mycology - Hasti Kamali Sarvestani; Alireza Ramandi; Muhammad Ibrahim Getso; Taraneh Razavyoon; Javad Javidnia; Miaad Banay Golrizi; Ali-Akbar Saboor-Yaraghi; Saham Ansari (Brazilian Journal of Microbiology, 2022)

Variations in the Serum Sialic Acid Profiles of Malaria Patients in Zaria, Nigeria: A Cross-Sectional Study - Mbateudi Danjuma Ika; Mohammed Auwal Ibrahim; Abdullahi Balarabe Sallau; Abdulmalik Abdullahi Salman; Abubakar Muhammad Sani; Murtala Bindawa Isah (Acta Parasitologica, 2022)

Exploring the linkage between export diversification and ecological footprint: evidence from advanced time series estimation techniques - Shahid Ali; Muhlis Can; Muhammad Ibrahim Shah; Junfeng Jiang; Zahoor Ahmed; Muntasir Murshed (Environmental Science and Pollution Research, 2022)

Recent approaches on the optimization of biomass gasification process parameters for product H2 and syngas ratio: a review - Muhammad Zain Siddiqui; Mahshab Sheraz; Umair Ali Toor; Ali Anus; Abid Mahmood; Muhammad Haseeb; Muhammad Ibrahim; Kuan Shiong Khoo; Vishno Vardhan Devadas; Muhammad Mubashir; Sami Ullah; Pau Loke Show (Environment, Development and Sustainability, 2022)

The potential role of dietary plant ingredients against mammary cancer: a comprehensive review - Amjad Hussain; Marie-Lise Bourguet-Kondracki; Farhad Hussain; Abdur Rauf; Muhammad Ibrahim; Muhammad Khalid; Hidayat Hussain; Javid Hussain; Iftikhar Ali; Anees Ahmed Khalil; Fahad A. Alhumaydhi; Muhammad Khan; et al. (Critical Reviews in Food Science and Nutrition, 2022)

Genesis and timing of Mo mineralization in the Mada Ring Complex, north-central Nigeria: insights from whole-rock geochemistry, Nd-Sr isotopes, zircon U-Pb-Hf isotopes, and molybdenite Re-Os systematics - Musa Bala Girei; Huan Li; Victor Ikechukwu Vincent; Thomas J. Algeo; Safiyanu Muhammad Elatikpo; Saleh Ibrahim Bute; Hafizullah Abba Ahmed; Abdulgafar Kayode Amuda (Mineralium Deposita, 2022)

Development of Genome-wide SSR Markers for Physical Map Construction with PCR-based Polymorphic SSRs in Jute (Corchorus Spp.) - Sylvain Niyitanga; Jiayu Yao; Aminu kurawa Ibrahim; Muhammad Zohaib Afzal; Siyuan Chen; Liwu Zhang (Tropical Plant Biology, 2022)

In silico molecular docking and molecular dynamic simulation of potential inhibitors of 3C-like main proteinase (3CLpro) from severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) using selected african medicinal plants - Mustafa Alhaji Isa; Adam Mustapha; Sahar Qazi; Khalid Raza; Ibrahim Alkali Allamin; Muhammad M. Ibrahim; Mohammed M. Mohammed (Advances in Traditional Medicine, 2022)

Effects of dietary palm oil on broiler chicken productive performance and carcass characteristics: a comprehensive review - Mookiah Saminathan; Wan Nooraida Wan Mohamed; ‘Abidah Md Noh; Nur Atikah Ibrahim; Muhammad Amirul Fuat; Suriya Kumari Ramiah (Tropical Animal Health and Production, 2022)

Sorghum Water Extract Application Mediates Antioxidant Defense and Confers Drought Stress Tolerance in Wheat - Muhammad Usman Ibrahim; Abdul Khaliq; Saddam Hussain; Ghulam Murtaza (Journal of Plant Growth Regulation, 2022)

Metabolite profile and gene expression of the roots of oil palm seedlings treated with Hendersonia GanoEF1 and infected with Ganoderma boninense - Muhammad Faiz Ismail; Rosimah Nulit; Idris Abu Seman; Mohd Hafiz Ibrahim; Nurrashyeda Ramli (Journal of Plant Pathology, 2022)

Assessing the effect of climate change and financial development on agricultural production in ASEAN-4: the role of renewable energy, institutional quality, and human capital as moderators - Abbas Ali Chandio; Muhammad Ibrahim Shah; Narayan Sethi; Zulqarnain Mushtaq (Environmental Science and Pollution Research, 2022)

Multivariate analysis of accumulation and critical risk analysis of potentially hazardous elements in forage crops - Muhammad Usman; Behzad Murtaza; Natasha Natasha; Muhammad Imran; Ghulam Abbas; Muhammad Amjad; Muhammad Shahid; Sobhy M. Ibrahim; Gary Owens; Ghulam Murtaza (Environmental Monitoring and Assessment, 2022)

Land-use change influence ecosystem services in an agricultural landscape in Central America - Diego E. Tobar López; Bonin Muriel; Hernán J. Andrade; Muhammad Ibrahim (Agroforestry Systems, 2022)

Waterbird Population Estimates in Hadejia-Nguru Wetlands: Analysis of a Five-Year Monitoring Program - Sulaiman Inuwa Muhammad; Harry Hanson Junior; Abubakar Surajo Ringim; Ibrahim Lawal Muhammad; Joseph Onoja (Wetlands, 2022)

QTL Mapping and Expression Analysis of Candidate Genes for Salt and Drought Tolerance in Corchorus capsularis Seedlings - Aminu Kurawa Ibrahim; Yi Xu; Sylvain Niyitanga; Muhammad Zohaib Afzal; Lilan Zhang; Liemei Zhang; Jianmin Qi; Liwu Zhang (Tropical Plant Biology, 2021)

Virulence Factors and Azole-Resistant Mechanism of Candida Tropicalis Isolated from Candidemia - Elahe Sasani; Mohammad Hossein Yadegari; Sadegh Khodavaisy; Sassan Rezaie; Mohammadreza Salehi; Muhammad Ibrahim Getso (Mycopathologia, 2021)

Quest for Novel Preventive and Therapeutic Options Against Multidrug-Resistant Pseudomonas aeruginosa - Sidra Irum; Saadia Andleeb; Amjad Ali; Muhammad Ibrahim Rashid; Mahnoor Majid (International Journal of Peptide Research and Therapeutics, 2021)

Petrogenesis of the peralkaline Dutsen Wai and Ropp complexes in the Nigerian younger granites: implications for crucial metal enrichments - Abdulgafar Kayode Amuda; Xiaoyong Yang; Jianghong Deng; Mohamed Faisal; Jinya Cao; Saleh Ibrahim Bute; Musa Bala Girei; Safiyanu Muhammad Elatikpo (International Geology Review, 2021)

Reduced root mycorrhizal colonization as affected by phosphorus fertilization is responsible for high cadmium accumulation in wheat - M. Atilla Yazici; Muhammad Asif; Yusuf Tutus; Ibrahim Ortas; Levent Ozturk; Hans Lambers; Ismail Cakmak (Plant and Soil, 2021)

Sources, chemistry, bioremediation and social aspects of arsenic-contaminated waters: a review - Syed Ejaz Hussain Mehdi; Rabia Amen; Awais Ali; Hirra Anjum; Abid Mahmood; Muhammad Mubashir; Ahmad Mukhtar; Sami Ullah; Abdullah G. Al-Sehemi; Muhammad Ibrahim; Mohd Shariq Khan; Muhammad Abdul Qyyum; et al. (Environmental Chemistry Letters, 2021)

Effects of vegetable oil supplementation on rumen fermentation and microbial population in ruminant: a review - Nur Atikah Ibrahim; Abdul Razak Alimon; Halimatun Yaakub; Anjas Asmara Samsudin; Su Chui Len Candyrine; Wan Nooraida Wan Mohamed; Abidah Md Noh; Muhammad Amirul Fuat; Saminathan Mookiah (Tropical Animal Health and Production, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Cytotoxic and genotoxic evaluation of copper oxychloride through Allium test and molecular docking studies - Recep Liman; Muhammad Muddassir Ali; İbrahim Hakkı Ciğerci; Erman Salih İstifli; Cengiz Sarıkurkcu (Environmental Science and Pollution Research, 2021)

Simulation-based non-linear vibration model for damage detection in RC beams - Muhammad Usman Hanif; Zainah Ibrahim; Mohammed Jameel; Khaled Ghaedi; Huzaifa Hashim (European Journal of Environmental and Civil Engineering, 2021)

Candidate Rlm6 resistance genes against Leptosphaeria. maculans identified through a genome-wide association study in Brassica juncea (L.) Czern - Hua Yang; Nur Shuhadah Mohd Saad; Muhammad Ishaq Ibrahim; Philipp E. Bayer; Ting Xiang Neik; Anita A. Severn-Ellis; Aneeta Pradhan; Soodeh Tirnaz; David Edwards; Jacqueline Batley (Theoretical and Applied Genetics, 2021)

Teleconnection of spatial variations of effective onset of rainfall and ENSO\IOD over savanna zones of Nigeria - Ishiaku Ibrahim; Muhammad T. Usman (Theoretical and Applied Climatology, 2021)

Employing social vulnerability index to assess household social vulnerability of natural hazards: an evidence from southwest coastal Bangladesh - Anjum Tasnuva; Md. Riad Hossain; Roquia Salam; Abu Reza Md. Towfiqul Islam; Muhammad Mainuddin Patwary; Sobhy M. Ibrahim (Environment, Development and Sustainability, 2021)

Immunoinformatics Driven Prediction of Multiepitopic Vaccine Against Klebsiella pneumoniae and Mycobacterium tuberculosis Coinfection and Its Validation via In Silico Expression - Sidra Rahmat Ullah; Mahnoor Majid; Muhammad Ibrahim Rashid; Khalid Mehmood; Saadia Andleeb (International Journal of Peptide Research and Therapeutics, 2021)

Sustainable management of cut flowers waste by activation and its application in wastewater treatment technology - Muhammad Ashraf Sabri; Taleb Hassan Ibrahim; Mustafa Ibrahim Khamis; Adriane Ludwick; Paul Nancarrow (Environmental Science and Pollution Research, 2021)

Comparison of PCR-RFLP with 21-plex PCR and rDNA Sequencing for Identification of Clinical Yeast Isolates - Mohammad Kord; Ahmad Elmimoghaddam; Seyed Jamal Hashemi; Sassan Reziae; Roshanak Daie Ghazvini; Mohammadreza Salehi; Alireza Abdollahi; Ali Ahmadi; Muhammad Ibrahim Getso; Teun Boekhout; Sadegh Khodavaisy (Mycopathologia, 2021)

Correction to: Cytotoxic and genotoxic assessment of tungsten oxide nanoparticles in Allium cepa cells by Allium ana-telophase and comet assays - Recep Liman; Bermal Başbuğ; Muhammad Muddassir Ali; Yaser Acikbas; İbrahim Hakkı Ciğerci (Journal of Applied Genetics, 2021)

Assessment of heavy metal pollution in Brassica plants and their impact on animal health in Punjab, Pakistan - Zafar Iqbal; Farhat Abbas; Muhammad Ibrahim; Tahir Imran Qureshi; Matin Gul; Abid Mahmood (Environmental Science and Pollution Research, 2021)

Comparative analyses of standardised precipitation index and moisture quality index for wet and dry periods monitoring over the savanna zones of Nigeria - Ishiaku Ibrahim; Muhammad T. Usman (Arabian Journal of Geosciences, 2021)

Remote Sensing of Narrowing Barrier Islands along the Coast of Pakistan over Past 30 Years - Shamsa Kanwal; Xiaoli Ding; Muhammad Sajjad; Majid Nazeer; Ibrahim Zia (Journal of Marine Science and Engineering, 2021)
Barrier islands (BIs) are the first line of defense against the sea/wave actions in coastal areas, and assessing their stability is crucial in the context of effective coastal planning. Therefore, this study evaluates the spatial–temporal shoreline changes of the BIs in Pakistan over the past three decades (1989–2018). Satellite data from Landsat missions are used to delineate the shorelines of 19 BIs in Pakistan. After delineating the shorelines from satellite observations, two well-known statistical methods (i.e., end point rate (EPR) and linear regression rate (LRR)) are used to capture the localized changes in the BIs. The results ascertain that nearly all of the BIs have experienced noteworthy erosion during the past three decades. While the mean erosion over all the BIs during the study period is estimated to be >6 m/y, significant spatial heterogeneities among the individual BIs exist. The interdecadal comparison indicates that the highest mean erosion of the BIs occurred during the period 1989–1999 (13.03 ± 0.62 m/y), which gradually reduced over the preceding decades (i.e., 7.76 ± 0.62 m/y during the period 1999–2009 and 3.8 ± 0.7 m/y during the period 2009–2018). Nevertheless, ~65% of the total BIs experienced high erosion (>2 m/y), ~15% experienced moderate (

Arsenic and lead in the indoor residential settings of different socio-economic status; assessment of human health risk via dust exposure - Nadeem Ali; Syed Ali Musstjab Akber Shah Eqani; Ehtisham Nazar; Nabil A. Alhakamy; Muhammad Imtiaz Rashid; Khurram Shahzad; Jahan Zeb; Heqing Shen; Iqbal Mohammad Ibrahim Ismail; Hussain Mohammed Salem Ali Albar (Environmental Science and Pollution Research, 2021)

CO2 from waste to resource by developing novel mixed matrix membranes - Adeel Shakoor; Asim Laeeq Khan; Parveen Akhter; Muhammad Aslam; Muhammad Roil Bilad; Ibrahim M. Maafa; Konstantinos Moustakas; Abdul-Sattar Nizami; Murid Hussain (Environmental Science and Pollution Research, 2021)

Cytotoxic and genotoxic assessment of tungsten oxide nanoparticles in Allium cepa cells by Allium ana-telophase and comet assays - Recep Liman; Bermal Başbuğ; Muhammad Muddassir Ali; Yaser Acikbas; İbrahim Hakkı Ciğerci (Journal of Applied Genetics, 2021)

Transfer Learning for Prognostics and Health Management (PHM) of Marine Air Compressors - Magnus Gribbestad; Muhammad Umair Hassan; Ibrahim A. Hameed (Journal of Marine Science and Engineering, 2021)
Prognostics is an engineering discipline focused on predicting the time at which a system or a component will no longer perform its intended function. Due to the requirements of system safety and reliability, the correct diagnosis or prognosis of abnormal condition plays a vital role in the maintenance of industrial systems. It is expected that new requirements in regard to autonomous ships will push suppliers of maritime equipment to provide more insight into the conditions of their systems. One of the stated challenges with these systems is having enough run-to-failure examples to build accurate-enough prognostic models. Due to the scarcity of enough reliable data, transfer learning is established as a successful approach to improve and reduce the need to labelled examples. Transfer learning has shown excellent capabilities in image classification problems. Little work has been done to explore and exploit the use of transfer learning in prognostics. In this paper, various deep learning models are used to predict the remaining useful life (RUL) of air compressors. Here, transfer learning is applied by building a separate prognostics model trained on turbofan engines. It has been found that several of the explored transfer learning architectures were able to improve the predictions on air compressors. The research results suggest transfer learning as a promising research field towards more accurate and reliable prognostics.

Effect of different measuring techniques, preservation methods and storage duration on the morphometric measurements of crustacean larvae - Hanafiah Fazhan; Khor Waiho; Mohamad Jalilah; Mhd Ikhwanuddin; Ghazali Azmie; Sabri Muda; Mohd Zaidi Ibrahim; Draman Shuhaimi; Mohd Husin Norainy; Muhammad Allim Jamalludin; Ngah Rusnita (Marine Biology Research, 2021)

Component Velocities and Turbulence Intensities within Ship Twin-Propeller Jet Using CFD and ADV - Yonggang Cui; Wei Haur Lam; How Tion Puay; Muhammad S. I. Ibrahim; Desmond Robinson; Gerard Hamill (Journal of Marine Science and Engineering, 2020)
This study presents the decays of three components of velocity for a ship twin-propeller jet associated with turbulence intensities using the Acoustic Doppler Velocimetry (ADV) measurement and computational fluid dynamics (CFD) methods. Previous research has shown that a single-propeller jet consists of a zone of flow establishment and a zone of established flow. Twin-propeller jets are more complex than single-propeller jets, and can be divided into zones with four peaks, two peaks, and one peak. The axial velocity distribution is the main contributor and can be predicted using the Gaussian normal distribution. The axial velocity decay is described by linear equations using the maximum axial velocity in the efflux plane. The tangential and radial velocity decays show linear and nonlinear distributions in different zones. The turbulence intensity increases locally in the critical position of the noninterference zone and the interference zone. The current research converts the axial momentum theory of a single propeller into twin-propeller jet theory with a series of equations used to predict the overall twin-propeller jet structure.

Mechanisms and Signaling Pathways of Salt Tolerance in Crops: Understanding from the Transgenic Plants - Muhammad Zohaib Afzal; Qi Jia; Aminu Kurawa Ibrahim; Sylvain Niyitanga; Liwu Zhang (Tropical Plant Biology, 2020)

Enhancement of photocatalytic potential and recoverability of Fe3O4 nanoparticles by decorating over monoclinic zirconia - Idrees Khan; Noor Zada; Ibrahim Khan; Muhammad Sadiq; Khalid Saeed (Journal of Environmental Health Science and Engineering, 2020)

In silico predictions on the possible mechanism of action of selected bioactive compounds against breast cancer - Aliyu Muhammad; Babangida Sanusi Katsayal; Gilead Ebiegberi Forcados; Ibrahim Malami; Ibrahim Babangida Abubakar; Amina Isah kandi; Adam Muntaka Idris; Sabi’u Yusuf; Salihu Muktar Musa; Nagedu Monday; Zak-wan Sidi Umar (In Silico Pharmacology, 2020)

Intraperitoneal injections of copper ferrite nanoparticles disturb blood, plasma, and antioxidant parameters of Wistar rats in a sex-specific manner - Hasna Riaz; Rimsha Hashmi; Shairyar Abid; Nisha Shareef; Abida Faqir; Aqsa Amir; Muhammad Saqib Shahzad; Muhammad Shakeel; Saeed Akhtar; Muhammad Naeem Ashiq; Ather Ibrahim; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Investigation of Amounts of Vitamins, Lycopene, and Elements in the Fruits of Opuntia ficus-indica Subjected to Different Pretreatments - Büşra Bakar; Meltem Çakmak; Muhammad Salihu Ibrahim; Dursun Özer; Sinan Saydam; Fikret Karatas (Biological Trace Element Research, 2020)

Principles and approaches of association mapping in plant breeding - Aminu Kurawa Ibrahim; Liwu Zhang; Sylvain Niyitanga; Muhammad Zohaib Afzal; Yi Xu; Lilan Zhang; Liemei Zhang; Jianmin Qi (Tropical Plant Biology, 2020)

Light intensity effects on the growth and biomass production of submerged macrophytes in different water strata - Shuquan Jin; Muhammad Ibrahim; Said Muhammad; Sardar Khan; Gang Li (Arabian Journal of Geosciences, 2020)

Epidemiology, Associated Factors and Treatment Methods of Cutaneous Leishmaniasis Based on Previous Data from 2013 to 2018 in Ilam, Western Iran - Nasrin Rezaee; Vahid Raissi; Ahmad Rajaeipour; Mehdi Nazari; Muhammad Getso; Ali Taghipour; Omid Raiesi; Asmaa Ibrahim (Acta Parasitologica, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Human health risk assessment of heavy metals in raw milk of buffalo feeding at wastewater-irrigated agricultural farms in Pakistan - Zafar Iqbal; Farhat Abbas; Muhammad Ibrahim; Tahir Imran Qureshi; Matin Gul; Abid Mahmood (Environmental Science and Pollution Research, 2020)

Sulfur dioxide removal: An overview of regenerative flue gas desulfurization and factors affecting desulfurization capacity and sorbent regeneration - Muhammad Adli Hanif; Naimah Ibrahim; Aishah Abdul Jalil (Environmental Science and Pollution Research, 2020)

Use of subsurface temperature as a groundwater flow tracer in the environs of Ismailia Canal, Eastern Nile Delta, Egypt - Zenhom El-Said Salem; Mohamed Sobhy Fathy; Abdel-Fattah Ibrahim Helal; Sofia Yahia Afifi; Abdullah Muhammad Attiah (Arabian Journal of Geosciences, 2020)

Knowledge, attitudes, and practices of Egypt’s future physicians towards antimicrobial resistance (KAP-AMR study): a multicenter cross-sectional study - Ahmed Assar; Mohamed Ibrahim Abdelraoof; Mohamed Abdel-Maboud; Kerollos H. Shaker; Amr Menshawy; Asia Hamdy Swelam; Muhammad Eid; Radwa Khalid; Mohamed Mogahed; Abdelrahman I. Abushouk; Lotfi Aleya; Mohamed Abdel-Daim (Environmental Science and Pollution Research, 2020)

Characterization of regional hydrological drought using improved precipitation records under multi-auxiliary information - Zulfiqar Ali; Ijaz Hussain; Muhammad Faisal; Marco Andreas Grzegorczyk; Ibrahim M. Almanjahie; Amna Nazeer; Ishfaq Ahmad (Theoretical and Applied Climatology, 2020)

Leea macrophylla (Roxb.) root extract reverses CCl4 induced liver injury through upregulation of antioxidative gene expression: a molecular interaction for therapeutic inception - Md. Rakibul Hassan Bulbul; Md. Atiar Rahman; Md. Zillur Rahman; Talha Bin Emran; Mirola Afroze; Mala Khan; Muhammad Abid Hasan Chowdhury; Mohammed Auwal Ibrahim; Mohammed Sohel Chowdhury (Advances in Traditional Medicine, 2020)

Urease inhibitory potential of extracts and active phytochemicals of Hypochaeris radicata (Asteraceae) - Tareq Abu-Izneid; Abdur Rauf; Muhammad Saleem; Nashwa Mansour; Mohamed I. S. Abdelhady; Munjed M. Ibrahim; Seema Patel (Natural Product Research, 2020)

Molecular characterization and phylogenetic analysis of Pantoea stewartii subspecies stewartii causing bronzing disease of jackfruit in Malaysia based on cps and hrp gene sequences - Rohaya Ibrahim; Noor Wahida Ismail-Suhaimy; Tan Shu-Qing; Siti Izera Ismail; Nuraizat Abidin; Mansor Hakiman; Daljit Singh Karam; Muhammad Saiful Ahmad-Hamdani; Mohd Termizi Yusof; Dzarifah Zulperi (Journal of Plant Pathology, 2020)

Cytotoxic and Genotoxic Assessment of Silicon Dioxide Nanoparticles by Allium and Comet Tests - Recep Liman; Yaser Acikbas; İbrahim Hakkı Ciğerci; Muhammad Muddassir Ali; Meltem Demirel Kars (Bulletin of Environmental Contamination and Toxicology, 2020)

Functional Annotation and Analysis of Dual Oxidase 1 (DUOX1): a Potential Anti-pyocyanin Immune Component - Muhammad Ibrahim Rashid; Amjad Ali; Saadia Andleeb (Interdisciplinary Sciences: Computational Life Sciences, 2019)

An overview of climate change and variability impact studies in Nigeria - Da’u Abba Umar; Mohammad Firuz Ramli; Ahmad Zaharin Aris; Wan Nor Azmin Sulaiman; Muhammad Amar Zaudi; Abubakar Ibrahim Tukur (Arabian Journal of Geosciences, 2019)

Effects of Rhizophagus clarus and biochar on growth, photosynthesis, nutrients, and cadmium (Cd) concentration of maize (Zea mays) grown in Cd-spiked soil - Mazhar Rafique; Ibrahim Ortas; Muhammad Rizwan; Tariq Sultan; Hassan Javed Chaudhary; Mehmet Işik; Oğuzhan Aydin (Environmental Science and Pollution Research, 2019)

Effects of biochar and NPK on soil microbial biomass and enzyme activity during 2 years of application in the arid region - Muhammad Azeem; Rifat Hayat; Qaiser Hussain; Muhammad Ibrahim Tahir; Muhammad Imran; Zafar Abbas; Muhammad Sajid; Abdul Latif; Muhammad Irfan (Arabian Journal of Geosciences, 2019)

Preliminary Assessment of Stress and Genotoxicity Biomarkers in Bivalve Molluscs from the Gulf of Annaba, Algeria - Fahima Drif; Cherif Abdennour; İbrahim Hakkı Ciğerci; Muhammad Muddassir Ali; Ouarda Mansouri; Mahfoud Messarah (Bulletin of Environmental Contamination and Toxicology, 2019)

Manganese dioxide nanoparticles/activated carbon composite as efficient UV and visible-light photocatalyst - Idrees Khan; Muhammad Sadiq; Ibrahim Khan; Khalid Saeed (Environmental Science and Pollution Research, 2019)

Alleviative role of exogenously applied mannitol in maize cultivars differing in chromium stress tolerance - Ume Habiba; Shafaqat Ali; Muhammad Rizwan; Muhammad Ibrahim; Afzal Hussain; Muhammad Rizwan Shahid; Saud A. Alamri; Mohammed Nasser Alyemeni; Parvaiz Ahmad (Environmental Science and Pollution Research, 2019)

Ecological structure and carbon storage in traditional silvopastoral systems in Nicaragua - Aura Cárdenas; Ana Moliner; Chiquinquirá Hontoria; Muhammad Ibrahim (Agroforestry Systems, 2019)

In situ ruminal degradation and effective degradation of foliage from six tree species during dry and rainy seasons in Veracruz, Mexico - Lidia Ascencio-Rojas; Braulio Valles-de la Mora; Epigmenio Castillo-Gallegos; Muhammad Ibrahim (Agroforestry Systems, 2019)

5,6-dehydrokawain from the rhizome of Alpinia mutica Roxb. induced proangiogenic tumour-derived VEGF of HT-29 colorectal cancer - Ibrahim Malami; Aliyu Muhammad; Ibrahim B. Abubakar; Imaobong C. Etti; Peter M. Waziri; Ramadan M. Abubakar; Halilu E. Mshelia (Natural Product Research, 2018)

Earthworms as plug flow reactors: a first-order kinetic study on the gut of the vermicomposting earthworm Eudrilus eugeniae - Katheem Kiyasudeen; Mahamad Hakimi Ibrahim; Syahidah Akmal Muhammad; Sultan Ahmed Ismail; Fadzil Noor Gonawan; Mark Harris Zuknik (Environmental Science and Pollution Research, 2018)

Dioclins A and B, new antioxidant flavonoids from Dioclea reflexa - Abdulkabir Oladele Oladimeji; Ibrahim Adebayo Oladosu; Muhammad Shaiq Ali; Mehreen Lateef (Natural Product Research, 2018)

Use of Eucalyptus camaldulensis as Biosorbent for Lead Removal from Aqueous Solution - Muhammad Ashraf Sabri; Taleb Hassan Ibrahim; Mustafa Ibrahim Khamis; Sameer Al-Asheh; Muhammad Faheem Hassan (International Journal of Environmental Research, 2018)

Pharmacological mechanisms underlying gastroprotective activities of binapthyl diselenide in Wistar rats - Mohammad Ibrahim; Musadiq Ibrahim; Niaz Muhammad; Muhammad Ishaq Ali Shah; Gerlânia de Oliveira Leite; Joao B. T. Rocha (Inflammopharmacology, 2018)

Genotoxic Assessment of Different Sizes of Iron Oxide Nanoparticles and Ionic Iron in Earthworm (Eisenia hortensis) Coelomocytes by Comet Assay and Micronucleus Test - İbrahim Hakkı Ciğerci; Muhammad Muddassir Ali; Şöhret Yüksek Kaygısız; Bülent Kaya; Recep Liman (Bulletin of Environmental Contamination and Toxicology, 2018)

Correction to: Biochars mitigate greenhouse gas emissions and bioaccumulation of potentially toxic elements and arsenic speciation in Phaseolus vulgaris L. - Muhammad Ibrahim; Gang Li; Sardar Khan; Qiaoqiao Chi; Yaoyang Xu; Yongguan Zhu (Environmental Science and Pollution Research, 2018)

Exhaust emission profiling of fatty acid methyl esters and NOx control studies using selective synthetic and natural additives - Saad Afzal; Muhammad Waseem Mumtaz; Umer Rashid; Muhammad Danish; Muhammad Asam Raza; Ahtasham Raza; Hamid Mukhtar; Saud Ibrahim Al-Resayes (Clean Technologies and Environmental Policy, 2018)

Impact of grazing on soil, vegetation and ewe production performances in a semi-arid rangeland - Muhammad Islam; Abdul Razzaq; Shamim Gul; Sarfraz Ahmad; Taj Muhammad; Sawsan Hassan; Barbara Rischkowsky; M. N. M. Ibrahim; Mounir Louhaichi (Journal of Mountain Science, 2018)

Prevailing trends of climatic extremes across Indus-Delta of Sindh-Pakistan - Farhat Abbas; Iqra Rehman; Muhammad Adrees; Muhammad Ibrahim; Farhan Saleem; Shafaqat Ali; Muhammad Rizwan; Muhammad Raza Salik (Theoretical and Applied Climatology, 2018)

Concurrent vaccination of goats with foot and mouth disease (FMD) and peste des petits ruminants (PPR) booster vaccines - Muhammad Khalid Mansoor; Abdullmajeed Hamood Al-Rawahi; Hatim Ali El-Tahir; Badar Al-Faraei; Muhammad Hammad Hussain; Muhammad Nadeem Asi; Ibrahim Al-Hussani; Safwat Sabar (Tropical Animal Health and Production, 2018)

Suppression of PGE2 production via disruption of MAPK phosphorylation by unsymmetrical dicarbonyl curcumin derivatives - Mohd Fadhlizil Fasihi Mohd Aluwi; Kamal Rullah; Md. Areeful Haque; Bohari M. Yamin; Waqas Ahmad; Muhammad Wahab Amjad; Sze Wei Leong; Nurul Amira Fahmizar; Juriyati Jalil; Faridah Abas; Nor Hadiani Ismail; Ibrahim Jantan; et al. (Medicinal Chemistry Research, 2017)

Impact of socio-demographic factors on the mitigating actions for climate change: a path analysis with mediating effects of attitudinal variables - Muhammad Mehedi Masud; Rulia Akhatr; Shamima Nasrin; Ibrahim Mohammed Adamu (Environmental Science and Pollution Research, 2017)

Assessment of sea water inundation along Daboo creek area in Indus Delta Region, Pakistan - Ibrahim Zia; Hina Zafar; Muhammad I. Shahzad; Mohsin Meraj; Jamil H. Kazmi (Journal of Ocean University of China, 2017)

Nitrogen-regulated changes in total amino acid profile of maize genotypes having contrasting response to nitrogen deficit - Arshid Hussain Ganie; Altaf Ahmad; Peerzada Yasir Yousuf; Renu Pandey; Sayeed Ahmad; Ibrahim M Aref; Muhammad Iqbal (Protoplasma, 2017)

Diurnal thermoregulatory responses in pregnant Yankasa ewes to the dry season in a tropical Savannah - Lukuman Surakat Yaqub; Joseph Olusegun Ayo; Muhammad Umar Kawu; Peter Ibrahim Rekwot (Tropical Animal Health and Production, 2017)

Biochars mitigate greenhouse gas emissions and bioaccumulation of potentially toxic elements and arsenic speciation in Phaseolus vulgaris L. - Muhammad Ibrahim; Gang Li; Sardar Khan; Qiaoqiao Chi; Yaoyang Xu (Environmental Science and Pollution Research, 2017)

Currently used organophosphate and brominated flame retardants in the environment of China and other developing countries (2000–2016) - Nadeem Ali; Khurram Shahzad; Muhammad Imtiaz Rashid; Heqing Shen; Iqbal Mohammad Ibrahim Ismail; Syed Ali Musstjab Akber Shah Eqani (Environmental Science and Pollution Research, 2017)

Does exogenous application of ascorbic acid modulate growth, photosynthetic pigments and oxidative defense in okra (Abelmoschus esculentus (L.) Moench) under lead stress? - Iqbal Hussain; Asif Siddique; Muhammad Arslan Ashraf; Rizwan Rasheed; Muhammad Ibrahim; Muhammad Iqbal; Sobia Akbar; Muhammad Imran (Acta Physiologiae Plantarum, 2017)

Biochar soil amendment on alleviation of drought and salt stress in plants: a critical review - Shafaqat Ali; Muhammad Rizwan; Muhammad Farooq Qayyum; Yong Sik Ok; Muhammad Ibrahim; Muhammad Riaz; Muhammad Saleem Arif; Farhan Hafeez; Mohammad I. Al-Wabel; Ahmad Naeem Shahzad (Environmental Science and Pollution Research, 2017)

Ameliorative effect of synthetic γ-aminobutyric acid (GABA) on performance traits, antioxidant status and immune response in broiler exposed to cyclic heat stress - Naila Chand; Sher Muhammad; Rifat Ullah Khan; Ibrahim Abdullah Alhidary; Zia ur Rehman (Environmental Science and Pollution Research, 2016)

Salt-stress-responsive chloroplast proteins in Brassica juncea genotypes with contrasting salt tolerance and their quantitative PCR analysis - Peerzada Yasir Yousuf; Altaf Ahmad; Ibrahim M. Aref; Munir Ozturk; Hemant; Arshid Hussain Ganie; Muhammad Iqbal (Protoplasma, 2016)

Protein profiling analysis of Gossypium hirsutum (Malvales: Malvaceae) leaves infested by cotton whitefly Bemisia tabaci (Homoptera: Aleyrodidae) - Muhammad Ibrahim; Sumaira Yasmeen; Ghanva Zaman; Li Bin; Fahad Al-Qurainy; Habib-ur-Rehman Athar; Kausar Hussain Shah; Muhammad Khurshid; Muhammad Ashraf (Applied Entomology and Zoology, 2016)

Modulation of antioxidant enzymes in Juniperus procera needles in relation to habitat environment and dieback incidence - Ibrahim M. Aref; Pervaiz R. Khan; Salim Khan; Hashim El-Atta; Abdalla I. Ahmed; Muhammad Iqbal (Trees, 2016)

Response of Datura innoxia Linn. to Gamma Rays and Its Impact on Plant Growth and Productivity - Ibrahim M. Aref; Pervaiz R. Khan; Abdulaziz A. Al Sahli; Azamal Husen; M. K. A. Ansari; Mahmooduzzafar; Muhammad Iqbal (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Anticoccidial effect of mananoligosacharide against experimentally induced coccidiosis in broiler - Naila Chand; Hassan Faheem; Rifat Ullah Khan; Muhammad Subhan Qureshi; Ibrahim A. Alhidary; Alaeldein M. Abudabos (Environmental Science and Pollution Research, 2016)

Gaseous pollutants from brick kiln industry decreased the growth, photosynthesis, and yield of wheat (Triticum aestivum L.) - Muhammad Adrees; Muhammad Ibrahim; Aamir Mehmood Shah; Farhat Abbas; Farhan Saleem; Muhammad Rizwan; Saadia Hina; Fariha Jabeen; Shafaqat Ali (Environmental Monitoring and Assessment, 2016)

Tissue specific metal characterization of selected fish species in Pakistan - Mukhtiar Ahmed; Taufiq Ahmad; Muhammad Liaquat; Kashif Sarfraz Abbasi; Ibrahim Bayoumi Abdel Farid; Muhammad Jahangir (Environmental Monitoring and Assessment, 2016)

Mechanisms of biochar-mediated alleviation of toxicity of trace elements in plants: a critical review - Muhammad Rizwan; Shafaqat Ali; Muhammad Farooq Qayyum; Muhammad Ibrahim; Muhammad Zia-ur-Rehman; Tahir Abbas; Yong Sik Ok (Environmental Science and Pollution Research, 2016)

Amberinone, a new guaianolide from Amberboa ramosa - Muhammad Ibrahim; Iqbal Hussain; Nusrat Hussain; Arruje Hameed; Tahir Farooq; Amjad Hussain; Muhammad Sajid Hamid Akash; Shabbir Hussain (Natural Product Research, 2016)

Mechanisms of silicon-mediated alleviation of drought and salt stress in plants: a review - Muhammad Rizwan; Shafaqat Ali; Muhammad Ibrahim; Mujahid Farid; Muhammad Adrees; Saima Aslam Bharwana; Muhammad Zia-ur-Rehman; Muhammad Farooq Qayyum; Farhat Abbas (Environmental Science and Pollution Research, 2015)

Synthesis and structural elucidation of two new series of aurone derivatives as potent inhibitors against the proliferation of human cancer cells - Aboubaker A. Elhadi; Hasnah Osman; Muhammad Adnan Iqbal; Sharmila K. Rajeswari; Mohamed B. Khadeer Ahamed; Amin M.S. Abdul Majid; Mohd Mustaqim Rosli; Ibrahim Abdul Razak; Aman Shah Abdul Majid (Medicinal Chemistry Research, 2015)

Citric acid enhances the phytoextraction of chromium, plant growth, and photosynthesis by alleviating the oxidative damages in Brassica napus L. - Sehar Afshan; Shafaqat Ali; Saima Aslam Bharwana; Muhammad Rizwan; Mujahid Farid; Farhat Abbas; Muhammad Ibrahim; Muhammad Aamer Mehmood; Ghulam Hasan Abbasi (Environmental Science and Pollution Research, 2015)

Fulvic acid mediates chromium (Cr) tolerance in wheat (Triticum aestivum L.) through lowering of Cr uptake and improved antioxidant defense system - Shafaqat Ali; Saima Aslam Bharwana; Muhammad Rizwan; Mujahid Farid; Sidra Kanwal; Qasim Ali; Muhammad Ibrahim; Rafaqat Ali Gill; Muhammad Daud Khan (Environmental Science and Pollution Research, 2015)

The effect of excess copper on growth and physiology of important food crops: a review - Muhammad Adrees; Shafaqat Ali; Muhammad Rizwan; Muhammad Ibrahim; Farhat Abbas; Mujahid Farid; Muhammad Zia-ur-Rehman; Muhammad Kashif Irshad; Saima Aslam Bharwana (Environmental Science and Pollution Research, 2015)

Membrane protein profiling of Acidovorax avenae subsp. avenae under various growth conditions - Bin Li; Li Wang; Muhammad Ibrahim; Mengyu Ge; Yanli Wang; Shazia Mannan; Muhammad Asif; Guochang Sun (Archives of Microbiology, 2015)

Application of GIS for the identification and demarcation of selective heavy metal concentrations in the urban groundwater - Sobia Ashraf; Farhat Abbas; Muhammad Ibrahim; Umer Rashid; Shoaib Khalid; Hammad Raza Ahmad; Khalid Rehman Hakeem; Tahir Majeed (Journal of Geographical Sciences, 2015)

EDTA enhanced plant growth, antioxidant defense system, and phytoextraction of copper by Brassica napus L. - Ume Habiba; Shafaqat Ali; Mujahid Farid; Muhammad Bilal Shakoor; Muhammad Rizwan; Muhammad Ibrahim; Ghulam Hasan Abbasi; Tahir Hayat; Basharat Ali (Environmental Science and Pollution Research, 2015)

Assessment of groundwater vulnerability to anthropogenic pollution and seawater intrusion in a small tropical island using index-based methods - Nura Umar Kura; Mohammad Firuz Ramli; Shaharin Ibrahim; Wan Nor Azmin Sulaiman; Ahmad Zaharin Aris; Adamu Idris Tanko; Muhammad Amar Zaudi (Environmental Science and Pollution Research, 2015)

Expression patterns of miR-221 and its target Caspase-3 in different cancer cell lines - Sercan Ergun; Kaifee Arman; Ebru Temiz; İbrahim Bozgeyik; Önder Yumrutaş; Muhammad Safdar; Hasan Dağlı; Ahmet Arslan; Serdar Oztuzcu (Molecular Biology Reports, 2014)

Growth, water status, and leaf characteristics of Brassica carinata under drought and rehydration conditions - Azamal Husen; Muhammad Iqbal; Ibrahim M. Aref (Brazilian Journal of Botany, 2014)

Biodegradable Injectable In Situ Implants and Microparticles for Sustained Release of Montelukast: In Vitro Release, Pharmacokinetics, and Stability - Tarek A. Ahmed; Hany M. Ibrahim; Ahmed M. Samy; Alaa Kaseem; Mohammad T. H. Nutan; Muhammad Delwar Hussain (AAPS PharmSciTech, 2014)

Soil organic C and nutrient contents under trees with different functional characteristics in seasonally dry tropical silvopastures - Pere Casals; Johanna Romero; Graciela M. Rusch; Muhammad Ibrahim (Plant and Soil, 2014)

Deciphering the role of Burkholderia cenocepacia membrane proteins in antimicrobial properties of chitosan - Muhammad Ibrahim; Zhongyun Tao; Annam Hussain; Yang Chunlan; Mehmoona Ilyas; Abdul Waheed; Fang Yuan; Bin Li; Guan-Lin Xie (Archives of Microbiology, 2014)

Drought-induced adaptive changes in the seedling anatomy of Acacia ehrenbergiana and Acacia tortilis subsp. raddiana - Ibrahim M. Aref; Abdallah I. Ahmed; Pervaiz R. Khan; Hashim A. El-Atta; Muhammad Iqbal (Trees, 2013)

Antifungal effect and mechanism of chitosan against the rice sheath blight pathogen, Rhizoctonia solani - He Liu; Wenxiao Tian; Bin Li; Guoxing Wu; Muhammad Ibrahim; Zhongyun Tao; Yangli Wang; Guanlin Xie; Hongye Li; Guochang Sun (Biotechnology Letters, 2012)

Characterization of pilP, a gene required for twitching motility, pathogenicity, and biofilm formation of Acidovorax avenae subsp. avenae RS-1 - He Liu; Wen-Xiao Tian; Muhammad Ibrahim; Bin Li; Guo-Qing Zhang; Bo Zhu; Guan-Lin Xie (European Journal of Plant Pathology, 2012)

High-density growth and crude protein productivity of a thermotolerant Chlorella vulgaris: production kinetics and thermodynamics - Shahid Mahboob; Abdul Rauf; Muhammed Ashraf; Tayyaba Sultana; Salma Sultana; Farhat Jabeen; Muhammad Ibrahim Rajoka; H. F. Alkahem Al-Balawi; Khalid A. Al-Ghanim (Aquaculture International, 2012)

Diversity of potential pathogenicity and biofilm formation among Burkholderia cepacia complex water, clinical, and agricultural isolates in China - Muhammad Ibrahim; Qiaomei Tang; Yu Shi; Abdulwareth Almoneafy; Yuan Fang; Liuhu Xu; Wen Li; Bin Li; Guan-Lin Xie (World Journal of Microbiology and Biotechnology, 2012)

Characterization of a thermostable and alkaline xylanase from Bacillus sp. and its bleaching impact on wheat straw pulp - Mahjabeen Saleem; Farheen Aslam; Muhammad Saleem Akhtar; Mohsin Tariq; Muhammad Ibrahim Rajoka (World Journal of Microbiology and Biotechnology, 2012)

Fat-tailed sheep production systems in the Khyber Pakhtunkhwa Province of Pakistan - Muhammad Ibrahim; Sohail Ahmad; Zahoor Ahmad Swati; Ghufran Ullah (Tropical Animal Health and Production, 2011)

Simultaneous perturbation stochastic approximation for tidal models - Muhammad Umer Altaf; Arnold W. Heemink; Martin Verlaan; Ibrahim Hoteit (Ocean Dynamics, 2011)

Heterologous expression of a gene for thermostable xylanase from Chaetomium thermophilum in Pichia pastoris GS115 - Abdul Ghaffar; Sher Afzal Khan; Zahid Mukhtar; Muhammad Ibrahim Rajoka; Farooq Latif (Molecular Biology Reports, 2011)

Using leaf tip necrosis as a phenotypic marker to predict the presence of durable rust resistance gene pair Lr34/Yr18 in wheat - Syed Jawad Ahmad Shah; Shaukat Hussain; Musharaf Ahmad; Farhatullah; Iftikhar Ali; Muhammad Ibrahim (Journal of General Plant Pathology, 2011)

Oxidative stress elevated DNA damage and homocysteine level in normal pregnant women in a segment of Pakistani population - Shazia A. Bukhari; Muhammad Ibrahim Rajoka; Z. Ibrahim; Fatima Jalal; Shahid Mahboob Rana; Saeed A. Nagra (Molecular Biology Reports, 2011)

Diversity of Burkholderia cepacia Complex from the Moso Bamboo (Phyllostachys edulis) Rhizhosphere Soil - Miaomiao Lou; Yuan Fang; Guoqing Zhang; Guanlin Xie; Bo Zhu; Muhammad Ibrahim (Current Microbiology, 2011)

Surface properties and sub-surface aggregate assimilation of rhamnolipid surfactants in different aqueous systems - Zulfiqar Ali Raza; Zafar M. Khalid; Mohammad Saleem Khan; Ibrahim M. Banat; Asma Rehman; Abdul Naeem; Muhammad Tahir Saddique (Biotechnology Letters, 2010)

Purification and characterization of xylanases from Thermomyces lanuginosus and its mutant derivative possessing novel kinetic and thermodynamic properties - Syed Ali Imran Bokhari; Farooq Latif; Muhammad Ibrahim Rajoka (World Journal of Microbiology and Biotechnology, 2009)

Solid-state fermentation-supported enhanced production of α-galactosidase by a deoxyglucose-resistant mutant of Aspergillus niger and thermostabilization of the production process - Muhammad Ibrahim Rajoka; Muhammad Siddique Awan; Mahjabeen Saleem; Najma Ayub (World Journal of Microbiology and Biotechnology, 2009)

Growth, production and carbon sequestration of silvopastoral systems with native timber species in the dry lowlands of Costa Rica - Hernán J. Andrade; Robert Brook; Muhammad Ibrahim (Plant and Soil, 2008)

Production and characterization of a highly active cellobiase from Aspergillus niger grown in solid state fermentation - Muhammad Ibrahim Rajoka; Muhammad Waheed Akhtar; Atif Hanif; A. M. Khalid (World Journal of Microbiology and Biotechnology, 2006)

Structural changes in root and shoot ofBacopa monniera in response to salt stress - Gayoor Ali; A. Arif Ibrahim; Prem Shankar Srivastava; Muhammad Iqbal (Journal of Plant Biology, 1999)